Experimental study on the coupling effects of diesel injection parameters and in-cylinder swirl on the combustion characteristics of methane premixture ignited by pilot diesel - Zechuan Cui; Zhanpeng Wang; Shuo Yin; Yuantao Yu; Mingyuan Ye; Jiangping Tian (Fuel, 2027)

Metagenomic insights into suppressing antibiotic-resistant bacteria in mesocosm-scale constructed wetlands: calamus-biochar alleviates selective pressure and disrupts genetic co-occurrence network - Wei Wu; Yu Wang; Tian-Bao Yang; Xian-Kai Zhang; Bing-Dang Wu; Jin-Long Zhuang; Qian-Yi Cao; Shuo Song; Wei Li; Tian-Yin Huang; Xiao-Yi Xu (Bioresource Technology, 2027)

Three-directional shaking table test of seismic response on twin stacked tunnels consider subway train load in clayey soil - Huayang Lei; Yao Hu; Tianbin Li; Peng Zeng; Shuo Yu (Soil Dynamics and Earthquake Engineering, 2026)

Optimizing dry seeding and wet emergence by integrating winter drip irrigation enhances cotton yield and fiber quality in saline soils of southern Xinjiang - Shuo Wang; Yungang Bai; Jianhui Du; Zheng Fang; Qiying Yu; Mingshen Wang; Zhenlin Lu; Biao Cao; Bangxin Ding; Ming Zheng; Zhenhua Wang; Jianghui Zhang (Soil and Tillage Research, 2026)

Regulation of humeral fracture healing by miR-21 through SMAD7-mediated activation of Wnt/β-catenin signaling - Juan Liu; Hong Ren; Shuo Zhang; Guiyong Yu (Mammalian Genome, 2026)

Integration of transcriptome and mendelian randomization elucidates the protective role of aspirin in pulmonary tuberculosis development - Wei Tan; Li Zhang; Shanmei Wang; Yu Chen; Hanqing Yu; Xinmiao Song; Changwei Wu; Ping Jiang; Shuo Liang (Functional & Integrative Genomics, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Salinity effect on soil organic carbon characteristics and microbial carbon metabolism in coastal wetland of Yellow River Delta - Wenhao Liu; Xinyi Zhang; Zhen Hu; Jian Zhang; Shuo Wang; Yanhui Zhao; Peihan Yu (Journal of Environmental Sciences, 2026)

A high proportion of A2 β-casein in β-casein impairs the gel properties of fermented milk by affecting protein aggregation following heat treatment - Qian Su; Shuo Yang; Miao Wen; Liang-Yu Ma; Xiang-Chen Meng; Wei Yu (Food Hydrocolloids, 2026)

From molecular assembly to functionality: structural characterization of chestnut 11S globulin and its implications for thermal gelation and bioactive peptide release - Haoxin Cui; Ying Zhang; Dongze Qin; Fan Wei; Zhenting Yu; Sihao Wu; Yazhou Ji; Wenhui Fu; Yan Zhang; Ruican Wang; Shuo Wang (Food Hydrocolloids, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

Isolation and pathogenicity of Actinobacillus pleuropneumoniae Serovar 19 in pigs - Bo Hong; Guangyuan Yi; XvDong Lin; YingXuan Ye; XiaoLi Liu; Ahmed H. Ghonaim; Yang Zeng; Shuo Zhang; Ping Bai; Wentao Li; Xuexiang Yu; Qigai He (Veterinary Microbiology, 2026)

Latest Carboniferous subduction initiation of Panthalassa: New evidence from the Yuejinshan Complex, NE China - Qingbin Guan; Yongjiang Liu; Yujia Du; Tong Zhou; Zhaoxu Chen; A. Yu Peskov; Shuo Deng; Boran Liu; Sanzhong Li (Lithos, 2026)

Effect of liquefaction solvent, catalyst sulfidation method and H2S on mild liquefaction behaviors of Jiangna coal over Fe-based catalysts - Jiaqi Yu; Yuxin Wen; Shuo Wang; Rui Zhang; He Yang; Yang Li; Xingxing Xiao; Yining Guan; Haoquan Hu; Lijun Jin (Fuel, 2026)

Dynamic evolution mechanism of carbon oxides during Low-Temperature oxidation and an Early-Warning model for the spontaneous combustion risk of lignite - Zhenshuai Sun; Ning Li; Xianliang Meng; Fan Wu; Ruizhi Chu; Jianqiao Zhao; Shuo Li; Ying Feng; Hengbo Hu; Yihao Sun; Shi Yu (Fuel, 2026)

Surface-engineered Au@Pt nanoparticles-based colorimetric/fluorescent dual-mode three-channel sensor array: Discrimination of light aroma-type Baijiu with variable qualities - Yukun Yang; Jian Liu; Rong Guo; Baoqing Bai; Tao Bo; Jinhua Zhang; Ligang Yu; Huilin Liu; Ying Zhang; Shuo Wang (Food Chemistry, 2026)

Dual regulation of sensory quality and safety in roast beef patties using novel flavor-enhanced salt complexes - Yingshuang Lu; Jin Deng; Sijia Wang; Yuekun Wu; Zhenting Yu; Yuanyifei Wang; Huan Lv; Yan Zhang; Shuo Wang (Food Chemistry, 2026)

Straw return enhances soil multifunctionality and maize yield through shifts in bacterial community structure - Shijie Deng; Yang Yu; Yubo Hao; Yubo Jiang; Guoyi Lv; Yiteng Zhang; Linjing Han; Meng Cheng; Shuo Zhang; Chunrong Qian (Field Crops Research, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Microtopographic differences in CO2 emissions under long-term straw return: The role of microbial resources limitation - Mengmeng Zou; Wantai Yu; Qiang Ma; Yu Ning; Siyu An; Shuo Wang; Zhuqing Xia; Xinhui Zhang; Yun Gao; Mulisa Faji Dida; Shuailin Li (CATENA, 2026)

Built environment constraints on well-being in resource-based cities - Shuo Lu; Feilong Yang; Jianhui Yu; Wenzhong Zhang (Building and Environment, 2026)

24-hour multi-station regional O3 concentration prediction through aggregating neighborhood spatial information - Mengfan Teng; Shuo Wang; Yu Ding; Miao Zhang (Atmospheric Environment, 2026)

Mesoscale research on voltage distribution and chloride ion migration mechanism in SFRC tunnel segment under direct stray current - Shuo Yu; Yao Hu; Chengtao Wang; Linzhi Peng (Tunnelling and Underground Space Technology, 2026)

A high-fidelity and scalable computational platform for large-scale SSI analysis of seismically isolated NPPs - Yu Liu; Jianbo Li; Zhiyuan Li; Xinbo Li; Shuo Feng (Soil Dynamics and Earthquake Engineering, 2026)

AI-2 type quorum-sensing signal enhances mercury resistance and adsorption in thermotolerant Bacillus subtilis - Shuo Han; Qianyun Mo; Xiaobin Wen; Xiangru Wang; Xiangqian Wang; Yao Yu; Yixiao Yang; Chunzhe Yang; Zhonghua Cai; Jin Zhou (Journal of Hazardous Materials, 2026)

Interfacial electro-demulsification of industrial oily wastewater: Challenges from fundamental mechanisms to industrial implementation - Xiangyu Sun; Kun Zhao; Hongtao Yu; Shuo Li; Zhongyu Guo; Junfeng Niu (Environmental Research, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Bridging thermal conduction and EMI shielding in polymer nanofiber-based composites: Mechanisms, structural design, and interfacial engineering - Zhuo Huang; Shuaiyuan Wang; Shuo Xiang; Ding Huang; Xiaolong Yu; Yong Liu; Hai Liu (Chemical Engineering Journal, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Microbial Remediation of Heavy Metal Contamination in Soils: A Meta-Analysis of Immobilization and Extraction Strategies Functions - Zaixing Li; Xiaozhan Zang; Shuo Yu; Chen Yuan; Yali Huang; Shengjun Xu; Xue Qin; Xiaoqing Fu; Nannan Wang; Yan Hu (Biocatalysis and Agricultural Biotechnology, 2026)

Synergistic effects of co-pyrolyzed rice straw/non-woven fabric biochar on soil enhancement and rice growth promotion - Shuo Su; Jiachen Zhu; Tian Xie; Zhihua Zhang; Yi Zhu; Yu Xie; Yuting Ran; Lingling Yao; Jie Qin; Jing Huang; Junxin Zhou; Zhi Zhou; et al. (Paddy and Water Environment, 2026)

Interactive Toxic Impacts of Thermal Stress and Residual Chlorine on Growth, Nutritional Composition and Digestive Physiology in Meretrix meretrix - Shuai Han; Sitong Wang; Haopeng Hu; Wenping Yang; Shuo Qin; Peng Gao; Yanming Sui; Yebing Yu; Mei Jiang; Lei Li (Fishes, 2026)
Thermal elevation and residual chlorine pollution are two anthropogenic stressors that co-occur in estuarine waters affected by coastal power plant effluents. A 30-day exposure experiment was established with six treatment combinations comprising three temperatures (27 °C, 28 °C, and 30 °C) and two residual chlorine concentrations (0 mg/L and 0.02 mg/L) on Meretrix meretrix. Sampling was conducted on days 0, 10, 20 and 30 of the trial. The results indicated that elevated temperature (30 °C) significantly suppressed shell height and total body weight, while residual chlorine (0.02 mg/L) exerted time-dependent effects on shell length and width, with a significant interactive effect on shell length only at day 30. Crude lipid content declined with increasing temperature and residual chlorine exposure, whereas moisture and ash contents showed significant two-way interactions at all sampling time points. Intestinal amylase activity was continuously regulated by both stressors, with interactive responses on days 10 and 20, and was significantly suppressed under combined high temperature and residual chlorine stress. Collectively, we infer that combined exposure to elevated temperature and residual chlorine impairs shell growth, muscle biochemical composition and intestinal amylase activity of M. meretrix. Long-term experiments are required to further clarify the joint toxic effects of thermal stress and residual chlorine on the clam species.

Decoding osteosarcoma mechanobiology: PIEZO channels in tumor progression, immune remodeling, and pain - Baicheng Yang; Zhangfu Li; Jethro Wang Zih-Shuo; Timothy M. Pawlik; Shengji Yu (Cancer and Metastasis Reviews, 2026)

Multi-criteria well-to-wheel sustainability assessment of energy pathways for China’s new energy vehicles - Shuo Zhang; Ji Feng; Hongtao Ren; Yadong Yu (Transportation Research Part D: Transport and Environment, 2026)

Symmetry-breaking engineered for polarization-sensitive bulk photovoltaic effect in b-As/2H-TMDs heterostructures - Xinyun Zhou; Junjie Zhou; Shuo Liu; Chenglin He; Yali Yu; Le Yuan; Ruiying Ma; Qinglin Xia; Le Huang; Ziqi Zhou; Mianzeng Zhong; Zhongming Wei (Science Bulletin, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

The cytokinin oxidase/dehydrogenase MdCKX4 regulates drought tolerance in Malus domestica - Tong Li; Yu-Feng Zhang; Joy Xin-Yue Zhai; Zi-Quan Feng; Shuo Ma; Xin-Yi Li; Huai-Na Gao; Long-Xin Luo; Zhi Li; Qi Zhang; Min-Min Zhou; Ya-Li Zhang; et al. (Plant Science, 2026)

Proximal-distal coordination engineering of iron single-atom nanozyme for synergistic multi-enzymatic-photothermal control of antibiotic-resistant bacteria - Yunsen Wang; Zhichao Yu; Xiuhui Liang; Zhilan Bi; Minglang Zou; Shuo Tian; Da Huang; Zuquan Weng; Dianping Tang; Jinfeng Kong (Journal of Hazardous Materials, 2026)

Decoding the temporal regulome of wheat starch: Wx allelic hierarchy unveils novel negative regulators - Shuo Zhang; Yuyan Zhang; Yu Tian; Liqiang Song; Maria Itria Ibba; Jianxi Bao; Haoyue Liu; Xuhua Li; Andreas Blennow; Aimin Zhang; Xingxun Liu; Dongcheng Liu (Carbohydrate Polymers, 2026)

Soil microbial biogeography: from maps to blueprints - Gui-Feng Gao; Shuo Jiao; Ke Dong; Xu Liu; Xin Xin; Beibei Chen; Kunkun Fan; Yu Shi; Congcong Shen; Teng Yang; Minyu Jing; Siyu Chen; et al. (Soil Ecology Letters, 2026)

Legume identity shapes soil multifunctionality and microbial networks in long-term cereal-based rotations - Shuting Yu; Shuo Li; Jin Yang; Kees Jan van Groenigen; Guiying Jiang; Mengru Wang; Beibei Wang; Fang Liu; Haitao Liu; Xiaolei Jie; Shiliang Liu (Applied Soil Ecology, 2026)

Electrical resistivity tomography for water-bearing structures incorporating the interference distribution pattern of steel arch in tunnels - Lichao Nie; Yu Zhou; Zhicheng Song; Zhi-Qiang Li; Guoan Chu; Shuo Zhang (Acta Geophysica, 2026)

Platelet membrane-fusing MSC-derived apoptotic extracellular vesicles enhanced cardiac repair after ischemia/reperfusion injury - Zhifeng Song; Fangshun Tan; Yu Jiang; Shuo Wang; ZhiYao Wei; Miao Yu; Hongrui Yu; YanXia Tu; Liaoming He; Weixian Yang; Haiyan Qian (Drug Delivery and Translational Research, 2026)

Genome-wide identification and expression analysis of the pectate lyase (PEL) gene family in soybean (Glycine max (L.) Merr. ) - Shuo Wu; Wanqing Du; Yu Han; Zhenggang Wang; Yujuan Gu; Xianlong Ding; Shouping Yang (Genetica, 2026)

Merbecoviruses exploit APN for entry: expanding the receptor toolkit of betacoronaviruses - Yu Wang; Jie Chen; Wanjie Song; Xin-Xin Li; Xing Ma; Qi Cui; Michael Veit; Andres Merits; Marina Gulyaeva; Ivan Sobolev; Xiaofeng Zhai; Xiaoguang Zhang; et al. (Science China Life Sciences, 2026)

Analysis of the Adaptability and Application of Matched-Field Processors for Stationary and Maneuvering Targets in Shallow Water - Zikun Meng; Wen Zhang; Jian Shi; Shuo Liu; Qiankun Yu (Journal of Marine Science and Engineering, 2026)
Passive acoustic localization in complex shallow waters requires algorithms tailored to specific operational constraints. This paper investigates the adaptability, computational efficiency, and statistical performance boundaries of five matched-field processing (MFP) methods—Bartlett, Minimum Variance Distortionless Response (MVDR), Multiple Signal Classification (MUSIC), Reduced Covariance Matrix (RCM), and Rank and Trace Minimization (RTM)—using the Elba-93 sea trial dataset. Error metrics and processing complexities are systematically evaluated across stationary and maneuvering target scenarios. Rigorous non-parametric statistical tests reveal distinct operational boundaries: under stationary conditions dominated by systemic environmental mismatch, energy-based processors guarantee reliable baseline stability. Conversely, under snapshot-deficient dynamic conditions tracking a receding target, standard high-resolution subspace methods become highly vulnerable to trajectory jumps. In such highly dynamic scenarios, adaptive energy-based processors (specifically MVDR) exhibit the most stable tracking continuity and lowest numerical peak errors. Simultaneously, the operational adaptability of subspace methods is improved via covariance matrix reconstruction (CMR). Specifically, the RCM technique effectively decouples unstructured sensor noise, mitigating maximum trajectory deviations and providing a balanced trade-off between computational efficiency and robustness. Statistical evaluations confirm the fundamental performance boundaries in static environments, while highlighting sample-size limitations in highly dynamic scenarios, thereby establishing a realistic, evidence-based benchmark for marine engineering applications.

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

The dynamic mechanism and enhancement effect of carboxymethyl cellulose foam dust suppression: Experimental and simulation evaluation - Xin-xiao Lu; Shuo Wang; Zi-yao Chen; Guan Wang; Long He; Jin-yu Zhang (Process Safety and Environmental Protection, 2026)

Research on hydrodynamic and load characteristics of offshore wind turbine tower during water entry - Yu Yao; Shuo Huang; Hailong Chen; Wenyi Zhu; Yupu Luo (Ocean Engineering, 2026)

Effects of micro/nanoplastics on physiological and biochemical responses at different life history stages of Neopyropia yezoensis - Shuo Wang; Mingyang Zhao; Mengran Yu; Yujun Duan; Guang Yang; Guanyu Chen; Zewei Wang; Xin Wang; Zhihua Feng (Marine Environmental Research, 2026)

Exploring antennal asymmetry in electrophysiological response, behavior, and olfactory gene expression in the diamondback moth, Plutella xylostella (lepidoptera: plutellidae) - Houjun Tian; Shuo Lin; Yueqin Zheng; Ruibin Xu; Yun Yu; Yong Chen; Hui Wei (Journal of Insect Physiology, 2026)

Dual-stage flash–ultrasonic extraction enhances anthraquinone yield and multifunctional bioactivities in Damnacanthus major cell cultures - Shuo Yu; Zhong-Yu Zhou; Yu-Qing Guo; Yue-Jun Hao; Mei-Yu Jin; Mei-Lan Lian (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Delivery technologies for chlorogenic acid: A comprehensive review of carrier platforms, performance, and challenges - Shumeng Hu; Runan Zhao; Shuo Yang; Wei Wang; Songfeng Yu; Xiangbo Zeng (Food Research International, 2026)

Pilot-scale partial denitrification/anammox demonstration of concentrated circulating cooling water and municipal wastewater co-treatment - Shuo Chen; Ruixin Wu; Yu-You Li; Jianyong Liu (Environmental Research, 2026)

Botryosphaeria dothidea: comprehensive understanding of its pathogenicity, resistance mechanisms, and management strategies in apple cultivation - Peng-Liang Han; Hou-Chao Wang; Hao Wu; Shuo-Chen Chai; Si-Qi Xu; Lei Yu; Da-Gang Hu (Planta, 2026)

Overexpression of PagAPX8 promotes poplar growth and enhances tolerance to drought and salt stress - Yuanyuan Shang; Zhaoyang Tian; Yingxin Zhang; Shuo Song; Yu Guo; Zibin Song; Hongling Mo; Kunlin Wang; Yanqiu Zhao; Hongxia Zhang; Lizi Zhao (Plant Cell Reports, 2026)

Highly sensitive H2O2 colorimetric sensing in tumor cells via stable phospholipid-coated CsCu2I3 peroxidase-like nanoenzyme - Jiatong Wang; Yang Yu; Yawen Fan; Sihan Chen; Meiyi Mo; Shuo Yang; Yangyang Zhao; Zixu Zhang; Hongxian Han (Analytica Chimica Acta, 2026)

Vesicle3D: An Integrative Platform for 3D Segmentation and Analysis of Vesicles in Cryo-electron Tomograms - Zheng-Yu Lv; Zhen-Hang Lu; Shuo Liu; Pengcheng Zhou; Pak-Ming Lau; Guo-Qiang Bi; Chang-Lu Tao (Neuroscience Bulletin, 2026)

Isolation of lytic phage and its inhibition of multidrug-resistant Salmonella and its biofilm - Shuqi Wei; Jikun Wu; Luyang Zhou; Changxu Yu; Shuo Yang; Aofei Wang; Xiaoyu Wang; Zhe Yan; Xiaomeng Yue; Yanli Zhu (Veterinary Microbiology, 2026)

Piezo-photocatalysis with BaTiO3 nanorod arrays–Ag nanoparticle composites for the photodegradation of rhodamine B - Yen-Lun Chiu; Thi Nghi Nhan Nguyen; Hsin-Yu Chi; Heng-Jun Lin; Kao-Shuo Chang (Journal of Environmental Chemical Engineering, 2026)

Reliable and interpretable effluent quality prediction in wastewater treatment plants through the integration of physics-informed neural network and deep learning - Zaixing Li; Shuo Yu; Bin Yang; Lina Tang; Nannan Wang (Journal of Environmental Chemical Engineering, 2026)

Interventional mechanisms of antioxidants on flavor profile modification in the fermented egg white powder system - Ru-yi Zhang; Zhi-shuo Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

“Global significant trends and countermeasures pertaining to climate change adaptation: Translating ambition into action post-COP29” - Shuo Liu; Yu-E. Li; Qin Ouyang (Environmental Science & Policy, 2026)

An efficient Mo-doped VS2 cathode material for rechargeable magnesium batteries - Guimiao Wang; Peilin Ran; Jingfei Guan; Baifei Wu; Shuo Wang; Min Liu; Hang Yang; Meilin Chen; Danmei Yu; Bin Zhang; Liyong Gan; Xiaoyuan Zhou (Chemical Engineering Journal, 2026)

Chemical constituents from the roots of Rubus crataegifolius Bunge and their chemotaxonomic significance - Wei Liu; Yu-Li Zhang; Piao Yan; Ze Wu; Meng-Wei Gao; Shuo Tian; Ren-Bo An; Li-Li Jin (Biochemical Systematics and Ecology, 2026)

Antimicrobial resistance analysis of Escherichia coli isolated from foxes in China - Hao Ni; Jiagong Hou; Qing-Yu Hou; Chao Xu; Xue Leng; Xue-Min Li; Ya Qin; Shuo Liu; Meng-Ting Yang; Lu-Yao Tang; Yu-Zhe Sun; Quan Zhao; et al. (Veterinary Research Communications, 2026)

Laver cultivation mitigates zooplankton miniaturization in eutrophic coastal ecosystems - Sen Li; Jieqing Yang; Jinchen Yu; Tao Sun; Shuo Chen; Jin Zhou; Peng Zhang; Hong Huang (Hydrobiologia, 2026)

Sustainable Chicken Manure Valorization in China: An Integrated Environmental and Economic Assessment - Qi Li; Hanqiao Liu; Guoxia Wei; Hanyang Lu; Qiuyu Yu; Shuo Ma (BioEnergy Research, 2026)

Talarombrevisone A, an β -aminopropionate with two polyketide units, isolated from an endophytic fungus Talaromyces brevis - Yun-He Tuo; Zhong-Duo Yang; Jian-Guo Chen; Cui-Juan Xu; Lin-bo Liu; Tian-Kun Zhao; Yue Li; Li-Bin Xia; Shuai Yu; Ai-Hong Zhao; Shuo Li (Natural Product Research, 2026)

Overcoming gastrointestinal mucosal barriers: Mechanistic innovations and technical advances in mucosal targeting strategies for animal oral vaccines - Meijun Yu; Yue Li; Zhaojun Wang; Ping Han; Yanping Jiang; Wen Cui; Yijing Li; Lijie Tang; Shuo Jia; Hongzhe Zhao; Yingying Ma; Jiaxuan Li; et al. (Veterinary Microbiology, 2026)

Occurrence, source identification, and ecological risk assessment of heavy metals in sediments of Beihai Marine Ranching - Yao Guan; Manyu Huang; Bo Yang; Qiongyuan Su; Shuo Yu; Zuhao Zhu; Xianqing Ouyang (Regional Studies in Marine Science, 2026)

Corrigendum to ‘ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection’ [Pesticide Biochemistry and Physiology 220 (2026) 107056] - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

Multiple unmanned surface vehicles formation method for target guard under environmental disturbance - Jia-Jia Fan; Yi-Shuai Zhang; Teng Ma; Yu-Lei Liao; Dong-Hao Xu; Shuo Niu (Ocean Engineering, 2026)

Self-catalyzed NiFe foam anode fabricated via tape-casting for oxygen evolution reaction in anion exchange membrane water electrolysis - Li-Da Chiu; Calvin Leo Putra; Shuo-En Yu; I-Chung Cheng; I-Chih Ni; Chih-I Wu; I-Chun Cheng; Jian-Zhang Chen (Fuel, 2026)

Lactic acid bacteria co-fermentation enhances the hypolipidemic potential of kombucha - Shuo Wang; Yu Su; Jiaxiu Wang; Yuhan Wang; Kaile Feng; Shuai Wang; Jia Yang; Lei Yuan (Food Bioscience, 2026)

Nature-inspired bicontinuous-topology 3D-printed TPMS solar interfacial evaporator - Yifeng Liao; Yizhe Liu; Lin Ren; Yujun Wei; Zhijian Huang; Jing Zhang; Zhongxin Xu; Jianing Wu; Junyang Tao; Shudong Yu; Shuo Wu (Chemical Engineering Journal, 2026)

Rational structuring engineering of a hydrogenation-dominated air electrode with Ag exsolution for reversible protonic ceramic cells - Dong Zhang; Ruinan Wang; Xi Chen; Na Yu; Mengxuan Zeng; Guanzhen Li; Yanya Liu; Meijing Hong; Shuo Zhai; Meng Ni (Chemical Engineering Journal, 2026)

Electric field as a priming trigger reshaping redox network for synergistic perfluorooctanoic acid degradation and humus synthesis during aerobic composting - Yueyi Liu; Zhenchao Wu; Hao Zhang; Xuan Tang; Weige Yao; Ying Yang; Shuo Li; Tong Yang; Jinyu Du; Tingting Xu; Yu Su; Yaqi Huang; et al. (Bioresource Technology, 2026)

Using ChatGPT to Solve Clinical Radiobiology Problems - Che-Wei Su; Kun-Yao Dai; Yu-Jen Chen; Yung-Shuo Kao (Journal of Cancer Education, 2026)

New nor-tirucallane triterpenoid with antitumor activity from Ailanthus altissima (mill.) swingle - Can Liu; Jun-ling Guo; Shuo-yu Zhao; Ning-ning Shi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Unloading Stress Path Effect in Deep Hard Rock Excavation: Model Development and a Case Analysis - Liangjie Gu; Zhaofeng Wang; Dingping Xu; Yangyi Zhou; Shuo Yu; Guoqiang Zhu; Yan Zhang; Jin-Shuai Zhao (Rock Mechanics and Rock Engineering, 2026)

Asymmetric Fe–N3C coordination in Fe single-atom sites boosts electrochemical activation of H2O2 for efficient •OH generation - Shiyan Sun; Peike Cao; Shuo Chen; Hongtao Yu; Yan Su; Xie Quan (Water Research, 2026)

Optimized hybrid deep learning model for accurate prediction of effluent quality in wastewater treatment plants - Li Zaixing; Yu Shuo; Yang Bin; Tang Lina; Wang Nannan (Journal of Environmental Management, 2026)

A tissue-to-blood mRNA classifier enables early detection of gastric cancer risk in precancerous lesions - Wenqian Ma; Honghai Guo; Tao Zheng; Mingchang Miao; Shuo Guo; Jiangao Yu; Ping’an Ding; Qun Zhao (The Science of Nature, 2026)

Endometrial microbiota-dimethylglycine-Treg cell axis affects endometrial receptivity in recurrent implantation failure - Fen-Ting Liu; Ping Zhou; Feng Deng; Bao-Ying Liao; Zi Yang; Di Sun; Heng Pan; Yang Yu; Shuo Yang; Rong Li (Science China Life Sciences, 2026)

Ex vitro rooting of Spathiphyllum cannifolium in a microponic system: optimization of key physicochemical factors - Peng-Yu Zhang; Xue-Han Zong; Shuo Yu; Yin-Ji Jiang; Xin-Mei Jin; Song-Hao An; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Integrated physiological and transcriptomic analysis revealed key genes and pathways related to continuous drought and salinity stress in Populus - Heng Zhang; Meng Wang; Xizhuo Xing; Dong Zeng; Xuanchen Liu; Zhanqi Ren; Shuo Yu; Hongfei Liu; Songjia Yu; Chenguang Zhou; Guanzheng Qu (Plant Cell Reports, 2026)

Immunomodulatory effects and gut microbiota modulation by brewer’s yeast mannatide in cyclophosphamide-induced immunosuppression mice - Shuang Zhao; Haidi Wang; Shuo Zhao; Jia Yu; Yuxi Wei (Archives of Microbiology, 2026)

Glymphatic system-dependent mechanisms connecting sudden sensorineural hearing loss to cognitive and emotional impairments - Zi-Huai Fang; Wei-Jie Ye; Shuo Li; Biao Li; Yu-Chen Chen; Richard Salvi; Xiao-Min Xu; Xin-Dao Yin (Brain Imaging and Behavior, 2026)

A generative AI-Driven framework integrating CNN-VLM-LLM for intelligent crop disease diagnosis and control strategy generation - Shuo Yang; Junxian Guo; Jiangtong Yu (Computers and Electronics in Agriculture, 2026)

Diversity loss of soil microbiome stimulates soil carbon emissions - Haibo Pan; Yingyi Fu; Hairong Tu; Yongxing Cui; Beibei Chen; Jiejun Qi; Ziheng Peng; Shi Chen; Chunling Liang; Jiai Liu; Xiaomeng Li; Min Gao; et al. (Soil Biology and Biochemistry, 2026)

The cytochrome P450 protein AtCYP85A2 increases stresses tolerance through promoting brassinosteroid biosynthesis in transgenic tomato - Yuanyuan Shang; Zhaoyang Tian; Kaifeng Lu; Yu Guo; Shuo Song; Zibin Song; Hongling Mo; Lizi Zhao; Hongxia Zhang; Yanqiu Zhao (Plant Science, 2026)

Blending global linearization with local learning: A Koopman neural framework for interpretable modeling and control of USV - Wenhao Yu; Jiucai Jin; Deqing Liu; Shuo Ding; Ligang Li (Ocean Engineering, 2026)

Investigating effects of elastic circular support arms on the aeroelastic response for offshore vertical axis wind turbines - Yu Yao; Shuo Huang; Kai Wang; Fenghua Zhou; Mengshang Zhao (Ocean Engineering, 2026)

Precambrian crustal evolution of the southern margin of the North China Craton: Evidence from the Paleo–Mesoproterozoic sedimentary rock - Shuo Wang; De-Bin Yang; Xiang-Yu Yan; Ke Wu; Jian-Ning Liu; Rui-Qing Xue (Journal of Asian Earth Sciences, 2026)

Responses of a harmful algal bloom-causing dinoflagellate Karenia mikimotoi to elevated temperature and high N:P ratio - Xiang Ye; Wen-Jing Sun; Wei-Ping Zhang; Yang Zhou; Shuo-Yu Zhang; Can-Jun Cai; Shu-Feng Zhang; Jae-Seong Lee; Minghua Wang; Da-Zhi Wang (Harmful Algae, 2026)

Competitive adsorption and temperature-dependent diffusion of O2/CO/CO2 in oxidized coal: Implications for coal spontaneous combustion - Yang Zhou; Shuo Li; Lulu Fan; Ruizhi Chu; Xianliang Meng; Ning Li; Haichen Liu; Xiaofeng Jiang; Yongzhou Wan; Shi Yu; Jingbo Li; Xiaomeng Du (Fuel, 2026)

Smartphone-assisted portable colorimetric detection of Salmonella based on a dual signal amplification mediated nanozyme cascade aptasensor - Qing Kang; Chenjing Ma; Yidi Liu; Xin Yu; Tong Lin; Jingbo Jiao; Yukun Huang; Shuo Wang; Xinjun Du (Food Bioscience, 2026)

Structural determinants of physicochemical properties and digestibility of chestnut (Castanea mollissima Blume) starches: Implications for functional and nutritional optimization - Zhenting Yu; Nan Ma; Fan Wei; Haoxin Cui; Jin Deng; Ruican Wang; Bowei Zhang; Yan Zhang; Yingshuang Lu; Shuo Wang (Food Hydrocolloids, 2026)

Comparative assessment of physicochemical and functional properties of chestnut protein obtained by different extraction methods - Haoxin Cui; Yazhou Ji; Yawei Chang; Zhenting Yu; Fan Wei; Bowei Zhang; Yingshuang Lu; Yan Zhang; Ruican Wang; Shuo Wang (Food Hydrocolloids, 2026)

FSMP storage stability: Comparing MASLT & GSI shelf-life models - Hong Yang; Ling Hou; Wei Guo; Mengxi Yu; Hongmei Sun; Shuo Zhang; Fang Yu; Hui Xiao; Liyuan Liu; Shuhong Ye (Food and Bioproducts Processing, 2026)

Seamless hourly PM2.5 mapping across China with a graph spatiotemporal deep neural network - Mengfan Teng; Miaomiao Liang; Shuo Wang; Yu Ding (Environmental Modelling & Software, 2026)

Intranasal biomimetic vesicle platform reprograms the glioblastoma microenvironment for enhanced immunotherapy - Shuo Li; Chao Qin; Fan-Yu Qian; Jin-Hao Wang; Xiang-Gui Wu; Wen-Qing Li; Tai-Yu Liu; Zhao-Jie Chen; Bei-Yuan Zhang; Qi-Yue Liu; Li-Sha Liu; Li-Fang Yin (Chemical Engineering Journal, 2026)

Decoupling multicellular activation circuits: MPDA-mediated co-delivery of quercetin/simvastatin for potent hepatic fibrosis reversal - Lu Zhang; Huan Shen; Boheng Liu; Tingting Liu; Yun Mei; Bin Li; Yang Liu; Gang Cao; Shuo Yu (Chemical Engineering Journal, 2026)

Automatic Detection of Disaster-Causing Organisms near the Waters of Nuclear Power Plant Based on LiveScope Scanning Sonar Images - Gangyi Yu; Shuo Wang; Wei Liu; Yongjian Xia; Yuchen Guo; Xiaolu Chen; Xueping Wei; Ao Chen; Zehua Lv; Chao Lu; Junbo Zhang; Rong Wan (Journal of Marine Science and Engineering, 2026)
Nuclear power serves as an efficient, clean, and low-carbon energy source that constitutes a significant component of the energy portfolio in numerous countries. Most nuclear power plants are predominantly situated in coastal regions, utilizing seawater as the ultimate heat sink for their cooling systems. Real-time monitoring of marine organism dynamics near water intakes is essential to mitigate the risk of unit shutdowns triggered by outbreaks of disaster-causing organisms (DCOs). This study employed LiveScope scanning sonar videos captured near the Ningde Nuclear Power Plant to develop a dataset for detecting the light spot area of the DCOs. We proposed a directionally optimized model, Bio-YOLO v7, which significantly enhances the detection of small targets in sonar images. The Bio-YOLO v7 model achieved precision, recall, and average precision rates of 85.29%, 83.28%, and 81.49%, respectively, demonstrating superior performance in identifying DCOs near the intakes of nuclear power plant. The light spot size of the DCOs exhibited significant periodic variations, serving as a crucial indicator for forecasting outbreak events.

Chronic social defeat stress accelerates lung cancer progression and induces hippocampal metabolic dysregulation in a duration-optimized comorbid model - Xiao-yu Liu; Shuo Wang; Yu-long Li; Jia Lu; Zheng Zhang; Jia-bin Zheng; Li-qun Jia (Metabolic Brain Disease, 2026)

Reinforcement-Learning-Based Adaptive PID Depth Control for Underwater Vehicles Against Buoyancy Variations - Jian Wang; Shuxue Yan; Honghao Bao; Cong Chen; Deyong Yu; Jixu Li; Xi Chen; Rui Dou; Yuangui Tang; Shuo Li (Journal of Marine Science and Engineering, 2026)
Underwater vehicles performing sampling tasks often encounter significant buoyancy variations due to payload adjustments and environmental changes, which severely challenge the stability and accuracy of controllers. To address this issue, this paper proposes a hybrid control framework that integrates Proximal Policy Optimization (PPO) with adaptive PID tuning. The framework employs PPO to dynamically adjust PID parameters online while incorporating output saturation, stepwise quantization, and dead zone filtering to ensure control safety and actuator longevity. A dual-error state representation—combining instantaneous error and its derivative—along with actuator command buffering is introduced to compensate for system lag and inertia. Comparative simulations and experimental tests demonstrate that the proposed method achieves faster convergence, lower steady-state error, and smoother control signals compared to both conventional PID and pure PPO-based control. The framework is validated through pool tests and field trials, confirming its robustness under realistic hydrodynamic disturbances. This work provides a practical and safe solution for adaptive depth control of sampling-capable AUVs operating in dynamic underwater environments.

Seasonal dynamics of plankton networks and copepod selection strategies in the laver cultivation area of Haizhou Bay, China: based on sparse correlations for compositional data analysis - Sen Li; Hong Huang; Jinchen Yu; Tao Sun; Shuo Chen; Jin Zhou; Yunrong Shi; Peng Zhang; Jieqing Yang (Marine Environmental Research, 2026)

Fourth-order kinetic model optimization and activation energy prediction for typical municipal solid waste components combustion - Yu Wang; Shuo Ma; Kexun Wang; Zhipeng Zhou; Hongting Ma (Journal of Environmental Chemical Engineering, 2026)

Tectonic and climate control on the stratigraphic cycles in a Late Paleozoic evaporitic basin in NW China - Kuanhong Yu; Shuo Du; Yingchang Cao; Zi Wang (Journal of Asian Earth Sciences, 2026)

Study on the suppression and CO elimination effect of Co3O4 catalyst on coal dust-methane mixed explosion - Xiaoyu Chen; Yating Liu; Jiaxin Shi; Bingjie Wang; Shuo Gao; Junyi Li; Xuan Xu; Jian Li; Yu Zhang; Chuyuan Liu; Jiahao Li; Mingya Wen; et al. (Fuel, 2026)

Investigation of water and oxygen influence on the coal thermal decomposition entire process kinetic mechanism and gas product source tracing - Xin-xiao Lu; Guo-yu Shi; Rui-nan Zhang; Shuo Wang; Long He; Guan Wang (Fuel, 2026)

From aroma to off-flavor: Metabolomics unveils the metabolic double-sided nature of traditional Chinese fermented foods - Wei Ruan; Jiayu Liu; Huanxin Guo; Shuo Yang; Mengmeng Niu; Hang Yu; Xiangchen Meng (Food Chemistry, 2026)

Data-driven optimization of a polarity-reversing electrooxidation-electrocoagulation system for simultaneous nitrogen and phosphorus removal - Ye Tian; Kongrui Yu; Xinyi Zhu; Luowei Pei; Songming Zhu; Shuo Wang; Zhangying Ye (Desalination, 2026)

Feasibility of direct co-firing centimeter-scale straw in pulverized coal boilers: Experimental and modeling study - Haoteng Zhang; Lihui Yu; Cuina Qin; Shuo Jiang; Chunjiang Yu (Chemical Engineering Journal, 2026)

Decoupling volume shrinkage from dehydration in hydrogels via hierarchical structural design for sustained cushioning and humidity regulation - Yilin Yu; Yong Zheng; Shuo Sun; Xiang Wu; Zhengjin Wang (Chemical Engineering Journal, 2026)

Synergistic engineering of a whole-cell catalyst immobilized on bimetallic CaZn-MOF for efficient PET Depolymerization - Yun-kang Chang; Xiao-huan Liu; Nan-Li; Jun-li Jin; Hai-tong Sun; Shuo Li; Fei-fei Zhang; Yu-xuan Song; Xin-hong Yu; Qi-zhi Cao; Fei Liu; Na Xu; et al. (Chemical Engineering Journal, 2026)

Development and performance analysis of novel thermochemical recuperation reactor based on foam metal monolithic catalyst and reinforced fins - Shuo Gao; Taixiu Liu; Shuzhan Ye; Binhui Yu; Junnan Zhan; Yu Fang; Qibin Liu; Hongguang Jin (Chemical Engineering Journal, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

Implications of phase information from GPS and GRACE(FO) for identifying GPS stations influenced by poroelastic deformation - Fei Lin; Yu Sun; Natthachet Tangdamrongsub; Shuo Zheng; Bao Zhang (Journal of Geodesy, 2026)

Investigation of a hybrid neural network framework for CHF prediction in a wire-wrapped rod bundle - Wei Zhang; Junsen Fu; Shuo Chen; Lijun Yu; Yao Xiao; Hanyang Gu (Annals of Nuclear Energy, 2026)

Cloud numerical computing: Informative support calculation for railway tunnels using data-driven numerical simulation and blocking sub-threaded HTTP protocol - Shuo Yuan; Li Yu; Hao Zhong; Ming-Nian Wang; Si-Ming Tian (Tunnelling and Underground Space Technology, 2026)

Biocontrol mechanisms, application potential, and challenges of Burkholderia spp. in plant fungal disease management - Abdulhamid Yusuf; Jinyan Yu; Bashir Abdullahi; Amina Musa Gumel; Sadiq Bishir; Yahaya Ibrahim Aliyu; Min Li; Shuo Duan; Yunzeng Zhang (Pesticide Biochemistry and Physiology, 2026)

Strain energy calculation and differential evolution in deep hard rocks under different true triaxial unloading paths with cyclic loading - Liangjie Gu; Guo-Qiang Zhu; Shaojun Li; Shuo Yu; Yangyi Zhou; Yan Zhang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Characterization of atmospheric cadmium deposition and its simulated combined toxicological effects on wheat (Triticum aestivum L.) seedlings with sulfamethoxazole in soil - Yun Gao; Shuailin Li; Yu Ning; Xinhui Zhang; Zhuqing Xia; Mengmeng Zhu; Shuo Wang; Wenzhi Huang; Qiang Ma; Wantai Yu (Environmental Pollution, 2026)

Potential Probiotic Lacticaseibacillus rhamnosus NKU FL1-11 Prevents Aging-Related Oxidative Stress and Inflammation via mTOR and FoxO Signaling Pathways in Zebrafish - Dan Li; Xiang Gao; Weiye Liu; Yu Jiang; Yingshuang Lu; Yan Zhang; Huan Lv; Shuo Wang (Probiotics and Antimicrobial Proteins, 2026)

Single-Cell RNA Sequencing Reveals Impaired CHIP-Mediated Heat Stress Response in SCA3 Pathogenesis - Mi-bo Tang; Shi-feng Sheng; Zheng-wei Hu; Hai-yang Luo; Meng-jie Li; Shuo Zhang; Xiao-yan Hao; Cheng-yuan Mao; Shao-hua Li; Hui-fang Sun; Zhi-hua Yang; Yi Song; et al. (Molecular Neurobiology, 2026)

Ecological characteristics and carrying capacity analysis of marine ranching ecosystem in Beibu Gulf based on Ecopath model - Cheng Cheng; Haolin Yu; Jie Feng; Yan Li; Qingxian Cao; Li Liu; Cheng Yang; Shan Zhao; Shuo Li; Zhen Zhang; Haiyan Wang; Tao Zhang (Journal of Oceanology and Limnology, 2026)

Intercropping maize and soybean promotes specialized soil microbial communities and boosts carbon and nitrogen cycling in a semi-arid agroecosystem - Olatunde Pelumi Oladele; Shuo Yao; Ming-Zhu Huang; Yu-Gang Tian; Xin Zhao; Yash Pal Dang; Wei Bai; Hai-Lin Zhang (Applied Soil Ecology, 2026)

EVCBiLNet: Carbon Emission forecasting Model Based on CNN-BiLSTM and Secondary Feature Decomposition - Shuo Feng; Yu Gu; Yanyan Zhao; Lei Chen; Xu Tang; Xinkai Qiao; Danli Wang (Emission Control Science and Technology, 2025)

Evaluation of quinazolin-4(3H)-one derivatives containing the bioactive acetohydrazide group as fungicidal candidates - Wenfei Zhang; Jiacheng Liu; Sifei Qi; Zihan Li; Yiwen Chen; Yufei Gong; Xiangkun Luo; Shuo Wang; Feng Liu; Yu-Cheng Gu; Xuewen Hua (Pesticide Biochemistry and Physiology, 2025)

Global inertial permeability for non-Darcian flow in porous media with different shape configurations - Fu-Shuo Gan; Jia-Qing Zhou; Liangqing Wang; Changdong Li; Xin-Yu Jiang; Yinbin Zhu (Journal of Hydrology, 2025)

Enhanced degradation of carbamazepine in water by a chitosan-supported tea polyphenols/nano-zero-valent iron system: Mechanistic insights and toxicological risk assessment - Weiwei Yu; Yuanxin Liu; Jianglin Tan; Yue Liang; Jiang Hu; Qing Tu; Shuo Yang; Ji Li; Sikai Zhao; Yang Liu; Xinyan Li; Yan Luo; et al. (Journal of Cleaner Production, 2025)

Combustion behavior and activation energy prediction for typical components of municipal solid waste (MSW) - Yu Wang; Shuo Ma; Kexun Wang; Zhipeng Zhou; Yutong Wang; Hongting Ma (Journal of Environmental Management, 2025)

Production of cellulose nanocrystals from waste Phellinus igniarius substrate by enzymatic hydrolysis-centrifugal fractionation method: Construction of a bioactive substance delivery system - Shuo Zhang; Shuang Guo; Jiayu Han; Zhaolian Han; Hailing Yu; Xue Zhang; Ningcan Ma; Zhiqiang Cheng (Food Research International, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

NADPH oxidase-mimicking nanozyme for disulfidptosis-induction strategy to amplify cuproptosis in cancer therapy - Juan Ruan; Chen Li; Yu Wang; Chunhui Wang; Xinda Yang; Chuansheng Xu; Yan Gao; Song Hu; Shuo Shi (Chemical Engineering Journal, 2025)

G Proteins-Associated Dose-Dependent Effects of Oxytocin on Oxytocin Neuronal Activity and Astrocytic Plasticity of the Supraoptic Nucleus - Xiao-Yu Liu; Shuo Ling; Yang Liu; Yunhao Jiang; Xiaoran Wang; Shuwei Jia; Chunmei Hou; Yanpeng Li; Delai Qiu; Yu-Feng Wang (Molecular Neurobiology, 2025)

Study on the spatial relationship between potential and actual rockbursts in a deeply buried hard rock tunnel - Wen-shuo Duan; Chun-an Tang; Tian-hui Ma; Xiao-yu Zhang; Ming-zhe Wang; Shuo-heng Yu; Kai-kai Wang; Yan-yan Pang; Xin Liang; Shichao Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Scalable production of Actinidia arguta adventitious roots in air-lift bioreactors and their antibacterial efficacy against Staphylococcus aureus - Wen Jiang; Xue-Han Zong; Song-Hao An; Jing-Run Xiu; Shuo Yu; Ke-Xin Zhang; Yue-Jun Hao; Mei-Yu Jin (In Vitro Cellular & Developmental Biology - Plant, 2025)

Greenhouse cultivation induced soil profile acidification, altered carbon sequestration and bacterial communities in natural barren land: A case study on the Qinghai-Tibet Plateau - Shuo Wang; Shuailin Li; Kai Zhang; Xiuli Zeng; Takuma Koyama; Arthur Lewis; Wantai Yu; Qiang Ma (Applied Soil Ecology, 2025)

Investigating lifetime characteristics of low-latitude ionospheric F-region irregularities using single-station GNSS data - YunZe Lu; Tao Yu; Yu Liang; Shuo Liu; ZuKang Dai; YiFan Qi; Yan Yu (Advances in Space Research, 2025)

IMM-DeepSort: An Adaptive Multi-Model Kalman Framework for Robust Multi-Fish Tracking in Underwater Environments - Ying Yu; Yan Li; Shuo Li (Fishes, 2025)
Multi-object tracking (MOT) is a critical task in computer vision, with widespread applications in intelligent surveillance, behavior analysis, autonomous navigation, and marine ecological monitoring. In particular, accurate tracking of underwater fish plays a significant role in scientific fishery management, biodiversity assessment, and behavioral analysis of marine species. However, MOT remains particularly challenging due to low visibility, frequent occlusions, and the highly non-linear, burst-like motion of fish. To address these challenges, this paper proposes an improved tracking framework that integrates Interacting Multiple Model Kalman Filtering (IMM-KF) into DeepSORT, forming a self-adaptive multi-object tracking algorithm tailored for underwater fish tracking. First, a lightweight YOLOv8n (You Only Look Once v8 nano) detector is employed for target localization, chosen for its balance between detection accuracy and real-time efficiency in resource-constrained underwater scenarios. The tracking stage incorporates two complementary motion models—Constant Velocity (CV) for regular cruising and Constant Acceleration (CA) for rapid burst swimming. The IMM mechanism dynamically evaluates the posterior probability of each model given the observations, adaptively selecting and fusing predictions to maintain both responsiveness and stability. The proposed method is evaluated on a real-world underwater fish dataset collected from the East China Sea, comprising 19 species of marine fish annotated in YOLO format. Experimental results show that the IMM-DeepSORT framework outperforms the original DeepSORT in terms of MOTA, MOTP, and IDF1. In particular, it significantly reduces false matches and improves tracking continuity, demonstrating the method’s effectiveness and reliability in complex underwater multi-target tracking scenarios.

Novel insights into quorum-sensing microbe combined with dimethylsulfoniopropionate enhancing bioremediation of oil-contaminated sediment under typical deep-sea conditions: The performances and molecular mechanisms - Shugang Hu; Shijie Li; Lingzhe Wang; Shuo Wang; Dongle Cheng; Jianliang Xue; Yu Gao; Siheng Lin; Chengbo Li; Yanlu Qiao; Yuyang Liu (Marine Pollution Bulletin, 2025)

Study on multi phase flow characteristics and anti-clogging mechanism of liquid fertiliser distributors using CFD-DEM coupling method - Peijie Guo; Jiahui Yu; Peilin Zhong; Yuxiang Chen; Haiying Wang; Yu Chen; Jun Chen; Shuo Zhang; Aiping Xiao (Biosystems Engineering, 2025)

From innovation to sustainability: How does the birth of innovative enterprises affect urban carbon emission intensity in China? - Tianheng Shu; Xia Liao; Shuo Yang; Guangyu Cheng; Taofang Yu (Sustainable Cities and Society, 2025)

Distribution and ecological risks of Per- and polyfluoroalkyl substances in constructed wetland: Field-scale case study - Wenhao Liu; Shuo Wang; Qian Zhao; Peihan Yu; Zizhang Guo; Huijun Xie; Jian Zhang; Zhen Hu (Journal of Water Process Engineering, 2025)

Assessing the effectiveness of non-point source pollution models in data-limited urban areas - Fangze Shang; Sijie Tang; Hantao Wang; Ruiyi Yang; Zhiqiang Hou; Yang Ping; Zhenzhou Zhang; Huayu Chen; Yange Yu; Ashantha Goonetilleke; Changhyun Jun; Xin Tian; et al. (Journal of Hydrology, 2025)

Responses of a harmful algal bloom-causing dinoflagellate Prorocentrum obtusidens to elevated temperature and urea - Wei-Ping Zhang; Yang Zhou; Wen-Jing Sun; Shuo-Yu Zhang; Shu-Feng Zhang; Jae-Seong Lee; Minghua Wang; Da-Zhi Wang (Harmful Algae, 2025)

Integration LC-MS/MS and molecular modeling techniques to elucidate the molecular mechanisms of goat whey protein-IgG interactions - Hongbo Li; Quan Gao; Xianjun Gao; Geng Long; Meng Bian; Shuo Feng; Shanbo Mu; Hongjuan Li; Jinghua Yu (Food Chemistry, 2025)

Investigation of the matrix effects on structural stability and application performance of aptamers: Insights from tetrodotoxin detection in typical seafood - Yu Li; Shuo Qi; Peifang Chen; Mingwei Qin; Ning Ding; Chifang Peng; Zhouping Wang (Food Chemistry, 2025)

Synergistic air pollution and CO2 emission reduction in China's iron and steel industry based on real-time monitoring data - Ling Tang; Qing Yu; Jiabao Qu; Ruxing Wan; Min Jia; Shuangyue Qian; Song Lv; Jieyi Li; Shuo Qi (Environmental Pollution, 2025)

Large-area epitaxial hexagonal boron nitride films demonstrating enhanced deep-ultraviolet photodetection enabled by defect suppression under N-rich growth environment - Le Chen; Shuo Wang; Ze Long; Kexiong Zhang; Jinqiang Yu; Hongwei Liang; Hong Yin (Chemical Engineering Journal, 2025)

Synergistic effect of carbon defects and iron active sites in biochar-activated peroxymonosulfate for acetaminophen degradation: Unlocking the non-radical mechanisms - Xuchao Sun; Kaizhen Wu; Gui Yang; Fang Shen; Shiping Zhang; Tingwei Wu; Shuo Sun; Yu Jiang; Xiaoyong Wu (Chemical Engineering Journal, 2025)

ISRIB-loaded nanoplatform disrupts cellular homeostasis by depleting glutathione and inhibiting stress granules formation to drive immunosuppressive reprogramming - Yu Wang; Zhongqi Cui; Yang Wang; Chunhui Wang; Yue Zhang; Nan Huang; Xinda Yang; Fenyong Sun; Sufeng Qiang; Shuo Shi; Bing Shen (Chemical Engineering Journal, 2025)

Boosting power output of NH3BH3 fuel cell by modulating H* and OH− adsorption via Cu@Pd core-shell structured nanowire arrays - Shuo Bi; Libo Zhu; Han Tian; Fantao Kong; Xu Yu; Qin Li; Xiangzhi Cui; Jianlin Shi (Chemical Engineering Journal, 2025)

Unveiling dynamics of microbial communities, species interactions, and ecological assembly during low-temperature-induced sludge bulking in full-scale wastewater treatment systems - Han-Jun Sun; Xian Zhao; Jie Ding; Yu-Qian Wang; Wen-Shuo Wang; Zhi-Hua Feng; Sha Zhao; Liang Wang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2025)

Optimizing flash extraction process of Eurycoma longifolia adventitious roots and evaluating antibiofilm effect - Ling-Hong Bai; Zhong-Yu Zhou; Shuo Yu; Liang-Liang Liu; Yue-Jun Hao; Mei-Lan Lian (Biocatalysis and Agricultural Biotechnology, 2025)

Multidirectional interstitial flow promotes microvascular network formation: insights from a square chip-based platform - Qihang Yang; Yuening He; Shuo Wang; Zengting Li; Jiaxuan Wang; Zehao Sun; Wenbo Yang; Xiang Zhong; Bo Peng; Zaozao Chen; Zhongze Gu; Dan Zhu; et al. (Angiogenesis, 2025)

Parametric dynamic responses analyses of subway station structure surrounded by saturated soft interlayer - Xue-lei Cheng; Sheng-hui Feng; Shuo-shuo Guo; Xiao-fan Xing; Lu-yun Guo; Zhong-yu Zhu (Applied Geophysics, 2025)

A lightweight method for apple disease segmentation using multimodal transformer and sensor fusion - Yihong Song; Manzhou Li; Zizhe Zhou; Jiahe Zhang; Xiangge Du; Min Dong; Qinhong Jiang; Che Li; Yuantao Hu; Qiulin Yu; Dongmei Wang; Hegan Dong; et al. (Computers and Electronics in Agriculture, 2025)

Immunoregulation and antibacterial effect of IFNf for Mycobacterium marinum infection in Chinese sturgeon (Acipenser sinensis) - Peipei Yu; Guangyi Ding; Simei Hu; Keli Gong; Shuo Yang; Kai Luo; Xincheng Jiang; Shuhuan Zhang; Dingda Xu; Qiaoqing Xu; Mei Liu (Aquaculture, 2025)

Effects of the lpfD gene on biofilm formation in Salmonella - Shuo Yang; Jing Gao; Changxu Yu; Fahui Song; Jikun Wu; Luyang Zhou; Shuqi Wei; Aofei Wang; Yanli Zhu (Veterinary Microbiology, 2025)

Transformation of waste PET into bimetallic MOF materials for photothermal interfacial evaporation - Meng Wang; Qingbo Yu; Shuo Yang; Guoqiang Wang; Xiujuan Feng (Journal of Environmental Chemical Engineering, 2025)

Pilot test study on a new physical treatment method for the electric desalting wastewater - Binghe Li; Shaoxuan Li; Yu Li; Haonan Liu; Shuo Huang; Qiang Yang; Yiqian Liu (Journal of Environmental Sciences, 2025)

Nitrogen addition decouples the microbial necro-mass from soil organic carbon formation in a temperate grassland - Huanhuan Cheng; Yingbin Li; Shuo Li; Tianran Sun; Guoxiang Niu; Qi Li; Junjie Yang; Yanxia Ma; Yingzhi Gao; Qiang Yu; Haitao Zhao; Qiushi Ning; et al. (Journal of Environmental Sciences, 2025)

Variations in quality attributes of cow and goat milk subjected to microwave and high-pressure treatments over a two-week storage period - Nina Ding; Qiyue Sun; Zhongna Yu; Qijing Du; Rongbo Fan; Guangxu Ren; Liangliang You; Shuo Feng; Yongxin Yang; Rongwei Han (Innovative Food Science & Emerging Technologies, 2025)

Sensitive dual detection of N-nitrosodiphenylamine and N-nitrosodiethylamine using a PtNPs-enhanced MWCNTs/Fe-porphyrinic MOF nanocomposite-based electrochemical sensor - Jiachen Zhao; Yue Zou; Junlan Yu; Chao Wang; Yili Hu; Fangkai Han; Ning Yang; Fuwei Pi; Ming Zhang; Xiaodan Liu; Jiahua Wang; Huang Dai; et al. (Food Chemistry, 2025)

Research on a method of generating future meteorological parameters for building HVAC design - Chen Cheng; Xiaoyi Fang; Mingcai Li; Jing He; Yaning Gao; Shuo Zhang; Ying Yu (Energy and Buildings, 2025)

Regulating chemical and electronic structure of Ni-based catalysts via introducing heteroatoms for boosting electrochemical oxidation of borohydride - Ying Yang; Zhihong Cui; Caini Yi; Meilin Chen; Hang Yang; Xiaolong Hou; Guimiao Wang; Shuo Wang; Yuping Liu; Guozhong Cao; Danmei Yu; Xiaoyuan Zhou (Chemical Engineering Journal, 2025)

Dopant alliance: K/Cu cooperative bonds lock structural stability in P2-type sodium cathodes - Yu Duan; Jia-xuan He; Zi-han Ma; Shu-wen Chen; Ying-ying Huang; Shuo Bao; Jin-lin Lu (Chemical Engineering Journal, 2025)

Progression of the Residual Lesion in Cavernous Sinus Extra-Axial Cavernous Hemangioma After Surgery - Ran Huo; Qifeng Yu; Hongyuan Xu; Jie Wang; Shaozhi Zhao; Jiancong Weng; Xiudan Bai; Yuming Jiao; Wenqian Zhang; Qiheng He; Zhiyou Wu; Shaowen Liu; et al. (Translational Stroke Research, 2025)

Attributing phase asymmetry in dynamic synoptic eddy feedback on NAO based on storm track model experiments - Shuo Zhao; Hong-Li Ren; Adam A. Scaife; Yu Nie; Jinqing Zuo (Climate Dynamics, 2025)

Spatial–Temporal Dynamics of Drought Characteristics and Its Influencing Factors on Tibetan Plateau - Zhizhu Zhou; Wenjun Yu; Lin Zhao; Yanzhong Li; Shuo Cheng; Jiazhe Duan; Yincong Xing; Wei Shao (International Journal of Climatology, 2025)
Assessing drought on the Tibetan Plateau (TP) is essential for understanding the spatial characteristics of the region's hydrological regimes, as well as the trends of the evolving climate‐ecological system. Based on the precipitation and the potential evapotranspiration data from the ERA5‐Land dataset, this study evaluated the drought characteristics on the TP from 1950 to 2022 using the Standardised Precipitation Evapotranspiration Index (SPEI) and the Run theory. The analysis of SPEI at multiple time scales—SPEI‐1 (monthly), SPEI‐3 (seasonal), and SPEI‐12 (annual)—consistently revealed a pronounced drying trend across the TP over the past 70 years. Notably, the wet‐to‐dry transition points were detected in 2000 and 2001 based on the SPEI‐1 and SPEI‐3 series, respectively, while the SPEI‐12 series indicated a later shift occurring in 2004. In addition, the SPEI values indicated a spatial trend of increasingly severe drought conditions from south to north. Particularly, pronounced drought stress was observed in the Brahmaputra, Ganges, and Indus basins, as well as in the southern regions of the Inner Plateau. Furthermore, the relationships between drought variability and key climatic drivers—including sunspots, El Niño‐Southern Oscillation (ENSO), temperature (TEMP), and annual mean areal precipitation (AP)—were identified through cross‐wavelet transform (XWT) and wavelet coherence analysis (WTC). In general, the analysis showed that the SPEI values on the TP were negatively correlated to ENSO and TEMP but positively correlated to sunspots and AP. This study offers a comprehensive spatiotemporal assessment of drought dynamics across the TP, providing critical insights for regional water resource management and climate change adaptation planning.

Altered effective connectivity within the hippocampal-prefrontal circuit in patients with non-small cell lung cancer after platinum chemotherapy - Lanyue Hu; Zhengqian Wang; Shuo Li; Yujie Zhang; Jia You; Qian Li; Yu-Chen Chen; Xindao Yin (Brain Imaging and Behavior, 2025)

Causal Matrix Long Short-Term Memory Network for Interpretable Significant Wave Height Forecasting - Mingshen Xie; Wenjin Sun; Ying Han; Shuo Ren; Chunhui Li; Jinlin Ji; Yang Yu; Shuyi Zhou; Changming Dong (Journal of Marine Science and Engineering, 2025)
This study proposes a novel causality-structured matrix long short-term memory (C-mLSTM) model for significant wave height (SWH) forecasting. The framework incorporates a two-stage causal feature selection methodology using cointegration testing and Granger causality testing to identify long-term stable causal relationships among variables. These relationships are embedded within the C-mLSTM architecture, enabling the model to effectively capture both temporal dependencies and causal information within the data. Furthermore, the model integrates Bayesian optimization (BO) and twin delayed deep deterministic policy gradient (TD3) algorithms for synergistic optimization. This combined TD3-BO approach achieves an 11.11% improvement in the mean absolute percentage error (MAPE) on average compared to the base model without optimization. For 1–24 h SWH forecasts, the proposed TD3-BO-C-mLSTM outperforms the benchmark models TD3-BO-LSTM and TD3-BO-mLSTM in prediction accuracy. Finally, a Shapley additive explanations (SHAP) analysis was conducted on the input features of the BO-C-mLSTM model, which reveals interpretability patterns consistent with the two-stage causal feature selection methodology. This research demonstrates that integrating causal modeling with optimization strategies significantly enhances time-series forecasting performance.

Vertical heterogeneity of dissolved ferrous and iron speciation in tropical seagrass beds - Shuo Yu; Yuzhou Huang; Fangchao Zhu; Tong Liu; Zhenming Zheng; Yongming Huang; Anhuan Lu (Marine Pollution Bulletin, 2025)

Effects of tank color on the survival, growth performance and carapace color of juvenile mud crab (Scylla paramamosain) - Xinyue Liu; Shujian Chen; Shuo Wang; Kaijia Yu; Yangfang Ye; Ronghua Li; Changkao Mu; Chunlin Wang; Ce Shi (Aquaculture, 2025)

Late Holocene transition from natural to anthropogenic forcing of fire regime in Arid Central Asia - Guoqiang Ding; Jianhui Chen; Yanbin Lei; Wensheng Zhang; Shuo Wang; Panpan Ji; Yu Cao; Shengqian Chen; Fahu Chen; Heikki Seppä (Science of The Total Environment, 2025)

Differential ecotoxicity of nanoencapsulated metamifop and its active ingredient in zebrafish (Danio rerio): Insights from transcriptome and metabolome analysis - Yujun Xu; Simin Yu; Jiaming Yin; Zeng Wang; Jie Shen; Shaowen Liu; Xile Deng; Shuo Yan (Pesticide Biochemistry and Physiology, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Transmembrane uptake of polystyrene nanoplastics mediated by aquaporin in tartary buckwheat: Physiological consequence and genomic mechanism - Yu-Kang Hou; Shuo Gao; Qiang Lai; Wen-Rui Lu; You-Bao Cai; Ya-Wen Yuan; Si-Yuan Yao; Hong-Yan Tao; Li-Zhe An; You-Cai Xiong; Yuan Song (Journal of Hazardous Materials, 2025)

Investigation on deactivation periods of ZSM-5/SAPO-34 catalyst in MTA reaction: Carbon deposition behavior - Jingbo Li; Bangming Yang; Ning Li; Jianqiao Zhao; Shuo Li; Ruizhi Chu; Xianliang Meng; Weisong Li; Shi Yu (Fuel, 2025)

An insight into the full aspects of bound polyphenols in dietary fiber: Interaction, composition, function and foundation as well as alteration in food processing - Chunyan Hou; Youkang Chen; Wanting Zhang; Jingjing Yu; Muhua Ji; Shuo Cai; Wenhao Guo; Xiaolong Ji; Lijun Sun; Xuebo Liu; Yutang Wang (Food Chemistry, 2025)

Investigating roasting conditions to explore AGEs formation in chicken breast: A dynamic model approach - Yingshuang Lu; Yu Jiang; Mengyu Sun; Lu Dong; Xiaolong Xing; Yan Zhang; Shuo Wang (Food Control, 2025)

An integrated CFD and CNN-GRU approach for accurate prediction of PM2.5 in greenhouse environments of Northeast China - Shuo Zhang; Li Guo; Haiye Yu; Bo Zhang; Meichen Chen; Lei Zhang; Dawei Li; Yuanyuan Sui (Building and Environment, 2025)

A stepwise-clustered concurrent extreme analysis for concurrent drought-heatwave events: a case study of North China - Shuo Han; Guohe Huang; Xiong Zhou; Shuguang Wang; Yongping Li; Bizheng Yu; Wenshu Kuang (Climatic Change, 2025)

Origin of reedmergnerite and searlesite in sodium-rich chert and their paleoclimatic implications from a late paleozoic marginal alkaline saline lake in China - Kuanhong Yu; Zi Wang; Yingchang Cao; Shuo Du (Carbonates and Evaporites, 2025)

Design of Control System for Underwater Inspection Robot in Hydropower Dam Structures - Bing Zhao; Shuo Li; Xiangbin Wang; Mingyu Yang; Xin Yu; Zhaoxu Meng; Gang Wan (Journal of Marine Science and Engineering, 2025)
As critical infrastructure, hydropower dams require efficient and accurate detection of underwater structural surface defects to ensure their safety. This paper presents the design and implementation of a robotic control system specifically developed for underwater dam inspection in hydropower stations, aiming to enhance the robot’s operational capability under harsh hydraulic conditions. The study includes the hardware design of the control system and the development of a surface human–machine interface unit. At the software level, a modular architecture is adopted to ensure real-time performance and reliability. The solution employs a hierarchical architecture comprising hardware sensing, real-time interaction protocols, and an adaptive controller, and the integrated algorithm combining a fixed-time disturbance observer with adaptive super-twisting controller compensates for complex hydrodynamic forces. To validate the system’s effectiveness, field tests were conducted at the Baihetan Hydropower Station. Experimental results demonstrate that the proposed control system enables stable and precise dam inspection, with standard deviations of multi-degree-of-freedom automatic control below 0.5 and hovering control below 0.1. These findings confirm the system’s feasibility and superiority in performing high-precision, high-stability inspection tasks in complex underwater environments of real hydropower dams. The developed system provides reliable technical support for intelligent underwater dam inspection and holds significant practical value for improving the safety and maintenance of major hydraulic infrastructure.

Statistical investigation of marine bacterial extracellular polysaccharides: deciphering the interplay among environmental adaptation, species distribution, and biomedical potential - Yuanyuan Jiang; Shuo Liang; Qingfeng Niu; Chanjuan Liu; Guangli Yu; Guoyun Li (Marine Life Science & Technology, 2025)

Integrated coordination of production scheduling, preventive maintenance, and energy conservation in flexible manufacturing environments - Yu Wang; Tangbin Xia; Yaping Li; Shuo Gao; Dong Wang; Lifeng Xi (Journal of Cleaner Production, 2025)

Effects of dietary polyphenols addition and oxygen concentration on digestion and absorption of fat in roast beef patties - Yu Chang; Bowei Zhang; Yuze Jia; Xiaolu Shi; Yingshuang Lu; Fan Wei; Yunhui Zhang; Huan Lv; Lu Dong; Yan Zhang; Xiangwei Tang; Shuo Wang (Food Chemistry, 2025)

Accelerating enrichment of ARGs and MGEs with increasing ammonium removal during partial nitrification treating high-strength ammonia wastewater - Heng Yu; Weiyi Jia; Yuqiu Luo; Rong Zhang; Junkai Zhao; Cong Lu; Yue Dong; Shuo han; Bing Li; Chengtun Qu (Environmental Research, 2025)

A dual-biomimetic evaporator with Marangoni-induced ultra-salt-resistance for long-durable solar desalination - Zhaolong Wang; Jiyuan Yu; Meiyang Hu; Ciwei Wu; Shuo Yang; Qihui Xie; Yong Shuai (Chemical Engineering Journal, 2025)

Carbon stocks in two temperate Zostera meadows in the Yellow Sea, North China - Ruiting Gu; Sichao Pu; Jianwu Tang; Tingting Liu; Linjing Ren; Shaochun Xu; Shuo Yu; Xiuzhen Li; Ning Zhao (CATENA, 2025)

EIF4A3-Mediated downregulation of circPTEN promotes hepatocellular carcinoma progression through the miR-1289/RBM38 Axis - Shuo Yu; Min Wang; Feng Peng; Hang Zhang; Renyi Qin; Chengjian Shi (Journal of Molecular Histology, 2025)

Effect of swirling strength on droplets impact on concave wall: Experimental and numerical investigation - Shuo OUYANG; Zhenqin Xiong; Hua Bei; Kaicheng Yu; Lichen Xue; Jiyun Zhao (Annals of Nuclear Energy, 2025)

Dual-stage matrix elimination-ICP-MS methodology for REEs profiling in barite-associated ores - Xue-lin Dong; Jun-han Liu; Zheng-xun Jia; Shao-zhan Tang; Shuo-yun Tong; Yu-xiang Xiong; Lei Ouyang (Analytica Chimica Acta, 2025)

Oxidative stress and antioxidant biomarker responses in fish exposed to heavy metals: a review - Yu Zeng; Zhixin Song; Gangfu Song; Shuo Li; Haosen Sun; Chao Zhang; Guoting Li (Environmental Monitoring and Assessment, 2025)

Quantifying the contribution of sediment recycling in mantle: A case study of Early Cretaceous gabbroic intrusions in the northeastern North China Craton - Xiang-Yu Yan; De-Bin Yang; Wen-Liang Xu; Feng Wang; Shuo Wang; Ke Wu (Lithos, 2025)

Organic fertilizer mitigated the oxidative stress of tomato induced by nanoplastics through affecting rhizosphere soil microorganisms and bacteriophage functions - Liang-Bin Zhao; Zi-Xuan Tang; Hui-Fang Zhai; Hong-Yu Lai; Hai-Yang Li; Shuo Liu; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Better ecosystem resistibility but with severer risk deriving from potential pathogens and antibiotic resistances in marine sediments adjacent to Yellow River estuary under oil contamination - Yanlu Qiao; Mingan Shen; Lingbing Kong; Yudi Sun; Shuo Wang; Yu Gao; Jianliang Xue; Qing Jiang; Dongle Cheng; Yuyang Liu (Environmental Research, 2025)

Modular DNA logic computing-driven multiplex MicroRNA detection: Precision breast cancer subtype diagnostics with multi-bit fluorescent encoding - Jingyuan Yu; Songchen Zhao; Xintong Hu; Liguo Chen; Hao Sun; Shuo Ling; Daoyu Zhang; Yanfang Jiang; Yan Du (Chemical Engineering Journal, 2025)

One-step forming strategy of highly stable Li4SiO4 for low-concentration CO2 capture - Yu Zhang; Shuo Chen; Shikun Wen; Jiaojiao Li; Rui Yang; Liang Huang; Junya Wang; Ping Ning; Qiang Wang (Chemical Engineering Journal, 2025)

Competitive roles of slow/delta oscillation-nesting-mediated sleep disruption under acute methamphetamine exposure in monkeys - Xin Lv; Jie Liu; Shuo Ma; Yuhan Wang; Yixin Pan; Xian Qiu; Yu Cao; Bomin Sun; Shikun Zhan (Journal of Zhejiang University-SCIENCE B, 2025)

Energy-Optimized Path Planning for Fully Actuated AUVs in Complex 3D Environments - Shuo Liu; Zhengfei Wang; Tao Wang; Shanmin Zhou; Yu Zhang; Pengji Jin; Guanjun Yang (Journal of Marine Science and Engineering, 2025)
This paper presents an energy-optimized path planning approach for fully actuated autonomous underwater vehicles (AUVs) in three-dimensional ocean environments to enhance their operational range and endurance. A fully actuated AUV is characterized by its high degrees of freedom and precise controllability. Using real terrain data, we construct environmental models incorporating a Lamb vortex and random obstacles. We develop a mathematical model of the AUV’s total energy consumption, accounting for constraints imposed by its fully actuated design and extensive maneuverability. To minimize energy usage, we propose an energy-optimized path planning algorithm that combines energy-optimized particle swarm optimization (EOPSO) and sequential quadratic programming (SQP). The proposed method identifies the optimal path for energy consumption and the corresponding optimal surge speed. The efficacy of the algorithm in optimizing the total energy consumption of the AUV is demonstrated through the simulation of various scenarios. In comparison to other algorithms, paths planned by this algorithm are shown to have superior robustness and optimized energy consumption.

Response of diatoms to environmental changes in the Porphyra cultivation system in Haizhou Bay using GBT model and GAM - Shuo Chen; Haibin Han; Jinchen Yu; Tao Sun; Jin Zhou (Marine Pollution Bulletin, 2025)

Effect of temperature on phosphorus release from waste activated sludge containing ferric-phosphate - Yu Dai; Xiaodi Li; Shuo Wang; Lu Wang; Yucheng Zou; Bo Wang (Journal of Water Process Engineering, 2025)

Montmorillonite-chitosan composite support enhances the electron transfer and stability of loaded copper nanoparticles during the catalytic reduction of Cr(VI) - Xiang-Zheng Cui; Yu Peng; Shuo Chen; Hong Jiang (Journal of Environmental Chemical Engineering, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Developing a drought-heatwave cluster projection (DHCP) approach for water shortage areas: A case study in Northwest China - Yingxia Tang; Guohe Huang; Wenshu Kuang; Shuo Han; Shuguang Wang; Yongping Li; Bizheng Yu (Theoretical and Applied Climatology, 2025)

Experimental and Molecular Simulation Research on the Oxidation Behavior of Soaked Coal Spontaneous Combustion - Xin-Xiao Lu; Guo-Yu Shi; Shuo Wang; Guan Wang; Zi-Yao Chen (Natural Resources Research, 2025)

Dual mobilization of buried microplastics and organic carbon driven by seagrass degradation: a case study from Swan Lake, China - Yuzhou Huang; Shuo Yu; Zhenming Zheng; Xi Xiao; Zuhao Zhu; Liangchao Deng; Huihua Wei; Jiani Liang; Shuilan Chen; Marianne Holmer (Frontiers in Marine Science, 2025)
Seagrass beds are significant sinks for microplastics. However, the degradation of seagrass beds poses significant challenges, and evidence regarding its impacts on microplastic sinks remains scarce. In this study, sediment cores were collected to investigate microplastic stock and composition, microplastic carbon, and organic carbon stock in Zostera japonica seagrass bed and adjacent degraded area in a lagoon Swan Lake, China. The microplastic stock in seagrass bed (84.5 ± 18.5 million particles ha -1 ) was found significantly higher than degraded area (51.8 ± 0.6 million particles ha -1 ), resulting in release of 38.7% of buried microplastics reactivated in water column. Similarly, 30.0% of the microplastic carbon stock and 66.1% of the total organic carbon stock were eroded due to seagrass degradation. The carbon stocks derived from microplastics were estimated at 0.19 ± 0.10 kg C ha -1 in the seagrass bed and 0.13 ± 0.11 kg C ha -1 in the degraded area, contributing minimally to the total organic carbon stock (0.0023% and 0.0026%, respectively). Notably, seagrass degradation within a single year may trigger rapid erosion of organic carbon and microplastics buried for over 20 years in Swan Lake. A linear relationship was observed between sediment microplastic carbon and total organic carbon contents (Organic carbon = 1990 + 35100 × Microplastic carbon, R² = 0.26, p < 0.001). Microplastics in the sediments were predominantly fiber (48.1%), black (40.7%), 250–500 µm (47.0%) microplastics in degraded area, while plate (26.7%), blue and transparent, each contributing 26.7% and 125–250 µm (38.2%) in seagrass bed. Seagrass bed degradation may not only reduce the stock of microplastics in the sediments but also alter their composition. This study initially quantified the contribution of microplastics to organic carbon stocks in seagrass bed sediments and underscored the urgent need for seagrass conservation to mitigate climate change and prevent the remobilization of historically buried microplastics.

AI-Driven urban planning optimization: A graph neural network and genetic algorithm framework for tackling peak-hour challenges - Jianyi Li; Yin Zhang; Shuo Yu; Haochen Qin; Zhen Xu (Sustainable Cities and Society, 2025)

(+)/(−)-Corydecumbenpines A and B, two pairs of dimeric phthalide-benzophenanthridine alkaloids with cytotoxicity from Corydalis decumbens - Peng Gao; Yu-Qi Wang; Shuo Yuan; Yan-Hang Wang; Ming-Bo Zhao; Ke-Wu Zeng; Yong Jiang; Qing-Ying Zhang; Peng-Fei Tu (Phytochemistry, 2025)

One-step high-efficiency recovery of high-purity MoO3 from spent hydrodesulfurization catalyst by water-vapor enhanced sublimation process - Shuo Liu; Haoran Yu; Ali Yaras; Linchao Hu; Wenyi Zhang; Mingguo Peng; Battsengel Enkhchimeg; Linqiang Mao (Journal of Hazardous Materials, 2025)

Vine tea (Ampelopsis grossedentata) ameliorates chronic alcohol-induced hepatic steatosis, oxidative stress, and inflammation via YTHDF2/PGC-1α/SIRT3 axis - Qihan Luo; Jiang Qiu; Minxia Chen; Na Yang; Xinyue Li; Shuo Huang; Qing Ma; Zongyuan Li; Dayong Lou; Yu Du; Li Chen; Qing Shen; et al. (Food Research International, 2025)

Comparative analysis of quality, structural, and flavor alterations in chestnuts (Castanea mollissima Blume) subjected to different thermal processing techniques - Zhenting Yu; Jin Deng; Nan Ma; Yi Sun; Jin Wang; Jing-Min Liu; Yan Zhang; Yingshuang Lu; Shuo Wang (Food Chemistry, 2025)

Does the residential photovoltaic station programme aid poverty alleviation? Evidence from rural China - Jiazheng Wu; Shuo Mi; Jiahui Meng; Nannan Yu (Energy Policy, 2025)

High-dielectric TiO2-mediated g-C3N4 enhanced self-polarized PVDF hybridized film for highly sensitive wearable triboelectric pressure sensors - Yen-Shuo Chiu; Mia Rinawati; Ling-Yu Chang; Sofiannisa Aulia; Ping-Chen Shi; Shu-Chih Haw; Wei-Hsiang Huang; Ni Luh Wulan Septiani; Brian Yuliarto; Min-Hsin Yeh (Chemical Engineering Journal, 2025)

Creep Behavior Research of Deep-Sea Pressure Hull: A Review - Yuan Zeng; Changli Yu; Shuo Yang (Journal of Marine Science and Engineering, 2025)
Pressure hulls are the primary pressure-bearing structures in submersibles and deep-sea space stations, which are essential for marine scientific research. Due to repeated dive cycles and extended operational periods, these hulls undergo creep deformation over time, posing risks to their structural integrity. This paper provides a comprehensive review of research on the creep behavior of pressure hulls, focusing on three key aspects: creep testing, creep constitutive models, and numerical simulation techniques. Initially, various creep testing methodologies are presented, with the experimental data serving as a foundational basis for subsequent analyses. Experimental data from creep tests form the foundation for constructing and validating constitutive models, which are critical for predicting long-term deformation. The review also explores advanced numerical simulation techniques, such as user subroutines and multiscale modeling, to analyze creep in complex pressure hull structures. Finally, based on the insights from the reviewed studies, the paper proposed potential directions for future research to address current challenges and enhance the design and maintenance of pressure hulls.

Study on the aeroelastic response of wind turbine blades with pitch system failure and strategies for typhoon resistance - Yu Yao; Shuo Huang; Kai Wang; Mengshang Zhao; Huanzhe Liu (Ocean Engineering, 2025)

Origin of reedmergnerite in sodium carbonate successions and environmental implications in a Late Paleozoic alkaline saline lake, NW Junggar Basin, China - Kuanhong Yu; Xinyu Duan; Yingchang Cao; Shuo Du (Marine and Petroleum Geology, 2025)

Recovery of valuable metals from spent hydrodesulfurization (HDS) catalysts: A comprehensive research review and specific industrial cases - Haoran Yu; Shuo Liu; Ali Yaraş; Battsengel Enkhchimeg; Linchao Hu; Wenyi Zhang; Mingguo Peng; Hasan Arslanoğlu; Linqiang Mao (Journal of Environmental Management, 2025)

Pilot study on a physical process for treating petrochemical wastewater - Shaoxuan Li; Binghe Li; Yu Li; Haonan Liu; Shuo Huang; Qiang Yang; Yiqian Liu (Journal of Environmental Management, 2025)

A novel antioxidant peptide from soybean meal alleviates H2O2-induced oxidative damage via the Keap1-Nrf2-HO-1 pathway - Yiding Yu; Sitong Ma; Yuxi Han; Shuo Zhang; Meng Yang; Zhiyang Du; Zhipeng Yu; Chunmei Liu (Food Research International, 2025)

Dynamic characterization of the changes in intestinal fungi and fecal metabolites during the reproductive cycle of sows - Jin-Wen Su; Xin-Wen Hou; Shuo Liu; Yu Chen; Ji-Xin Zhao; Xiao-Xuan Zhang; Hong-Bo Ni; He Ma; Rui Liu (Veterinary Research Communications, 2025)

Functional divergence of CAD-like family genes in Saccharum complex under biotic and abiotic stress - Zhu-Qing Wang; Sheng-Ren Sun; Hao-Yu Wang; Zheng-Wang Bi; Hai-Long Chang; Shuo-Hang Zhang; Jun-Lv Chen; Yuan-Xia Qin; Jian-Tao Wu; Wei Zhang; Huan-Ying Xu; San-Ji Gao; et al. (Plant Cell Reports, 2025)

Assimilation of MetOp-C AMSU-A Data Using the ARMS as an Observation Operator in the YH4DVAR System - Tengling Luo; Shuo Ma; Weimin Zhang; Yanlai Zhao; Yi Yu; Jinhui Yang; Shaoying Li (Journal of Meteorological Research, 2025)

Targeted editing of CCL5 with CRISPR-Cas9 nanoparticles enhances breast cancer immunotherapy - Wei Yan; Shuo Wang; Lihui Zhu; Xinlin Yu; Jianglong Li (Apoptosis, 2025)

Trees show higher resilience than herbs under phosphorus deficit induced by 12‐year simulated acid rain - Guangcan Yu; Mianhai Zheng; Ying‐Ping Wang; Mengxiao Yu; Jun Jiang; Enqing Hou; Nannan Cao; Shu Ye; Songjia Chen; Jingtao Wu; Fengcai Liu; Linhua Wang; et al. (Ecology, 2025)
Acid rain, with 60% deposition in Asia, may exacerbate plant phosphorus (P) limitation; however, its long‐term effects on different plant life‐forms remain largely undetermined. Understanding these effects is essential for predicting ecosystem resilience and promoting forest health under environmental change. Herein, we investigated the P status in two tree and two herb species and their rhizosphere soils after 12 years of acid treatment at three pH levels (pH: 4.0, 3.5, and 3.0) in a tropical forest in Southern China. We found that leaf, litter, and root P; leaf N and P resorption efficiency; and their ratios remained stable in trees; however, herb leaf and litter P levels declined. Acid addition reduced inorganic P in tree rhizosphere soil and inorganic and organic P in herb rhizosphere soil. Rhizosphere soil P fractions were more regulated by soil physicochemical properties and less regulated by microbial community in trees than in herbs. Under long‐term simulated acid rain, stable tree P status benefited from soil inorganic P depletion, and herbs partially met their P requirements via biological mineralization of soil organic P. These distinct P‐associated responses and acquisition strategies provide insights into safeguarding forest health among plants of different functional types under long‐term acid rain events.

Inflammation May Mediate the Effects of Fluoride on Liver and Kidney Function of Adults: Cross-Sectional Studies in China - Minghao Geng; Yi Cheng; Leizhen Duan; Guangshen Dong; Shuo Yang; Xuecheng Jiao; Weihua Jia; Hui Huang; Ming Dou; Xiaoli Fu; Fangfang Yu; Yuhui Du; et al. (Biological Trace Element Research, 2025)

Critical review: Considerations in applying avian egg injection studies to characterize effects of hydrophobic organic compounds on wild birds - Shuo Yu; Sydney Kruse; Phyllis Fuchsman (Chemosphere, 2025)

An omnidirectional dynamic levelling system with less tuning parameters for mountainous tea plantations - Haijun Zhu; Hongling Jin; Yifan Hou; Shujie Wang; Yu Chen; Shuo Zhang; Jianhu Shen (Biosystems Engineering, 2025)

Flusulfinam, a novel amide herbicide to control weed in rice fields, targets 4-hydroxyphenylpyruvate dioxygenase - Hengzhi Wang; He Sun; Shuo Yu; Lei Lian; Tao Jin; Xuegang Peng; Jinxin Wang; Weitang Liu (Pesticide Biochemistry and Physiology, 2025)

Research on improved null space based unmanned surface vehicle formation maneuver control method for merchant ship escort - Yulei Liao; Yu Ge; Zhibin Song; Ruiwen Qian; Wei Yu; Yongtong Xu; Ye Li; Shuo Pang (Ocean Engineering, 2025)

Spiral-structured electrospun conductive conduits filled with aligned nanofibers for peripheral nerve regeneration - Jiahui Song; Siyuan Wu; Chenlong Liao; Zhengchao Yuan; Xiao Yu; Panpan Shang; Yihong Shen; Jie Cui; Jinglei Wu; Binbin Sun; Mohamed EL-Newehy; Meera Moydeen Abdulhameed; et al. (Chemical Engineering Journal, 2025)

Experimental and kinetic study of laminar combustion characteristics of ammonia/air mixtures under oxygen enrichment at high temperature and pressure - Jiangping Tian; Chunlei Hou; Jianing Liu; Song Shi; Hongen Yang; Qingxing Zhou; Shuo Yin; Yuantao Yu; Xiaolei Zhang; Zechuan Cui (Chemical Engineering Journal, 2025)

NIN-like proteins NLP8 negatively regulate drought resistance in Arabidopsis by regulating the expression level of PUB23 - QiJun Ma; Yu Sun; Shuo Xu; KaiJing Zuo (Plant Cell Reports, 2025)

Tahyna virus: an emerging threat to public health - Wenbing Zhu; Lijun Shao; Shuo Feng; Ke Lu; Xiaoli Yu; Guoyu Niu (Archives of Virology, 2025)

Nutrient Availability Shapes the Resistance of Soil Bacterial Community and Functions to Disturbances in Desert Ecosystem - Hang Gao; Yuan Song; Mingyu Li; Min Gao; Ziheng Peng; Haibo Pan; Jiejun Qi; Shi Chen; Yu Liu; Yang Wang; Chujie Jin; Gehong Wei; et al. (Environmental Microbiology, 2025)
Climate change has exposed desert ecosystems to frequent extreme disturbances, including wet‐dry cycles and freeze–thaw events, which accelerate desertification on a global scale. The limited nutrient availability characteristic of these ecosystems may constrain microbial survival and growth, making them more vulnerable to environmental perturbations and stressors. However, how nutrient availability modulates the stability of soil ecological communities and functions in desert ecosystems remains poorly understood. In this study, we examined how nutrient addition, applied either before or after disturbances, affects the resistance of bacterial communities and multifunctionality to drought and freeze events in desert ecosystems. Our findings revealed that freeze–thaw events, rather than drought, significantly reduced bacterial diversity, with all disturbances altering the community structure. Pre‐disturbance nutrient addition notably improved the resistance of soil bacterial diversity and community composition to disturbances, which played a critical role in maintaining multifunctionality in desert ecosystems. This enhanced bacterial resistance was strongly associated with increased bacterial network complexity and the enrichment of disturbance‐tolerant taxa. Our results highlight the pivotal role of nutrient availability in stabilising soil bacterial communities and multifunctionality under extreme climatic conditions in desert ecosystems. These findings offer valuable insights and practical strategies for the ecological protection and management of desertification.

Experimental study on a smoke airflow CO filtration and elimination device based on particulate Co3O4 catalyst - Sheng He; Shuo Gao; Jia Li; Yitao Yu; Jianguo Wu; Jiaxin Shi; Xiao Wang; Xiaoyu Chen; Fubao Zhou (Process Safety and Environmental Protection, 2025)

Utilization of molybdenum tailings in subgrade materials: Orthogonal experiments, long-term leaching behavior of heavy metals, and environmental impact assessment - Wentao Ji; Shuo Pan; Jialin Yu; Lili Liu; Quanyin Tan; Jinhui Li (Process Safety and Environmental Protection, 2025)

Semi-supervised learning-based identification of the attachment between sludge and microparticles in wastewater treatment - Tianlong Jia; Jing Yu; Ao Sun; Yipeng Wu; Shuo Zhang; Zhaoxu Peng (Journal of Environmental Management, 2025)

Titanium-based hollow fiber membrane: Fabrication, optimization, and electrochemical filtration treatment performance - Xiaoqing Yan; Zonglin Pan; Xinyuan Zhou; Shuo Liu; Hang Yu; Ruisong Xu; Yawei Shi; Xinfei Fan; Tianjun Sun; Yongxin Song; Chengwen Song (Journal of Environmental Chemical Engineering, 2025)

Interactive mechanisms of CF3CHFCF3 with H2-CH4-air mixture explosion: A synergistic study using chemical kinetic simulation and density functional theory - Hongfu Mi; Nan Luo; Peng Shao; Hang Yi; Shuo Wang; Wenhe Wang; Yihui Niu; Ao Yang; Xinsheng Jiang; Yu Feng; Li-Huan Zhu; Chi-Min Shu (Fuel, 2025)

Lipid peroxidation inhibition by icaritin and its glycosides as a strategy to combat iron overload-induced osteoporosis in zebrafish - Chang-Yu Yan; Xiao-Yuan Gu; Shuo-Yan Tan; Ao-Yu Mei; Jiang-Hao Mao; Yi Dai; Jie Niu; Wei-Xi Li; Hiroshi Kurihara; Yi-Fang Li; Rong-Rong He (Food Research International, 2025)

Ultra-stable MAPbBr3@ZIF-8-based fluorescent aptasensor for highly sensitive and specific detection of azlocillin in food - Anqi Sun; Shuo Qi; Yu Li; Yiyao Wu; Yin Zhang; Zhouping Wang (Food Bioscience, 2025)

Differentiation revelation of wine quality induced by maceration technology under the mediation of environmental factors and microbial community - Manman Gao; Shuo Yu; Jianing Bai; Ru Chen; Yunjie Li; Liping Du; Lijuan Ma; Huiling Zhang; Xiaoju Tian (Food Bioscience, 2025)

SIGIRR plays a dual role in zebrafish infected with Edwardsiella piscicida: Boosting digestive system wellness and mitigating inflammation - Ting Yu; Shuo Yang; Lifeng Zhang; Dan Deng; Xiao Zhang; Kai Luo; Weihua Gao; Bei Wang; Shuhuan Zhang; Qiaoqing Xu (Fish & Shellfish Immunology, 2025)

Toxic effects of exposure to polymethyl methacrylate and polyvinyl chloride microplastics in Pacific oysters (Crassostrea gigas) - Chunmei Gao; Zhuolong Wu; Baogui Liang; Jikun Lu; Guanghui Fu; Miaomiao Sun; Wenwen Yu; Shuo Zhang; Shike Gao (Environmental Pollution, 2025)

Structural and physicochemical properties of corn starch modified by phosphorylase b, hexokinase and alkaline phosphatase - Shuo Sun; Dengyue Sun; Li Guo; Bo Cui; Feixue Zou; Jinpeng Wang; Chunrui Sun; Yu Zhu; Xueling Li (Carbohydrate Polymers, 2025)

Timing of carbon uptake during seafloor alteration: Insight from in situ U-Pb dating at DSDP sites 417A and 417D - Zhichao Liu; Shuo Chen; Yanhong Chen; Lifeng Zhong; Renbiao Tao; Yaoling Niu; Zhaojie Yu; Laurence A. Coogan (Chemical Geology, 2025)

Enhancement of nitrogen transformation in media-based aquaponics systems using biochar and zerovalent iron - Muhammad Tanveer; Shuo Wang; Xiaolong Ma; Piehan Yu; Peipei Xu; Linlan Zhuang; Zhen Hu (Bioresource Technology, 2025)

Light-emitting diodes affect plantlet growth of Spathiphyllum cannifolium by regulating photosynthesis and sucrose metabolism during ex vitro rooting - Shuo Yu; Kui-Hua Li; Hang-Lin Song; Yue Dai; Yin-Ji Jiang; Mei-Yu Jin; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Correction to: Dexmedetomidine Promoted HSPB8 Expression via Inhibiting the lncRNA SNHG14/UPF1 Axis to Inhibit Apoptosis of Nerve Cells in AD - QingYun Tan; LiLi Liu; Shuo Wang; QingDong Wang; Yu Sun (Neurotoxicity Research, 2025)

Regulating self-assembly of concomitant isotropic Ag78 and anisotropic Ag110 nanoclusters - Xin-Lan Peng; Shuo Huang; Yu-Jing Zhao; Xi-Ming Luo; Hai-Yang Li; Jia-Hua Hu; Jia-Hong Huang; Shuang-Quan Zang (Science Bulletin, 2025)

PagNAC2a promotes phloem fiber development by regulating PagATL2 in poplar - Yu Guo; Yang-Xin Shi; Shuo Song; Yan-Qiu Zhao; Meng-Zhu Lu (Plant Science, 2025)

Transcription factor PdMYB118 in poplar regulates lignin deposition and xylem differentiation in addition to anthocyanin synthesis through suppressing the expression of PagKNAT2/6b gene - Shuo Song; Wei Guo; Yu Guo; Erkun Chao; Sujie Sun; Lizi Zhao; Yanqiu Zhao; Hongxia Zhang (Plant Science, 2025)

Nitrogen-cycling processes under long-term compound heavy metal(loids) pressure around a gold mine: Stimulation of nitrite reduction - Xuesong Hu; Xiaoxia Liu; Shuo Zhang; Caihong Yu (Journal of Environmental Sciences, 2025)

Divergent responses of an armored and an unarmored dinoflagellate to ocean acidification - Wei-Ping Zhang; Shuo-Yu Zhang; Yang Zhou; Wen-Jing Sun; Shu-Feng Zhang; Jae-Seong Lee; Minghua Wang; Da-Zhi Wang (Harmful Algae, 2025)

Impact of lipid oxidation products on the digestibility and structural integrity of Myofibrillar proteins during thermal processing - Yingshuang Lu; Yuan Zhuang; Yu Jiang; Junping Wang; Lu Dong; Yan Zhang; Shuo Wang (Food Chemistry, 2025)

A baroduric immobilized composite material promoting remediation of oil-polluted sediment at typical deep-sea condition: The performances and potential mechanisms - Yanlu Qiao; Lingbing Kong; Mingan Shen; Yudi Sun; Shuo Wang; Yu Gao; Jianliang Xue; Qing Jiang; Dongle Cheng; Yuyang Liu (Environmental Research, 2025)

Preparation of Al-5Li@FSG powders through fluorination-energetic modification to improve the comprehensive performance of alloy powders - Haiyang Wang; Shuo Wang; Xuanyan Liu; Youqi Zhu; Tinglu Song; Haiyue Yu; Hongdi Fu; Kangcheng Xu; Huaqiang Zhu; Yonghao Zhao; Siyuan Tang; Meishuai Zou (Chemical Engineering Journal, 2025)

Electrochemical hydrogenation and hydrogenolysis of furfural on copper electrode enhanced by surface environment modulation with metal–organic framework - Yu-Shuo Lee; Chi-Wei Huang; Chun-Ting Yueh; Chung-Wei Kung; Wen-Yueh Yu (Chemical Engineering Journal, 2025)

A scalable wood-based interfacial evaporator assisted with localized joule heating for round-the-clock operations - Yang Ming; Shuo Shi; Wei Cai; Jing Liu; Daming Chen; Xin Hu; Rujun Yu; Xia Zhou; Benjamin Tawiah; Bin Fei (Chemical Engineering Journal, 2025)

Phototunable phosphorescence energy transfer based on photodimerization of coumarin-12-crown-4 accelerated by γ-cyclodextrin - Hui-Juan Wang; Yan-Tao Li; Ming-Che Shao; Chang-Shuo Yu; Jin-Yao Yang; Lingyang Liu; Suna Wang; Jianmin Dou (Chemical Engineering Journal, 2025)

Plasma-enhanced methanol steam reforming over Pt/In2O3-ZnO/Al2O3 catalyst with ultralow Pt-loading for in-situ H2 production - Hao-Yu Lian; Shuo Geng; Yi-Zhi Wang; Yuan Lv; Hao-Chen Yang; He Zhang; Xiao-Qing Deng (Chemical Engineering Journal, 2025)

Pioneering food analysis: Transformative antioxidant testing with colorimetric assays using Co–Mn bimetallic oxide nanozyme - Shuyun Chen; Zhichao Yu; Yunsen Wang; Shuo Tian; Qiaohua Wei; Dianping Tang (Analytica Chimica Acta, 2025)

A Global Relationship Between Genome Size and Encoded Carbon Metabolic Strategies of Soil Bacteria - Xingjie Wu; Jingjing Peng; Ashish Anil Malik; Ziheng Peng; Yu Luo; Fenliang Fan; Yahai Lu; Gehong Wei; Manuel Delgado‐Baquerizo; Werner Liesack; Shuo Jiao (Ecology Letters, 2025)
Microbial traits are critical for carbon sequestration and degradation in terrestrial ecosystems. Yet, our understanding of the relationship between carbon metabolic strategies and genomic traits like genome size remains limited. To address this knowledge gap, we conducted a global‐scale meta‐analysis of 2650 genomes, integrated whole‐genome sequencing data, and performed a continental‐scale metagenomic field study. We found that genome size was tightly associated with an increase in the ratio between genes encoding for polysaccharide decomposition and biomass synthesis that we defined as the carbon acquisition‐to‐biomass yield ratio (A/Y). We also show that horizontal gene transfer played a major evolutionary role in the expanded bacterial capacities in carbon acquisition. Our continental‐scale field study further revealed a significantly negative relationship between the A/Y ratio and soil organic carbon stocks. Our work demonstrates a global relationship between genome size and the encoded carbon metabolic strategies of soil bacteria across terrestrial microbiomes.

Cretaceous evolution of the Lhasa-Qiangtang Orogen: insights from mafic igneous rocks - Di Shen; Ming Wang; Chang-Sheng Yu; Quewan Danzeng; Sheng-Shuo Zhang (International Geology Review, 2024)

Parameter Identification of an Unmanned Sailboat Combining Experiments and Numerical Analysis - Yifan Chen; Shuo Liu; Tian Xie; Zhaozhao Zhang; Yu Zhang; Wanglin Lin; Kaiyou Jiang; Tao Wang (Journal of Marine Science and Engineering, 2024)
It is meaningful to develop an accurate model to predict the dynamical motion of an unmanned sailboat. Considering cost and convenience, this work proposes a parameter identification method based on the combination of experiments and numerical analysis. Firstly, a free-running trial is carried out by utilizing the propellers on the studied sailboat to acquire real navigation information. Secondly, particle swarm optimization (PSO), which is highly efficient and easily implemented, is designed to acquire the hydrodynamic parameters of the sailboat’s hull. At the same time, the aerodynamic parameters of the sail are acquired by computational fluid dynamics (CFD) simulation. Finally, a three degree-of-freedom (DOF) model is established, the effectiveness of which is verified through comparisons between sea trials and simulation. The results prove that this parameter identification method has the desired accuracy and reliability.

Green flash extraction optimization of Cynanchum wilfordii adventitious roots and evaluation of their cancer cell inhibition - Ke-Xin Zhang; Wei-Qi Ye; Seok Joong Yun; Zhong-Yu Zhou; Shuo Yu; Xuan-Chun Piao; Jun Jiang; Mei-Lan Lian (Sustainable Chemistry and Pharmacy, 2024)

Exploring the leaf regeneration cycles response of Zostera japonica to ocean acidification - Hongzhen Wang; Yu Zang; Jiayi Xin; Xinqi Li; Song Xue; Shuo Liang; Xuexi Tang; Jun Chen (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

The bio–accumulation and –magnification of microplastics under predator–prey isotopic relationships - Shike Gao; Shuo Zhang; Zhihua Feng; Jikun Lu; Guanghui Fu; Wenwen Yu (Journal of Hazardous Materials, 2024)

Remediation of atrazine contaminated soil with the help of hydrothermal carbon/diatomite composite inoculated with degrading microorganisms - Tong Zhang; Hailing Yu; Zhaolian Han; Shuo Zhang; Jingjing Zhang; Shuang Xu; Zhihui Dong; Zhiqiang Cheng (Journal of Environmental Chemical Engineering, 2024)

Discovery of Late Cretaceous basalts in the Asuo area, Central Tibet: Implications for orogenic root removal beneath the Lhasa-Qiangtang orogenic belt - Di Shen; Ming Wang; Chang-sheng Yu; Quewang Danzeng; Sheng-shuo Zhang; Jin-lu Zhou; Bin-xuan Hao (Journal of Asian Earth Sciences, 2024)

Amelioration of tiger nut insoluble dietary fiber as a partial substitute for fat in meat emulsions: Techno-functional properties and in vitro protein digestibility - Xi-xi Wang; Ling-yu Wang; Shuo-meng Li; Zhong-kai Zhou (Food Research International, 2024)

Bacterial specialists playing crucial roles in maintaining system stability and governing microbial diversity in bioremediation of oil-polluted sediments under typical deep-sea condition - Yanlu Qiao; Wenhui Xu; Lingbing Kong; Mingan Shen; Shuo Wang; Yudi Sun; Yu Gao; Qing Jiang; Jianliang Xue; Dongle Cheng; Yuyang Liu (Bioresource Technology, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Cross-Scale Quantitative and Qualitative Study of Grotto Sandstone Under Salt Weathering - Sicheng Lin; Luqi Wang; Wengang Zhang; Shuo Wang; Kaiqiang Zhang; Yu Lei; Siwei Jiang; Huili Chen; Gang Zhao; Xuemei Feng (Rock Mechanics and Rock Engineering, 2024)

Wolbachia of phylogenetic supergroup K identified in oribatid mite Nothrus anauniensis (Acari: Oribatida: Nothridae) - Shuo-Fang Kang; Yu Chen; Jun Chen (Experimental and Applied Acarology, 2024)

Optimizing microbial electrolysis cell performance: strategies to mitigate electron mediator degradation on membranes - Shuo Zhao; Yu Zeng; Ying Li; Zhen Wang; Li Chen; Kequan Chen (Biotechnology Letters, 2024)

Design and experimentation of direct injection in-line mixing control system for sprayers - Yu Chen; Yuxiang Chen; Peijie Guo; Shuo Zhang; Hongling Jin; Sugirbay Adilet; Jun Chen (Computers and Electronics in Agriculture, 2024)

Bridging ecological processes to diversity formation and functional profiles in belowground bacterial communities - Beibei Chen; Ziheng Peng; Shi Chen; Yu Liu; Jiejun Qi; Haibo Pan; Hang Gao; Jiamin Gao; Chunling Liang; Jiai Liu; Xun Qian; Xiao Zhang; et al. (Soil Biology and Biochemistry, 2024)

Elevated temperature as the dominant stressor on the harmful algal bloom-causing dinoflagellate Prorocentrum obtusidens in a future ocean scenario - Wei-Ping Zhang; Hui Wei; Shuo-Yu Zhang; Shu-Feng Zhang; Yang Zhou; Wen-Jing Sun; Jae-Seong Lee; Minghua Wang; Da-Zhi Wang (Science of The Total Environment, 2024)

Detecting the interaction between microparticles and biomass in biological wastewater treatment process with Deep Learning method - Tianlong Jia; Zhaoxu Peng; Jing Yu; Antonella L. Piaggio; Shuo Zhang; Merle K. de Kreuk (Science of The Total Environment, 2024)

Late Triassic basaltic andesites unveil inception of Neo-Tethys Ocean in Gyaca area of Tethyan Himalaya - Qinwen Gao; Feng Huang; Song Zhang; Yunchuan Zeng; Mingjian Li; Shuo Wang; Chenyuan Hua; Hongxia Yu; Yinhui Zhang; Jifeng Xu (Lithos, 2024)

Nondestructive electrochemical capacity restoration of LiNi1/3Co1/3Mn1/3O2 cathode for lithium batteries - Chenyu Bai; Yiding Jiao; Wei Mao; Fangyan Li; Shuo Yang; Jie Song; Yiran Li; Luhe Li; Yu Deng; Peng Wang; Ye Zhang (Chemical Engineering Journal, 2024)

Glutamine metabolism in fluorosis: Integrated metabolomics and transcriptomics analysis - Yue Ba; Shu Niu; Zichen Feng; Shuo Yang; Shuiyuan Yu; Chaofan Shi; Xuecheng Jiao; Guoyu Zhou; Fangfang Yu (Science of The Total Environment, 2024)

Identification and transcriptome analysis of a photosynthesis deficient mutant of Populus davidiana Dode - Xinyu Wang; Yan Zhou; Song Chen; Meiqi Lu; Chunyu Guan; Ruihan He; Yue Yu; Huiling Yan; Wenxuan Liu; Siyuan Li; Yuanfu Liu; Kanglei Li; et al. (Plant Science, 2024)

Enhanced and robust nitrogen removal using an integrated zeolite and partial denitrification anammox process - Shuo Wang; Tan Jiang; Xiang Hao; Yu Dai; Jiayi Yang; Bo Wang (Journal of Environmental Management, 2024)

Uranium extraction from wastewater by heteroatom-doped carbon microspheres derived from polyphosphazene loading with zinc oxide - Huojiao Chen; Yunyun Bao; Luowen Xu; Shuo Ning; Changfu Wang; Yun Wang; Dingzhong Yuan; Fengtao Yu; Yan Liu (Journal of Environmental Chemical Engineering, 2024)

Simultaneous fouling and scaling-resistant membrane based on glutamic acid grafting for robust membrane distillation - Yin-Shuang Hu; Shuo-Chun Ke; Yu-Xi Huang (Desalination, 2024)

A novel vanadium-copper rechargeable battery for solar energy conversion and storage - Chunkun Lin; Jiangxin Wang; Kaixin Zhang; Huibin Shi; Yibing Liu; Kuanhong Mei; Minmin Liu; Yu Zhang; Shuo Li (Chemical Engineering Journal, 2024)

Mechanisms elucidation of secondary seawater batteries: From ion migration to conversion for sustainable energy storage - Yile Lu; Yu Yuan; Tianyue Liang; Haowei Jia; Linghui Meng; Xinren Zhang; Shuo Zhang; Bohao Wen; Ziheng Feng; Tao Yin; Peiyuan Guan; Lu Zhou; et al. (Chemical Engineering Journal, 2024)

Constructing alkaline microenvironment on catalyst surface for enhanced electrocatalytic synthesis of hydrogen peroxide in a neutral electrolyte - Haoyu Li; Peike Cao; Hourui Zhang; Kaixuan Wang; Shuo Chen; Hongtao Yu; Xie Quan (Chemical Engineering Journal, 2024)

MiR-223-3p-loaded Exosomes Derived from Bone Marrow Mesenchymal Stem Cells Ameliorate Mouse Myocardial Infarction Injury through Inhibiting NLRP3 Inflammasome Activation - Shuo Wang; Xiangyu Zhang; Yu Wang; Shuiling Wang; Liu Li (Journal of Medical and Biological Engineering, 2024)

Unearthing the impact of urban sprawl on transport carbon dioxide emissions: Fresh evidence from 274 Chinese cities - Tianheng Shu; Taofang Yu; Xia Liao; Shuo Yang (Journal of Geographical Sciences, 2024)

Biotic/abiotic transformation mechanisms of phenanthrene in iron-rich constructed wetland under redox fluctuation - Jiaxing Lu; Peihan Yu; Jian Zhang; Zizhang Guo; Yanwei Li; Shuo Wang; Zhen Hu (Water Research, 2024)

Enhanced nitrogen removal from low C/N municipal wastewater through nitrification, partial denitrification and anammox via a step-feed strategy: Synergistic contribution by bacteria in biofilm and floc sludge - Wenjie Li; Lu Wang; Xiaodi Li; Yu Dai; Shuo Wang; Wen Wang; Jiayi Yang; Bo Wang (Journal of Water Process Engineering, 2024)

Flexible roles of TiO2 in enhancing carrier separation for the high photocatalytic performance of water treatment under different spectrum sunlight - Zhongxi Lu; Shaosheng Rao; Shuo Li; Xiaohui Yu; Haopeng Jiang; Yangyang Sun; Weikang Wang; Lele Wang; Juan Yang; Qinqin Liu (Journal of Water Process Engineering, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Amorphous bimetallic-organic framework enable accelerated redox kinetics and polysulfide trapping for lithium-sulfur batteries - Jingkun Bi; Lu Chen; Xiao Yan; Jian Guo; Ya Tang; Ma Jian; Shuo Meng; Kexuan Liao; Jia Yu; Wenli Yao; Ting He; Hongbin Zhao (Chemical Engineering Journal, 2024)

Frequent Flowering but Low Reproductive Success of the Dioecious Seagrass Enhalus acoroides (L.f.) Royle in Li’an lagoon, China - Shuo Yu; Lijun Cui; Brigitta I. van Tussenbroek; Yunchao Wu; Fangchao Zhu; Juan Diego Gaitán-Espitía; Kai Jiang (Estuaries and Coasts, 2024)

Linking regional species pool size to dispersal–selection relationships in soil fungal communities across terrestrial ecosystems - Beibei Chen; Haibo Pan; Xiaofeng Song; Yajun Yao; Jiejun Qi; Xiaoli Bai; Ziheng Peng; Yu Liu; Shi Chen; Hang Gao; Chunling Liang; Jiai Liu; et al. (Global Ecology and Biogeography, 2024)
Aim Revealing the role of regional species pool size in community assembly rules is essential for extending the species‐pool framework to large‐scale community ecology, and thus for more comprehensive understanding of biodiversity formation. However, little has been done to couple the regional species‐pool effect into local ecological processes in soil fungal communities, which play essential roles in ecosystems worldwide. Here, we performed large‐scale soil surveys of fungal communities to examine the linkage between regional species pool size and D ispersal– S election R elationships (DSRs), and their relations to community structure. Location China. Time period July–August 2019. Major taxa studied Fungal communities. Methods By conducting the nationwide soil survey of ~1200 samples from various ecosystems across China, including agricultural, forest, grassland, and wetland soils, we examined the linkage between regional species pool size and DSRs, and their relationship to fungal community structure. Results We found that selection was negatively related to dispersal, which was consistent with the general view that the strength of selection is weakened by dispersal homogenization, and that this relationship was stronger in regions with larger species pools. Moreover, an increase in community dispersion was correlated with stronger effect size of DSRs, implying greater heterogeneity among fungal communities under larger species pools. Main conclusions Our study clearly illustrates the association of regional species pool size with local assembly rules and community formation of soil fungi across terrestrial ecosystems.

Research on Hydrodynamics of Trans-Media Vehicles Considering Underwater Time-Varying Attitudes - Shuo Liu; Chihao Du; Yijie Han; Yu Zhang; Wanglin Lin; Yong Cai; Tao Wang (Journal of Marine Science and Engineering, 2024)
A trans-media vehicle is a new type of equipment that can adapt to two environments, water and air, to maintain optimal hydrodynamic and aerodynamic performance. However, no matter what kind of trans-media vehicle, its dynamics are much more complicated when traversing the interface of the medium, as the parameters are time-varying due to the change in ambient medium and vehicle attitudes. In order to improve the stability and performance of the trans-media vehicle in complex environments, an accurate mathematical model is established to characterize the dynamics of the trans-media vehicle in this process in this study. The time-varying hydrodynamic coefficients with different attitudes or depths are obtained using computational fluid dynamics software. The mathematical model is solved iteratively using a Runge–Kutta solver to calculate the dynamic response. A prototype of trans-media vehicle is fabricated, and motion experiments are performed in the pool. The experimental results confirm the effectiveness of the established model and lay the foundation for further controller design, providing a reference for the dynamic modeling of other similar equipment operating in complex environments. The primary novelty of this study lies in the fact that the established dynamic model considers the complex interaction between the attitude of the trans-media vehicle and the inherent different properties of water and air and utilizes computational fluid dynamics software to accurately obtain time-varying coefficients under different attitudes and depths. This approach not only recognizes the criticality of orientation-dependent hydrodynamic coefficients but also incorporates their temporal variations, which were often overlooked in previous studies.

Bayesian analysis of physiologically based toxicokinetic (PBTK) modeling for pentachlorophenol exposure in pregnant women - Chunfeng Wu; Yajiao Tan; Xiaoyi Wei; Xun Li; Sifei Sun; Bing Lyu; Zhen Shen; Xiao Wei; Shuo Xiao; Yuanyuan Ruan; Jun Yu; Gengsheng He; et al. (Toxicology in Vitro, 2024)

N-acetyl-l-methionine dietary supplementation improves meat quality by oxidative stability of finishing Angus heifers - Yue Liu; Wanbao Chen; Shuo Zhang; Xiaohui Zhu; Hao Wu; Qingxiang Meng; Muhammad Zahoor Khan; Zhu Yu; Zhenming Zhou (Meat Science, 2024)

Opaline silica precipitations in the Permian Fengcheng Formation indicate hot spring environments in north Mahu Sag, NW China - Kuanhong Yu; Shuo Du; Yingchang Cao; Tao Zhang (Marine and Petroleum Geology, 2024)

MgO-loaded tubular ceramic membrane with spatial nanoconfinement for enhanced catalytic ozonation in refractory wastewater treatment - Zijie Lu; Haokun Bai; Lanlan Liang; Shuo Chen; Hongtao Yu; Xie Quan (Journal of Hazardous Materials, 2024)

Research on an in-situ synchronous CO elimination method in blasting operations and engineering experimental application based on nano-CO catalysts - Sheng He; Shuo Gao; Jia Li; Shujing He; Yitao Yu; Jianguo Wu; Xiao Wang; Guiming Wang; Xiaoyu Chen; Fubao Zhou (Journal of Environmental Chemical Engineering, 2024)

Effects of air frying on protein digestive properties in scallop (Patinopecten yessoensis) adductor muscles and the mechanisms involved - Zi-Ye Wang; Ying Luo; Rui Zheng; Shuo Lv; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2024)

Unveiling the comprehensive performance and safety advancements in PVC films through environmentally friendly PMgLaCe-LDH incorporation - Yongchun Li; Lijuan Qiao; Yu Tang; Zhi Jia; Xiang Guan; Zhaocai Wang; Shuo Xu; Weilu Yang; Yunfei Ma; Yuting Qiao; Bingxin Liu; Li Gao; et al. (Chemical Engineering Journal, 2024)

Combined transcriptomics and metabolomics analysis reveals salinity stress specific signaling and tolerance responses in the seagrass Zostera japonica - Shuo Liang; Yu Zang; Hongzhen Wang; Song Xue; Jiayi Xin; Xinqi Li; Xuexi Tang; Jun Chen (Plant Cell Reports, 2024)

Positive feedback between the negative phase of interannual component of the Pacific Decadal Oscillation and La Niña - Hong-Shuo Tang; Yu Zhang; Yu Kosaka; Jun-Chao Yang; Qi Shu; Yi Liu; Xiaopei Lin (Climate Dynamics, 2024)

Optimization of recirculating water scallop larval cultivation system based on EDEM-fluent coupling - Xiuchen Li; Yu Yang; Dongshuo Liu; Shuo Chen; Shuqiao Wu; Xiang Yuan; Zibo Liu; Yubao Wang; Hanbing Zhang (Frontiers in Marine Science, 2024)
This article aims to address the issues of low cultivation density and high labor intensity of manual water exchange in existing scallop seedling ponds, an upwelling recirculating water system for scallop larval cultivation is designed. EDEM-Fluent coupled model was used to simulate the movement of scallop larvae in the culture cone in order to guarantee the uniform distribution of larvae in the cultivation device. Design-Expert software was utilized to investigate the impact of the bottom cone angle( θ ), the column height/cone height ratio( n ) and the inflow velocity( v ) on the variation coefficients of the axial and radial distributions of D-shaped larvae within the culture cone. The results indicated that θ = 108.97° and n = 1.8 represent the ideal structural parameters for the culture cone. The further investigation of the culture cones prototype was conducted to examine the impact of the inlet deflector angle ( α ), cultivation density ( τ ), and inflow velocity ( v ) on its performance. θ =108.97°, n =1.8, v =0.19m/s, α =60.94°, and τ=110pcs/ml were found to be the ideal combination of parameters, in this scenario, the D-shaped larvae’s radial distributions’ coefficients of variation is 22.13%, the error between the experimental and simulation results is 4.41%. Research has shown that EDEM-Fluent based simulation analysis methods can be used for the design and parameter optimization of upwelling recirculating water scallop larval cultivation system, this paper can provide a reference for the design of an upwelling recirculating water scallop larval cultivation system.

Optimization of Joint Scheduling for Automated Guided Vehicles and Unmanned Container Trucks at Automated Container Terminals Considering Conflicts - Liangyong Chu; Zijian Gao; Shuo Dang; Jiawen Zhang; Qing Yu (Journal of Marine Science and Engineering, 2024)
Port development is a critical component in constructing a resilient transportation infrastructure. The burgeoning integration of automated guided vehicles (AGVs) within container terminals, in conjunction with the orchestrated scheduling of unmanned container trucks (UCTs), is essential for the sustainable expansion of port operations in the future. This study examined the influence of AGVs in automated container terminals and the synergistic scheduling of UCTs on port operations. Comparative experiments were meticulously designed to evaluate the feasibility of integrated scheduling schemes. Through the development of optimization models that consider conflict-free paths for both AGVs and UCTs, as well as strategies for conflict resolution, a thorough analysis was performed. Advanced genetic algorithms were engineered to address task-dispatching models. In contrast, the A* optimization search algorithm was adapted to devise conflict-free and conflict-resolution paths for the two vehicle types. A range of scaled scenarios was utilized to assess the impact of AGVs and UCTs on the joint-scheduling process across various configuration ratios. The effectiveness of the strategies was appraised by comparing the resultant path outcomes. Additionally, comparative algorithmic experiments were executed to substantiate the adaptability, efficacy, and computational efficiency of the algorithms in relation to the models. The experimental results highlight the viability of tackling the joint-scheduling challenge presented by AGVs and UCTs in automated container terminals. When juxtaposed with alternative scheduling paradigms that operate independently, this integrated approach exhibits superior performance in optimizing the total operational costs. Consequently, it provides significant insights into enhancing port scheduling practices.

Deep underwater image compression for enhanced machine vision applications - Hanshu Zhang; Suzhen Fan; Shuo Zou; Zhibin Yu; Bing Zheng (Frontiers in Marine Science, 2024)
Underwater image compression is fundamental in underwater visual applications. The storage resources of autonomous underwater vehicles (AUVs) and underwater cameras are limited. By employing effective image compression methods, it is possible to optimize the resource utilization of these devices, thereby extending the operational time underwater. Current image compression methods neglect the unique characteristics of the underwater environment, thus failing to support downstream underwater visual tasks efficiently. We propose a novel underwater image compression framework that integrates frequency priors and feature decomposition fusion in response to these challenges. Our framework incorporates a task-driven feature decomposition fusion module (FDFM). This module enables the network to understand and preserve machine-friendly information during the compression process, prioritizing task relevance over human visual perception. Additionally, we propose a frequency-guided underwater image correction module (UICM) to address noise issues and accurately identify redundant information, enhancing the overall compression process. Our framework effectively preserves machine-friendly features at a low bit rate. Extensive experiments across various downstream visual tasks, including object detection, semantic segmentation, and saliency detection, consistently demonstrated significant improvements achieved by our approach.

A review of vision-based crop row detection method: Focusing on field ground autonomous navigation operations - Shuo Zhang; Yu Liu; Kun Xiong; Yonghao Tian; Yuefeng Du; Zhongxiang Zhu; Mingwei Du; Zhiqiang Zhai (Computers and Electronics in Agriculture, 2024)

Honokiol and magnolol: A review of structure-activity relationships of their derivatives - Si-Yang Dai; Wen-Xiu Qin; Shuo Yu; Chang Li; Yi-Hui Yang; Yue-Hu Pei (Phytochemistry, 2024)

Correlations between bone metabolism biomarkers and fluoride exposure in adults and children - Shuo Yang; Shuiyuan Yu; Yuhui Du; Zichen Feng; Xuecheng Jiao; Qinyang Li; Jingjing Wu; Lei Sun; Juan Zuo; Xiaoli Fu; Zhiyuan Li; Hui Huang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

The ecological risk and fate of microplastics in the environmental matrices of marine ranching area in coastal water - Shike Gao; Shuo Zhang; Zhihua Feng; Jikun Lu; Guanghui Fu; Wenwen Yu (Journal of Hazardous Materials, 2024)

Porous molecularly imprinted beads for highly specific separation of 10-hydroxycamptothecine: An imprinted strategy based on modified cellulose hydrogel - Zidan Luo; Mengfei Tian; Shuo Liu; Qi Liang; Yaru Zhang; Xiaofei Xie; Yu Zhang; Ziqi Xu; Chunying Li; Chunjian Zhao (Chemical Engineering Journal, 2024)

The phytochemistry, pharmacology, pharmacokinetics, quality control, and toxicity of Forsythiae Fructus: An updated systematic review - Jin-Jin Li; Zi-Hao Chen; Cheng-Jun Liu; Yu-Shuo Kang; Xin-Pu Tu; Hong Liang; Wei Shi; Feng-Xiang Zhang (Phytochemistry, 2024)

Evolutionary genomics of climatic adaptation and resilience to climate change in alfalfa - Fan Zhang; Ruicai Long; Zhiyao Ma; Hua Xiao; Xiaodong Xu; Zhongjie Liu; Chunxue Wei; Yiwen Wang; Yanling Peng; Xuanwen Yang; Xiaoya Shi; Shuo Cao; et al. (Molecular Plant, 2024)

Simultaneous production of biosurfactant and extracellular unspecific peroxygenases by Moesziomyces aphidis XM01 enables an efficient strategy for crude oil degradation - Ji-Zheng Song; Chu-Qi Wang; Guan-Shuo Yu; Zhe Sun; Ai-Hua Wu; Zhen-Ming Chi; Guang-Lei Liu (Journal of Hazardous Materials, 2024)

Predicting soil organic carbon content using simulated insitu spectra and moisture correction algorithms in southern Xinjiang, China - Peimin Yang; Yu Wang; Bifeng Hu; Shuo Li; Songchao Chen; Defang Luo; Jie Peng (Geoderma Regional, 2024)

WITHDRAWN: Organic molecule-mediated synthesis of GdPO4:Eu3+micro/nano-luminescent materials and MRI tracing performance evaluation - Ziyi Guo; Jingjing Liu; Meng Lv; Shuo Wang; Fei Li; Tong Xu; Ruyun Wan; Yu Wang; Jing Huang; Long Zhang (Chemical Engineering Journal, 2024)

Response of photosynthetic characteristics and antioxidant system in the leaves of safflower to NaCl and NaHCO3 - Linlin Song; Yongliang Yu; Hongzhi Chen; Yuwei Feng; Shuo Chen; Huihui Zhang; Haijia Zhou; Li Meng; Yue Wang (Plant Cell Reports, 2024)

Noninvasive Deep Brain Stimulation via Temporal Interference Electric Fields Enhanced Motor Performance of Mice and Its Neuroplasticity Mechanisms - Xiaodong Liu; Shuo Qi; Lijuan Hou; Yu Liu; Xiaohui Wang (Molecular Neurobiology, 2024)

Influence of main operating parameters on the incineration characteristics of municipal solid waste (MSW) - Wuqing Zeng; Yu Wang; Qingguo Bu; Shuo Ma; Haoran Hu; Dandan Ma; Hongting Ma (Process Safety and Environmental Protection, 2024)

Comparative study on dynamic responses of integrated installation process of a 5-MW and a 15-MW offshore wind turbine considering a pre-installed foundation - Jiaming Liu; Zhongming Xiao; Kai Wang; Shuo Huang; Yu Du (Ocean Engineering, 2024)

Improving lipid digestion by modulating interfacial structure of fat globule based on milk fat globule membrane and different phospholipids - Qian Ma; Meng Sun; Yanjie Zhao; Shuo Chen; Xiaodong Li; Lu Liu; Xiuxiu Zhang; Yuxin Wang; Kouadio Jean Eric-Parfait Kouame; Xiaoxue Yu (Food Hydrocolloids, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Bio-based and fireproof radiative cooling aerogel film: Achieving higher sustainability and safety - Wei Cai; Bicheng Lin; Liangyuan Qi; Tianyang Cui; Zhaoxin Li; Junling Wang; Sicheng Li; Chengfei Cao; Mohammad Ziaur Rahman; Xin Hu; Rujun Yu; Shuo Shi; et al. (Chemical Engineering Journal, 2024)

Key characteristics of new particle formation events occurring simultaneously in the Yangtze River Delta and northeast rural sites in China - Shuo Liu; Peng Wang; Qianli Ma; Xiaojing Shen; Hanqing Kang; Junying Sun; Quan Liu; Yangmei Zhang; Muzhen Shi; Dajiang Yu; Junting Zhong; Xinyao Hu; et al. (Atmospheric Environment, 2024)

Magnetic enhancement of road dusts in Shanghai and its implications for the urban environment - Yan-Shuo Zhang; Xue-Feng Hu; Xin-Dong Wang; Le-San Mei; Yu-Ting Jia (Journal of Soils and Sediments, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Bayesian hybrid-kernel machine-learning-assisted sensitivity analysis and sensitivity-relevant inverse modeling for groundwater DNAPL contamination - Zeyu Hou; Ke Zhao; Shuo Wang; Yu Wang; Wenxi Lu (Journal of Hydrology, 2024)

Optimum investment strategy for hydrogen-based steelmaking project coupled with multiple uncertainties - Shuo Xu; Xiaoyang Wang; Yingqi Jiang; Biying Yu; Yi-Ming Wei (Journal of Environmental Management, 2024)

A novel derivative synchronous fluorescence method for the rapid, non-destructive and intuitive differentiation of denitrifying bacteria - Huang-Zhou Lv; Jinliang Chen; Yan Zhao; Yu Li; Shuo-Hui Cao; Wei-Peng Cai; Liang Shen; Yinghua Lu; Yao-Qun Li (Journal of Environmental Management, 2024)

Solid waste-derived solar desalination devices: Enhanced efficiency in water vapor generation and diffusion - Jiahui Yu; Chenxi Wang; Shu Liu; Shuo Yang; Xingmin Du; Shuai Liu; Changxiang Shao; Huijun Kong; Baolei Wang; Tao Wu; Chenwei Li (Chemical Engineering Journal, 2024)

Oxidation Characterization of Water Immersion Coal on Pore Evolution and Oxygen Adsorption Behavior - Xin-xiao Lu; Guo-yu Shi; Shuo Wang; Jin-xiang Xiao (Natural Resources Research, 2024)

Intramuscularly injected long-acting testosterone-cholesterol prodrug suspension with three different particle sizes: extended in vitro release and enhanced in vivo safety - Shuo Li; Zhaomeng Wang; Jiang Yu; Chuang Zhang; Jianying Ye; Hengzhi Liu; Yiguo Jiang; Zhonggui He; Yongjun Wang (Drug Delivery and Translational Research, 2024)

Genome-wide identification and quantification of salinity-responsive Na+/K+-ATPase α-subunits in three salmonids - Yue Su; Shuang-En Yu; Yong-Xu Sun; Liang Zhang; Yue Tan; Yu-Yang Zhang; Shuo Wang; Yan-Gen Zhou; Li-Sha Hu; Yun-Wei Dong (Aquaculture, 2024)

New design to enhance phosphonate selective removal from water by MOF confined in hyper-cross-linked resin - Shuangli Li; Yu Zhang; Shuo Zhao; Liying Zhang; Sen Qiao; Jiti Zhou (Science of The Total Environment, 2024)

Whole blood cadmium levels and depressive symptoms in Chinese young adults: A prospective cohort study combing metabolomics - Liu Yang; Qingxia Yu; Siqi Dou; Xinyuan Li; Shuo Wen; Jia Zhang; Mingyu Feng; Lailai Yan; Chengshuai Zhang; Shanshan Li; Peng Lu; Yuming Guo (Journal of Hazardous Materials, 2024)

The ecological characteristics of the safe sites for early-stage establishment of Chamaecyparis obtusa var. formosana seedlings in Taiwan - Shuo Wei; Yu-Pei Tseng; David Zelený (Forest Ecology and Management, 2024)

The impact of natural spices additions on hazards development and quality control in roast beef patties - Zhenting Yu; Yingshuang Lu; Fan Wei; Yan Zhang; Lu Dong; Shuo Wang (Food Chemistry, 2024)

Accelerating the generation of NiOOH by in-situ surface phosphating nickel sulfide for promoting the proton-coupled electron transfer kinetics of urea electrolysis - Xin Guo; Longyu Qiu; Menggang Li; Fenyang Tian; Xue Ren; Sheng Jie; Shuo Geng; Guanghui Han; Yarong Huang; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2024)

Thermally managed and fireproof composite aerogels for safer and year-round energy saving - Wei Cai; Zhaoxin Li; Heng Xie; Wei Wang; Tianyang Cui; Bicheng Lin; Liangyuan Qi; Xin Hu; Yu Du; Yang Ming; Shuo Shi; Daming Chen; et al. (Chemical Engineering Journal, 2024)

Enhanced adsorption of micropollutants on oxygen plasma-modified carbon nanotubes (O-CNTs) under electrochemical assistance - Chunhui Yu; Jiajian Xing; Kunkun Xu; Shuo Chen (Journal of Water Process Engineering, 2024)

High-efficiency recycling of Mo and Ni from spent HDS catalysts: Enhanced oxidation with O2-rich roasting and selective separation with organic acid leaching- complexation extraction - Haoran Yu; Changmin Liu; Shuo Liu; Yu Gu; Shuya Wang; Ali Yaraş; Linchao Hu; Wenyi Zhang; Mingguo Peng; Hasan Arslanoğlu; Linqiang Mao (Journal of Hazardous Materials, 2024)

Function-oriented bifunctional Mg & MoP modified polymeric carbon nitride for selective photoreduction CO2 to CH4 - Jun-ying Tang; Wei-guo Pan; Yu-lian He; Tian-shuo Zhao; Qing-shan Wang; Rui-tang Guo (Chemical Engineering Journal, 2024)

Revealing the roles of biochar derived from iron-rich fermented sludge residue in anaerobic digestion - Hong-Yu Jin; Zhang-Wei He; Yong-Xiang Ren; Zheng-Shuo Zou; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Zhihua Li; Aijie Wang (Chemical Engineering Journal, 2024)

Significant influence of nitrate on light absorption enhancement of refractory black carbon in the winter of 2022 in Beijing - Xinyao Hu; Quan Liu; Yangmei Zhang; Xiaojing Shen; Jiayuan Lu; Aoyuan Yu; Shuo Liu; Huizheng Che; Xiaoye Zhang; Junying Sun (Atmospheric Environment, 2024)

Size-resolved effective density of ambient aerosols measured by an AAC–SMPS tandem system in Beijing - Jiayuan Lu; Xiaojing Shen; Qianli Ma; Aoyuan Yu; Xinyao Hu; Yangmei Zhang; Quan Liu; Shuo Liu; Huizheng Che; Xiaoye Zhang; Junying Sun (Atmospheric Environment, 2024)

Mean annual precipitation modulates the assembly of high-affinity methanotroph communities and methane oxidation activity across grasslands - Chenxiao Ding; Yaowei Liu; Marc G. Dumont; Hong Pan; Kankan Zhao; Yuanheng Li; Qichun Zhang; Yu Luo; Shuo Jiao; Hongjie Di; Jianming Xu; Yong Li (Agriculture, Ecosystems & Environment, 2024)

Catch organism assemblages along artificial reefs area and adjacent waters in Haizhou Bay - Shike Gao; Bin Xie; Chengyu Huang; Xiao Zhang; Shuo Zhang; Wenwen Yu (Acta Oceanologica Sinica, 2024)

Effects of different picking patterns and sequences on the vibration of apples on the same branch - Guangrui Hu; Jianguo Zhou; Qingyu Chen; Tongyun Luo; Puhang Li; Yu Chen; Shuo Zhang; Jun Chen (Biosystems Engineering, 2024)

Combined microbe-plant remediation of cadmium in saline-alkali soil assisted by fungal mycelium-derived biochar - Zirun Zhao; Lin Liu; Ying Sun; Liling Xie; Shuo Liu; Mingchun Li; Qilin Yu (Environmental Research, 2024)

Long-Life flexible mild Ag-Zn fibrous battery with bifunctional gel electrolyte - Yanzhe Zhu; Jiajun Fan; Shuo Zhang; Ziheng Feng; Chao Liu; Renbo Zhu; Yunjian Liu; Peiyuan Guan; Mengyao Li; Zhaojun Han; Tao Wan; Jianbo Tang; et al. (Chemical Engineering Journal, 2024)

Enhancing Mo leaching efficiency from spent catalyst via Fenton-like oxidation process: A comprehensive investigation of leaching effects, mechanism and environmental impacts - Haoran Yu; Shuo Liu; Ali Yaraş; Linchao Hu; Wenyi Zhang; Mingguo Peng; Hasan Arslanoğlu; Qingqing Huang; Bolormaa Oyuntsetseg; Bingying Gao; Linqiang Mao (Chemical Engineering Journal, 2024)

Porous polypyrrole Nanotube-Based Organohydrogels: Versatile materials for robust electromagnetic interference shielding in harsh environments - Lingsai Meng; Shuo Yang; Yu Ma; Yupeng Zou; Yang Zhang; Gang Chen; Chengjun Dong; Hongtao Guan (Chemical Engineering Journal, 2024)

Genetic diversity of RNA viruses infecting invertebrate pests of rice - Haoran Wang; Shufen Chao; Qing Yan; Shu Zhang; Guoqing Chen; Chonghui Mao; Yang Hu; Fengquan Yu; Shuo Wang; Liang Lv; Baojun Yang; Jiachun He; et al. (Science China Life Sciences, 2024)

The neglected roles of adjacent natural ecosystems in maintaining bacterial diversity in agroecosystems - Ziheng Peng; Yunfeng Yang; Yu Liu; Lianyan Bu; Jiejun Qi; Hang Gao; Shi Chen; Haibo Pan; Beibei Chen; Chunling Liang; Xiaomeng Li; Yining An; et al. (Global Change Biology, 2024)
A central aim of community ecology is to understand how local species diversity is shaped. Agricultural activities are reshaping and filtering soil biodiversity and communities; however, ecological processes that structure agricultural communities have often overlooked the role of the regional species pool, mainly owing to the lack of large datasets across several regions. Here, we conducted a soil survey of 941 plots of agricultural and adjacent natural ecosystems (e.g., forest, wetland, grassland, and desert) in 38 regions across diverse climatic and soil gradients to evaluate whether the regional species pool of soil microbes from adjacent natural ecosystems is important in shaping agricultural soil microbial diversity and completeness. Using a framework of multiscales community assembly, we revealed that the regional species pool was an important predictor of agricultural bacterial diversity and explained a unique variation that cannot be predicted by historical legacy, large‐scale environmental factors, and local community assembly processes. Moreover, the species pool effects were associated with microbial dormancy potential, where taxa with higher dormancy potential exhibited stronger species pool effects. Bacterial diversity in regions with higher agricultural intensity was more influenced by species pool effects than that in regions with low intensity, indicating that the maintenance of agricultural biodiversity in high‐intensity regions strongly depends on species present in the surrounding landscape. Models for community completeness indicated the positive effect of regional species pool, further implying the community unsaturation and increased potential in bacterial diversity of agricultural ecosystems. Overall, our study reveals the indubitable role of regional species pool from adjacent natural ecosystems in predicting bacterial diversity, which has useful implication for biodiversity management and conservation in agricultural systems.

Study on the Hydrodynamic Performance of the Beam Used in the Antarctic Krill Beam Trawl - Yuyan Li; Zheng Liu; Zhongqiu Wang; Xun Zhang; Lumin Wang; Yu Zhang; Shuo Ma; Guangrui Qi; Yongjin Wang (Fishes, 2023)
The beam trawl is one of the primary operational trawls for Antarctic krill, and its beam provides horizontal expansion support for the trawl net. The hydrodynamic performance of the beam significantly affects the vertical expansion and sinking performance of the trawl, as well as impacts the energy consumption of the fishing vessel. In this study, the beam of the Antarctic krill trawl used on the “Shen Lan” fishing vessel served as a prototype. Three types of beams, cylindrical, airfoil, and elliptical, were designed. The hydrodynamic performances of beams with different shapes at different angles of attack were studied using numerical simulation, and the accuracy of the numerical simulation was validated through the flume test. The results show that the cylindrical beam has a higher drag coefficient and a lower lift coefficient, compared to the airfoil beam and the elliptical beam. Under different angles of attack, the cylindrical beam’s drag coefficient is, on average, 49.54% higher than that of the airfoil beam and 59.74% higher than that of the elliptical beam. Its lift coefficient is 87.79% lower than that of the airfoil beam and 85.06% lower than that of the elliptical beam, respectively. At different angles of attack, the hydrodynamic coefficients of the airfoil beam and the elliptical beam are similar, and their trends, with respect to the angle of attack, are generally consistent. The drag coefficients increase with an increasing angle of attack, while the lift coefficients show a trend of initially increasing and then decreasing with an increasing angle of attack. The absolute values of the lift coefficients for the airfoil beam and the elliptical beam both reach their maximum values at an angle of attack of 45°, with values of 0.703 and 0.473, respectively. Compared to the cylindrical beam, the hydrodynamic performances of the airfoil beam and elliptical beam are superior.

Estimating Spatiotemporal Fishing Effort of Trawlers with Vessel-Monitoring System Data: A Case Study of the Sea Area of the Bohai Sea and the Yellow Sea, China - Dan Li; Feng Lu; Shuo Xu; Huiyuan Liu; Muhan Xue; Guohui Cui; Zhenhua Ma; Hui Fang; Yu Wang (Journal of Marine Science and Engineering, 2023)
Measuring the distribution of the fishing effort of trawlers is of great significance for describing marine fishery activities, quantifying fishing systems in terms of marine ecological pressure, and revising the regulations of fishing. The purpose of this paper is to develop an efficient learning algorithm to detect the fishing behavior of trawlers to analyze the distribution of fishing effort. The vessel-monitoring system data of more than 4600 trawlers from September 2019 to April 2023 were used for feature extraction. According to the spatiotemporal information provided by the vessel position data, 11-dimensional features were extracted to form the feature vectors. A Slime Mould Algorithm-optimized Light Gradient-Boosting Machine (SMA-LightGBM) algorithm was proposed to classify the feature vectors to recognize fishing behavior. The presented method showed a remarkable generalization ability and high accuracy, sensitivity, specificity, and Matthews correlation coefficient in the test results, with scores of 98.23%, 98.75%, 97.75%, and 0.9646, respectively. Subsequently, the trained model was used to identify the fishing behavior of trawlers belonging to the coastal provinces of the Bohai Sea and the Yellow Sea in the sea area of 117° E~132° E, 26° N~41° N. The fishing effort was calculated and evaluated according to the fishing behavior recognition results. The mean absolute error was 0.3031 kW·h, and the coefficient of determination score was 0.9772. The thermal map of the fishing effort of the trawler was mapped, and the spatiotemporal characteristics were estimated in the region of interest from 2019 to 2023 with a spatial resolution of 18 degree × 18 degree. This method is an efficient way of analyzing the spatiotemporal characteristics of the fishing effort of trawlers. It provides a quantitative basis for the assessment of fishery resources and can inform fishing policies.

The role of arbuscular mycorrhizal fungi in the alleviation of cadmium stress in cereals: A multilevel meta-analysis - Yamin Gao; Tingting An; Qiqiang Kuang; Yujie Wu; Shuo Liu; Liyan Liang; Min Yu; Andrew Macrae; Yinglong Chen (Science of The Total Environment, 2023)

Spatially resolved transcriptomics reveals distinct pulmonary immune responses during influenza virus and SARS-CoV-2 infections - Min Zhao; Fei Shao; Zhen Liu; Jiangwen Ma; Dou Yu; Hangjie Zhang; Lianpan Dai; Kun Xu; Xin Zhao; Mengli Zheng; George Fu Gao; Shuo Wang (Science Bulletin, 2023)

Experimental study on the effects of injection pressure on the combustion in a SI aviation piston engine fueled with kerosene - Shuo Zhang; Zhenfeng Zhao; Lei Wang; Chuncun Yu; Zhenhuan Yang; Shangxue Wang (Fuel, 2023)

Influences and potential mechanisms of zein-fucoidan nanoparticles loaded with and without curcumin on casein before and after thermal treatment - Shuo Xu; Shaoxuan Yu; Zihao Zhang; Geyu Pang; Yuqing Zhang; Xinrui Wang; Haifang Xiao; Yuanda Song (Food Hydrocolloids, 2023)

Remediation of atrazine in environment by persulfate activation via N/B co-doped Si-rich biochar: Performance, mechanisms, degradation pathways and phytotoxicity - Tong Zhang; Hailing Yu; Zhaolian Han; Shuang Xu; Zhihui Dong; Kaishan Zhou; Shuo Zhang; Zhiqiang Cheng (Chemical Engineering Journal, 2023)

Enhanced nitrogen removal in the upgrading of municipal wastewater treatment plants by using zero-valent iron-modified biofilm carriers and clinoptilolite-modified biofilm carriers - Yanping Shi; Tao Liu; Xie Quan; Shuo Chen; Hongtao Yu; Wuzhe Quan (Chemical Engineering Journal, 2023)

Transcriptome sequencing identifies prognostic genes involved in gastric adenocarcinoma - Mingyue Li; Miao Bai; Yulun Wu; Shuo Yang; Lihua Zheng; Luguo Sun; Chunlei Yu; Yanxin Huang (Molecular and Cellular Biochemistry, 2023)

Transfer pattern of microplastics at an individual level: A case study of two typical Sciaenidae fish in coastal waters - Ruilin Shu; Wenbo Hu; Shike Gao; Shuo Zhang; Zheng Li; Baogui Liang; Wenwen Yu (Science of The Total Environment, 2023)

Economic analysis of global microalgae biomass energy potential - Shuo Yuan; Wenbin Lei; Yu Cen; Qi Liu; Jingping Liu; Jianqin Fu; Yubo Han (Science of The Total Environment, 2023)

VTwins: inferring causative microbial features from metagenomic data of limited samples - Qingren Meng; Qian Zhou; Shuo Shi; Jingfa Xiao; Qin Ma; Jun Yu; Jun Chen; Yu Kang (Science Bulletin, 2023)

Zircon U–Pb geochronology, Hf–O isotopes and whole-rock geochemistry of A-type granitoids in Halajun, South Tienshan, NW China: Implications for subdivision, petrogenesis and tectonic settings - Tian-Chu Chen; Ming-Xing Ling; Yu-Long Liu; Ying Wei; Xi-Hui Cheng; Xiao-Yan Jiang; Shuo Xue; Ze-Bin Luo; Jiang-Hao Bai (Lithos, 2023)

Regioselective [3 + 2] cycloaddition of diazo reagents and internal alkynes: Accessing regiosomers of highly substituted trifluoromethylpyrazoles - Shuo-Han Li; Ran Guo; Ning Lv; Yu Liu; Xiaodong Tang; Jun-An Ma (Journal of Fluorine Chemistry, 2023)

Long-term PM2.5 concentration prediction based on improved empirical mode decomposition and deep neural network combined with noise reduction auto-encoder- A case study in Beijing - Mengfan Teng; Siwei Li; Jie Yang; Shuo Wang; Chunying Fan; Yu Ding; Jiaxin Dong; Hao Lin; Shansi Wang (Journal of Cleaner Production, 2023)

Evaluation of the impact of moral dissonance-based low-carbon interventions on consumer behavior - Li Xue; Chaoran Li; Endi Cai; Wenqing Wan; Shuo Wei; Zhuo Yu; Hejun Xu (Journal of Cleaner Production, 2023)

Experimental study on enhanced coal seam gas extraction by uniform pressure/pulse pressure N2 injection - Peng-fei Ji; Hai-fei Lin; Xiang-guo Kong; Shu-gang Li; Yu-chu Cai; Rui-zhe Wang; Yu Tian; Tian-shuo Zhao (Fuel, 2023)

Serum organophosphate flame retardants and plasticizers in Chinese females of childbearing age: Association with serum reproductive and thyroid hormones - Yarui Liu; Yongcheng Li; Nan Xiao; Min Liu; Yu Wang; Haining Luo; Yiming Yao; Yujie Feng; Shuo Wang (Chemosphere, 2023)

Fusing vegetation index and ridge segmentation for robust vision based autonomous navigation of agricultural robots in vegetable farms - Shuo Wang; Daobilige Su; Yiyu Jiang; Yu Tan; Yongliang Qiao; Shenghui Yang; Yuliang Feng; Nan Hu (Computers and Electronics in Agriculture, 2023)

Mechanisms of high ammonium loading promoted phosphorus release from shallow lake sediments: A five-year large-scale experiment - Shuo-Nan Ma; Yuan-Feng Xu; Hai-Jun Wang; Hong-Zhu Wang; Yan Li; Xu-Meng Dong; Ji-Lin Xu; Qing Yu; Martin Søndergaard; Erik Jeppesen (Water Research, 2023)

Natural resources governance and geopolitical risks: A literature review and bibliometric analysis - Jiangli Yu; Shuo Wang; Wantong Yang (Resources Policy, 2023)

Multidisciplinary design optimization of dynamic positioning system for semi-submersible platform - Yongliang Yuan; Qianlong Shen; Wenhui Xi; Shuo Wang; Jianji Ren; Jiangong Yu; Qingkang Yang (Ocean Engineering, 2023)

Emission characteristics of (halogenated) polycyclic aromatic hydrocarbons during printed circuit board combustion and estimated emission intensity of a typical e-waste dismantling site in South China - Xiang Ge; Muhammad Zaffar Hashmi; Shuo Lin; Zenghua Qi; Yingxin Yu; Taicheng An (Environmental Pollution, 2023)

Local compression behavior of UHPFRC: Experiments and bearing capacity calculation model - Chuanxi Li; Haichun Li; Zheng Feng; Lu Ke; Jiale Zhou; Shuo Yu (Engineering Structures, 2023)

Inactivation of SSIIIa enhances the RS content through altering starch structure and accumulating C18:2 in japonica rice - Yufeng Zhou; Zhenfeng Cheng; Shuo Jiang; Jinxi Cen; Siyuan Yuan; Chao Yu; Shaojie Huo; Ning Zhang; Dianxing Wu; Xiaoli Shu (Carbohydrate Polymers, 2023)

Dexmedetomidine Promoted HSPB8 Expression via Inhibiting the lncRNA SNHG14/UPF1 Axis to Inhibit Apoptosis of Nerve Cells in AD - QingYun Tan; LiLi Liu; Shuo Wang; QingDong Wang; Yu Sun (Neurotoxicity Research, 2023)

Analysis of a Middle-Rank Coal Reservoir on a Triple Porosity/Dual Permeability Model - Bo Wei; Fangkai Quan; Yu Song; Shuo Feng (Natural Resources Research, 2023)

PLK3 promotes the proneural–mesenchymal transition in glioblastoma via transcriptional regulation of C5AR1 - Shuo Yu; Lin Lv; Yang Li; Qian Ning; Tingting Liu; Tinghua Hu (Molecular Biology Reports, 2023)

Hippocampal LIMK1-mediated Structural Synaptic Plasticity in Neurobehavioral Deficits Induced by a Low-dose Heavy Metal Mixture - Fankun Zhou; Lu Ouyang; Qi Li; Shuo Yang; Sisi Liu; Han Yu; Qiyue Jia; Shaoqi Rao; Jie Xie; Guihua Du; Chang Feng; Guangqin Fan (Molecular Neurobiology, 2023)

Tectonic evolution of the north Lhasa subterrane: insights from early Cretaceous marine strata in the Asuo area, central Tibet - Di Shen; Ming Wang; Chang-sheng Yu; Sheng-shuo Zhang; Trevon Tenzin (International Journal of Earth Sciences, 2023)

Anti-inflammatory, cardioprotective effect of gypenoside against isoproterenol-induced cardiac remodeling in rats via alteration of inflammation and gut microbiota - Xuemei Zhang; Ying Zhao; Xin Zhao; Ji Zhang; Jiayu Diao; Shuo Jia; Panpan Feng; Penghua Yu; Gong Cheng (Inflammopharmacology, 2023)

Occurrence and accumulation of microplastics in commercial fish in the coastal waters of the Lvsi fishing ground in China - Ruilin Shu; Zheng Li; Shike Gao; Shuo Zhang; Wenwen Yu (Marine Pollution Bulletin, 2023)

High-efficiency refractory organic pollutants removal boosted by combining heterogeneous electro-Fenton with electrochemical anodic oxidation over a broad pH range - Kaixuan Wang; Xin Qin; Peike Cao; Shuo Chen; Hongtao Yu; Xie Quan (Process Safety and Environmental Protection, 2023)

Enhanced electrochemical-activation of H2O2 to produce •OH by regulating the adsorption of H2O2 on nitrogen-doped porous carbon for organic pollutants removal - Zijun Tan; Xin Qin; Peike Cao; Shuo Chen; Hongtao Yu; Yan Su; Xie Quan (Journal of Hazardous Materials, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

Proportion of mycorrhiza-associated trees mediates community assemblages of soil fungi but not of bacteria - Hua Xing; Shuo Jiao; Xian Wu; Minhua Zhang; Shu Dong; Fangliang He; Yu Liu (Fungal Ecology, 2023)

Migration of hazardous substances during peanut oil squeezing for their dietary assessment - Bolei Yang; Xiaohua Yu; Jihao Shan; Xiaoyu Tian; Tosin Victor Adegoke; Shuo Yang; Gang Wang; Bowen Tai; Junning Ma; Qiang Yu; Fuguo Xing (Food Control, 2023)

Electro-Fenton process with scalable modified carbonaceous electrode material processed by direct calcination for refractory organic pollutant degradation - Kaixuan Wang; Peike Cao; Xin Qin; Shuo Chen; Hongtao Yu; Xie Quan (Chemical Engineering Journal, 2023)

Halide salt-tuning at interface: Highly water-stable and anion-exchange-active CsPbX3@SiO2 Trimurti nanoparticles for multicolor metabolite assay - Shuo Wang; Zhongyu Wei; Long Yu; Jinxuan Hou; Gaosong Wu; Yuxiu Xiao (Chemical Engineering Journal, 2023)

The pivotal role of MYB transcription factors in plant disease resistance - Yongbo Yu; Shuo Zhang; Yang Yu; Na Cui; Guangchao Yu; Hongyan Zhao; Xiangnan Meng; Haiyan Fan (Planta, 2023)

Correlation Analysis of Molecularly-Defined Cortical Interneuron Populations with Morpho-Electric Properties in Layer V of Mouse Neocortex - Jun-Wei Cao; Xiao-Yi Mao; Liang Zhu; Zhi-Shuo Zhou; Shao-Na Jiang; Lin-Yun Liu; Shu-Qing Zhang; Yinghui Fu; Wen-Dong Xu; Yong-Chun Yu (Neuroscience Bulletin, 2023)

First report of Trichoderma atroviride causing rot of Morchella sextelata in Anhui Province, China - Yiwen Fu; Honghui Wu; Shuo Wang; Qiang Yu; Dashuan Tian; Xi Xu (Crop Protection, 2023)

Optimal maneuver strategy for an autonomous underwater vehicle with bearing-only measurements - Xiang Li; Yan Wang; Bin Qi; Yu Hao; Shuo Li (Ocean Engineering, 2023)

High Fischer ratio oligopeptides from hard-shelled mussel: Preparation and hepatoprotective effect against acetaminophen-induced liver injury in mice - Shuo-Lei Zheng; Yue-Zheng Wang; Yu-Qin Zhao; Chang-Feng Chi; Wang-Yu Zhu; Bin Wang (Food Bioscience, 2023)

Boosting the selectivity and efficiency of nitrate reduction to ammonia with a single-atom Cu electrocatalyst - Xueyang Zhao; Qin Geng; Fan Dong; Kun Zhao; Shuo Chen; Hongtao Yu; Xie Quan (Chemical Engineering Journal, 2023)

Seasonal variation of particle hygroscopicity and its impact on cloud-condensation nucleus activation in the Beijing urban area - Sinan Zhang; Xiaojing Shen; Junying Sun; Huizheng Che; Yangmei Zhang; Quan Liu; Can Xia; Xinyao Hu; Junting Zhong; Jialing Wang; Shuo Liu; Jiayuan Lu; et al. (Atmospheric Environment, 2023)

Phase asymmetry in synoptic eddy feedbacks on the negatively-skewed winter NAO - Shuo Zhao; Hong-Li Ren; Fang Zhou; Adam A. Scaife; Yu Nie (Atmospheric Research, 2023)

Plant above-ground biomass and litter quality drive soil microbial metabolic limitations during vegetation restoration of subtropical forests - Shuo Zhang; Ying-Ping Wang; Xi Fang; Jinlei Chen; Nannan Cao; Pingping Xu; Mengxiao Yu; Xin Xiong; Xiangping Tan; Qi Deng; Junhua Yan (Soil Ecology Letters, 2023)

Liposomal Nanodrug Based on Norcantharidin Derivative for Increased in Vivo Activity - Hailong Kuang; Peipei Wang; Yuhang Wang; Jinbo Li; Jiang Yu; Lirui Jia; Shuo Li; Yan Ma; Hongzhuo Liu; Zhonggui He; Yongjun Wang (AAPS PharmSciTech, 2023)

Simultaneous carbon dioxide sequestration and nitrate removal by Chlorella vulgaris and Pseudomonas sp. consortium - Qian Yu; Manshuang Yin; Yanrui Chen; Shiqi Liu; Shuo Wang; Yuying Li; Hongli Cui; Daoyong Yu; Baosheng Ge; Fang Huang (Journal of Environmental Management, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

Blood Lead Level Is Associated with Visceral Adipose Dysfunction in Patients with Type 2 Diabetes - Chi Chen; Bin Wang; Haojie Zhang; Yuying Wang; Shiyan Yu; Shuo Zhou; Yi Chen; Fangzhen Xia; Hualing Zhai; Ningjian Wang; Yingli Lu (Biological Trace Element Research, 2023)

The climate‐driven distribution and response to global change of soil‐borne pathogens in agroecosystems - Ziheng Peng; Yu Liu; Jiejun Qi; Hang Gao; Xiaomeng Li; Qi Tian; Xun Qian; Gehong Wei; Shuo Jiao (Global Ecology and Biogeography, 2023)
Aim Soil‐borne pathogens severely affect crop production, but the present distribution of agricultural soil‐borne pathogens and their response to global changes are unexplored at large spatial scales. Here, we examine the nationwide‐scale distribution patterns, dominant taxa and environmental drivers of fungal soil‐borne pathogens, and their response to warming, nutrient enrichment and their interaction. Location China. Time period July and August 2019. Major taxa studied Fungal plant pathogens. Methods Through nationwide field surveys of 711 top‐ and subsoil samples in 51 cropland locations, we investigated the distribution patterns, environmental drivers and dominant taxa of fungal plant pathogens. We then conducted a mesocosm experiment with soils collected at 40 survey locations to evaluate the response patterns of fungal pathogens to global changes, including warming, nutrient enrichment and their interaction. Results We observed that the abundance and richness of potential soil‐borne pathogens were higher in the topsoil than in the subsoil. Mean annual temperature and mean annual precipitation as the main drivers had a stronger effect on the abundance, richness and community of pathogens in the topsoil than subsoil. Two phylotypes, belonging to genus Fusarium , were the dominant soil‐borne pathogens accounting for approximately one third of total abundance, and their abundances (e.g. relative and absolute abundance via quantitative polymerase chain reaction) were negatively correlated with precipitation and temperature. The mesocosm experiment simulating global changes further revealed that the abundance and richness distributions of soil pathogens predicted the direction of their response to global changes, with a positive response in pathogen‐poor soil and negative in pathogen‐rich soil. We further constructed spatial atlases of the dominant soil‐borne pathogens and their responses to global changes in agricultural fields. Main conclusions Our findings suggest that the current distribution of potential soil‐borne pathogens is regulated by climate, which could affect their future dynamics and is vital to agricultural practices for pathogen control and crop production.

Ecological compensation in the Beijing-Tianjin-Hebei region based on ecosystem services flow - Heqiu Du; Li Zhao; Pengtao Zhang; Jinxiao Li; Shuo Yu (Journal of Environmental Management, 2023)

Improving the performance of nanogenerators via micro-capacitors and enhanced dipoles - Binbin Zhao; Lulu Lei; Yanfang Zhu; Zefei Cheng; Yansong Liu; Shuo Wang; Mingjia Liu; Tao Yu; Weidong Yang; Yan Li (Chemical Engineering Journal, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Adventitious roots of Hypericum perforatum are potential material for inhibiting foodborne bacteria - Wei-Qi Ye; Hao-Ding Sun; Miao Wang; Liang-Liang Liu; Shuo Yu; Mei-Yu Jin; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

A Storage-Saving Quadtree-Based Multibeam Bathymetry Map Representation Method - Zheng Cong; Teng Ma; Ye Li; Mingxiao Yuan; Yu Ling; Haohan Du; Chi Qi; Ziyuan Li; Shuo Xu; Qiang Zhang (Journal of Marine Science and Engineering, 2023)
With the rapid advancement of the simultaneous localization and mapping (SLAM) technology, the collaboration of several autonomous underwater vehicles (AUVs) in large-scale seafloor imaging has become a trending topic. Electromagnetic waves are difficult to transfer underwater, the only viable method of communication is acoustic transmission, but its bandwidth is limited. Therefore, how to compress and process multibeam bathymetry maps so that AUVs can acquire maps gathered by other AUVs has become an important topic of study. This study presents a representation approach for multibeam bathymetry maps based on a quadtree structure. In comparison to the girding approach, the sparse pseudo-input Gaussian processes (SPGPs) method, and the octree-based method, the quadtree-based method suggested in this study preserves precision while compressing storage space. Experiments utilizing field data validate the performance of the proposed technique, and the method’s ability to compress storage space towards an AUV cooperative SLAM’s scenario.

Long Acting Ionically Paired Pamoate-based Suspension of Lurasidone: An exploration of Size Effects on in vitro Dissolution and in vivo Pharmacokinetic Behaviors - Shuo Li; Ying He; Dianjun Sun; Zhaomeng Wang; Jiang Yu; Jianying Ye; Zhonggui He; Yongjun Wang (AAPS PharmSciTech, 2023)

Determining effect of seagrass-mediated CO2 flux on the atmospheric cooling potential of a subtropical intertidal seagrass meadow - Pengxiang Zheng; Guangcheng Chen; Wenlu Lan; Shiman Li; Mingmin Li; Shunyang Chen; Wenshuo An; Jiahui Chen; Shuo Yu; Bin Chen (Marine Pollution Bulletin, 2023)

Enhanced PMS activation by surface electronic reconstruction at Co3O4/ZnO heterointerface: Performance and mechanism - Hang Zhang; Shuo Chen; Liyu Ran; Hongtao Yu (Process Safety and Environmental Protection, 2023)

Highly efficient electro-Fenton process on hollow porous carbon spheres enabled by enhanced H2O2 production and Fe2+ regeneration - Xin Qin; Kaixuan Wang; Peike Cao; Yan Su; Shuo Chen; Hongtao Yu; Xie Quan (Journal of Hazardous Materials, 2023)

Rapid synthesis of hierarchical silicoaluminophosphate molecular sieves using carbon-silicon composites from rice husk ash for deoxygenation of stearic acids - Yingying Fu; Delin Guo; Wenlong Jiang; Shuo Tao; Xiaosheng Wang; Shitao Yu; Zhanqian Song; Yuxiang Liu (Fuel, 2023)

The effect of lactulose thermal degradation products on β-lactoglobulin: Linear-, loop-, and cross-link structural modifications and reduced digestibility - Lu Dong; Zhenting Yu; Runmin Zhao; Bo Peng; Yan Zhang; Shuo Wang (Food Chemistry, 2023)

Modeling collective motion for fish schooling via multi-agent reinforcement learning - Xin Wang; Shuo Liu; Yifan Yu; Shengzhi Yue; Ying Liu; Fumin Zhang; Yuanshan Lin (Ecological Modelling, 2023)

Constraints on the spatial variations of soil carbon fractions in a mangrove forest in Southeast China - Shuo Yin; Junjian Wang; Tianfang Yu; Mingqi Wang; Yixuan Wu; Hui Zeng (CATENA, 2023)

High density mapping of wheat stripe rust resistance gene QYrXN3517-1BL using QTL mapping, BSE-Seq and candidate gene analysis - Shuo Huang; Yibo Zhang; Hui Ren; Xin Zhang; Rui Yu; Shengjie Liu; Qingdong Zeng; Qilin Wang; Fengping Yuan; Ravi P. Singh; Sridhar Bhavani; Jianhui Wu; et al. (Theoretical and Applied Genetics, 2023)

MPC-Based Collaborative Control of Sail and Rudder for Unmanned Sailboat - Shuo Liu; Zijing Yu; Tao Wang; Yifan Chen; Yu Zhang; Yong Cai (Journal of Marine Science and Engineering, 2023)
In the traditional motion control method of an unmanned sailboat, the sail and rudder are divided into two independent controllers. The sail is used to obtain the thrust and the rudder is used to adjust the yaw angle. The traditional control method does not consider the synergy between the two controllers and ignores the influence of the roll angle on sailing. It is easy for these methods to cause an excessive roll angle and large yaw angle error, which will weaken the safe navigation and accurate path tracking of an unmanned sailboat. This paper presents a collaborative control method of sail and rudder based on model predictive control. A four-degree-of-freedom kinematics and dynamics model of the unmanned sailboat considering roll angle was established, with the yaw angle and roll angle as the control objectives at the same time. The collaborative control method outputs sail angle and rudder angle simultaneously. By comparing the motion of this method and the separation control of sail and rudder under the same wind field conditions, it is verified that the collaborative control has better effects of yaw angle control and roll angle limitation and can obtain a more accurate path tracking effect.

Experimental and numerical study on flame fusion behavior of premixed hydrogen/methane explosion with two-channel obstacles - Shuo Wang; Guoqing Xiao; Hongfu Mi; Yu Feng; Jian Chen (Fuel, 2023)

Probing the stability of perovskite solar cell under working condition through an ultra-thin silver electrode: Beyond the halide ion diffusion and metal diffusion - Hao Li; Zheng Yan; Min Li; Xiaoyan Wen; Shuo Deng; Sisi Liu; Wallace C.H. Choy; Lijie Li; Ming-Yu Li; Haifei Lu (Chemical Engineering Journal, 2023)

Engineering electron redistribution of bimetallic phosphates with CeO2 enables high-performance overall water splitting - Xin Guo; Menggang Li; Longyu Qiu; Fenyang Tian; Lin He; Shuo Geng; Yequn Liu; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2023)

The construction of high efficient visible-light-driven 3D porous g-C3N4/Fe3O4 photocatalyst: A new photo-induced bacterial inactivation material enhanced by cascade photo-Fenton reaction - Ze-Yu Liu; Wen-Qian Huang; Chuan-Qing Huang; Zhao-Zhen Liu; Xiao-Yue Tang; Wei-Chang Chen; Zheng-Zheng Tang; Yu-Xing Huang; Shuo-Chun Zheng; Lin Lin; Changzhu Li; Yong Ye (Chemosphere, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Study on energy management model of integrated New Energy-Storage-Charging system considering the influence of uncertainties - Huanan Liu; Jing Jiang; Shuo Zhan; Xiuyu Yang; Dongmin Yu; Gangui Yan (Fuel, 2023)

Development of a recombinant adenovirus-vectored vaccine against both infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus in rainbow trout (Oncorhynchus mykiss) - Shouhu Li; Xincang Li; Rui Yuan; Xiaoxue Chen; Shouxu Chen; Yu Qiu; Qingfeng Yang; Meng Wang; Jiangao Shi; Shuo Zhang (Fish & Shellfish Immunology, 2023)

Ultrafast Self-propelling directionally water transporting wood via cell wall reshaping for water manipulation - Zhe Qiu; Fanjun Yu; Dan Xu; Zengbin Wang; Junya Huang; Shuo Wang; Yanxiao Yang; Yonggui Wang; Jian Li; Zefang Xiao; Yanjun Xie; Kai Zhang (Chemical Engineering Journal, 2023)

Construction of microchannel charcoal cathodes with spatial-constraint capability for enhancing reduction of NO3− in high-salinity water - Yueyao Wu; Yuwei Gu; Wenda Kang; Hongtao Yu; Shuo Chen; Xie Quan; Na Lu (Chemical Engineering Journal, 2023)

The involvement of AtMKK1 and AtMKK3 in plant-deleterious microbial volatile compounds-induced defense responses - Ching-Han Chang; Wu-Guei Wang; Pei-Yu Su; Yu-Shuo Chen; Tri-Phuong Nguyen; Jian Xu; Masaru Ohme-Takagi; Tetsuro Mimura; Ping-Fu Hou; Hao-Jen Huang (Plant Molecular Biology, 2023)

Long-term effects of cattle manure application on the soil aggregate stability of salt-affected soil on the Songnen Plain of North-Eastern China - Shuo Zhao; Fei Yu; Cheyu Zhai; Rui Zhong; Ying Zhao; Yong Wang; Juan Zhang; Qingfeng Meng (Journal of Soils and Sediments, 2023)

Green algae monitoring via ground-based GNSS-R observations - Wei Ban; Nanshan Zheng; Kefei Zhang; Kegen Yu; Shuo Chen; Qi Lu (GPS Solutions, 2023)
Outbreaks of harmful algal blooms (HABs) exhibit high frequency, large range and damage aggravation characteristics, but existing monitoring methods, such as artificial and optical near-infrared remote sensing, cannot accommodate these characteristics. We propose a new method for monitoring green algae using Global Navigation Satellite System Reflectometry (GNSS-R) observations. The basic principle states that changes in the seawater dielectric constant and sea surface roughness due to the emergence of green algae lead to an increase in brightness temperature, which can be inverted based on the reflection time delay waveform. Shipboard reflection waveform data collected during an Enteromorpha prolifera outbreak in the Qingdao sea area were used for model development and validation of the detection and estimation performance. The results indicated that the root mean square error of GNSS-R-based inversion of the green algae density was 6.74%, indicating the potential of GNSS-R technology for rapid preliminary monitoring of green algae. Moreover, the advantages of a low cost, short return time and no climatic limitations support GNSS-R technology as a new and efficient means of green algae monitoring.

Associations between residential proximity to agricultural land use as pesticides exposure and birth outcomes - Kuna-Chun Chen; Shuo-Fang Lee; Shyang-Woei Lin; Jia-Shan Xie; Yu‐Hsun Chang; Lih-Ming Yiin; Chia-Jung Hsieh (Environmental Science and Pollution Research, 2022)

Seed bank dynamics and quality in the seagrass Halophila ovalis along estuarine salinity gradients—a case in the Swan-Canning Estuary - Ruiting Gu; John Statton; Susi Rahmawati; Renae Hovey; Yi Zhou; Jianwu Tang; Shuo Yu; Gary A. Kendrick (Frontiers in Marine Science, 2022)
The seed bank of Halophila ovalis is crucial for resilience to disturbance through re-establishment. Understanding seasonal changes in abundance and quality of seeds in natural seed banks is critical for seed-based restoration. We selected an estuary in southwestern Australia and investigated the seasonal changes of seed distribution and viability in H. ovalis seed banks. We also adapted an X-ray viability test used for terrestrial seeds to test the viability of H. ovalis seeds. We then simulated the effect of low salinity on seed viability through a short-term indoor experiment. Seed density was significantly different between sites and seasons (0 to 43590 seeds·m -2 ), and the highest seed density in the seed banks was found after the reproductive season (May). The proportion of viable seeds in the seed bank was less than 22%, and was not subjected to substantial seasonal variability. The density of seeds in the seed bank decreased in spring, which indicated winter conditions were not prompt seed loss. We also predicted that extreme rainfall events and the resulting extremely low salinity would significantly reduce seed viability, and could decrease in seed germination; limit population recruitment. As it rapidly colonizes marine sediments from seeds, H. ovalis was considered an ideal seagrass for restoration purposes. Our results provide physiological information for H. ovalis seed banks to support seed-based restoration plans. Such understanding would enable accurate predictions about seagrass population resilience to extreme climate events in estuaries, where variable and extremely low salinity may limit seagrass population recovery from seeds through decreasing their viability.

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

Core phylotypes enhance the resistance of soil microbiome to environmental changes to maintain multifunctionality in agricultural ecosystems - Shuo Jiao; Jiejun Qi; Chujie Jin; Yu Liu; Yang Wang; Haibo Pan; Shi Chen; Chunling Liang; Ziheng Peng; Beibei Chen; Xun Qian; Gehong Wei (Global Change Biology, 2022)
Agricultural ecosystems are facing increasing environmental changes. Revealing ecological stability of belowground organisms is key to developing management strategies that maintain agricultural ecosystem services in a changing world. Here, we collected soils from adjacent pairs of maize and rice fields along large spatial scale across Eastern and Southeast China to investigate the importance of core microbiota as a predictor of resistance of soil microbiome (e.g. bacteria, fungi and protist) to climate changes and nutrient fertilization, and their effect on multiple ecosystem functions, representing key services for crop growth and health in agro‐ecosystems. Soil microbiome in maize soils exhibited stronger resistance than that in rice soils, by considering multiple aspects of the resistance index, for example, community, phylogenetic conservation and network complexity. Community resistance of soil microbiome showed a geographic pattern, with higher resistance at lower latitudes, suggesting their stronger resistance in warmer regions. Particularly, we highlighted the role of core phylotypes in enhancing the community resistance of soil microbiome, which was essential for the maintenance of multifunctionality in agricultural ecosystems. Our results represent a significant advance in linking core phylotypes to community resistance and ecosystem functions, and therefore forecasting agro‐ecosystems dynamics in response to ongoing environmental changes. These suggest that core phylotypes should be considered a key factor in enhancing agricultural sustainability and crop productivity under global change scenarios.

Variation in the attached community structure and function of artificial habitats during ecological succession: A case study of the artificial reef area in Bailong Pearl Bay, China - Ruolin Li; Yu Guo; Ankai Zhang; Shuo Zhang; Hui Zhang; Chuanxin Qin (Frontiers in Marine Science, 2022)
With the continuous development of ports, ship transportation, resource extraction and artificial habitat deployment, an increasing number of artificial structures have created new usable spaces for marine organisms, and the biological communities living on their surfaces have undergone ecological succession. However, related studies have ignored ecological functions, interspecific relationships, and stability in different successional stages. Based on traditional taxonomy, this study applied functional diversity, niche overlap and niche breadth indexes to compare the attached organisms on artificial reefs (ARs) with different construction times in Bailong Pearl Bay, Fangchenggang City, Guangxi Zhuang Autonomous Region, China. The change trends of richness, habitat resource supply, resource utilization degree and efficiency, and interspecific relationships during the succession process were analysed. The results indicated that richness increased with functional diversity. While the number of species increased, the attached organisms showed different functional characteristics, and the number of species with identical traits decreased. The attached community in the later stage of development had a higher degree of utilization of ecological space, more comprehensive and efficient utilization of effective resources, a stronger degree of complementarity of organismal niches, and weaker interspecific competition. In the early stage of the developmental process, the attached community was affected by more environmental factors and had very significant correlations with those factors. The combination of the niche overlap index and the niche breadth index indicated that the resource supply supporting the survival and development of the attached organisms on the ARs with earlier construction times may be greater. The decrease in the number of biomarkers, the similarity of biomarkers belonging to the same family, and the similarity of dominance alternation all indicated that during the process of long-term development and community succession, the organisms attached to the various parts of the ARs tended to become more similar.

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

Catalytic Hydrothermal Liquefaction of Algae for Production of Bio-oil with Solid Superacid Catalyst SO42−/ZrO2 - Mengfan Liu; Xin Yu; Xiaofan Yu; Yongnian Zhao; Lijuan Feng; Xianguo Li; Shuo Yao (Journal of Ocean University of China, 2022)

Degradation characteristics of crude oil by a consortium of bacteria in the existence of chlorophenol - Jing Li; Qiyou Liu; Shuo Sun; Xiuxia Zhang; Xiuying Zhao; Junlong Yu; Wu Cui; Yi Du (Biodegradation, 2022)

LncRNA GATA3-AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR-361/ARRB2 axis - Yu-xi Liu; Shuo Yuan; Xiao-jing Liu; Yan-xi Huang; Pin Qiu; Jie Gao; Gao-pi Deng (Journal of Molecular Medicine, 2022)

Finite Element Analysis of the Biomechanical Effect of Bone Resection Depth in the Distal Tibia after Total Ankle Replacement - Jian Yu; Dahang Zhao; Shuo Wang; Pengfei Chu; Chao Zhang; Jiazhang Huang; Xu Wang; Xin Ma (Journal of Medical and Biological Engineering, 2022)

Allergy from perspective of environmental pollution effects: from an aspect of atopic dermatitis, immune system, and atmospheric hazards—a narrative review of current evidences - Su Boon Yong; Shuo-Yan Gau; Yu-Chen Guo; James Cheng-Chung Wei (Environmental Science and Pollution Research, 2022)

Rhodohalobacter sulfatireducens sp. nov., isolated from a marine solar saltern - Yu-Sheng Wang; Yu-Yan Yue; Yi-Lin Bai; Xu-Yang Zhang; Shuo Wang; Zong-Jun Du (Archives of Microbiology, 2022)

Isolation, identification, molecular docking analysis, and cytoprotection of seven novel angiotensin I-converting enzyme inhibitory peptides from miiuy croaker byproducts-swim bladders - Wang-Yu Zhu; Yu-Mei Wang; Shi-Kun Suo; Shuo-Lei Zheng; Bin Wang (Frontiers in Marine Science, 2022)
For efficiently utilizing the processing byproducts of miiuy croaker to prepare novel angiotensin I-converting enzyme (ACE) inhibitory (ACEi) peptides, in vitro gastrointestinal (GI) digestion method was screened and employed to prepare swim bladder hydrolysate with the highest ACEi activity. Subsequently, seven novel ACEi peptides were isolated from the hydrolysate and identified as DEGPE, EVGIQ, SHGEY, GPWGPA, GPFGTD, SPYGF, and VIGPF with molecular weights of 545.49, 544.58, 591.55, 583.63, 592.59, 569.60, and 531.63 Da, respectively. SHGEY and SPYGF exhibited remarkable ACEi activity with IC 50 values of 0.86 ± 0.12 and 0.37 ± 0.06 mg/mL. Molecular docking experiment illustrated that the significant ACEi activity of SHGEY and SPYGF with the affinity of -8.7 and -9.7 kcal/mol mainly attributed to effectively combining with the ACEi active sites by hydrophobic interaction, electrostatic force and hydrogen bonding. Moreover, SHGEY and SPYGF could significantly up-regulate the nitric oxide (NO) production and decrease the endothelin-1 (ET-1) secretion in human umbilical vein endothelial cells (HUVECs), but also abolished the negative impacting of norepinephrine to the levels of NO and ET-1. Furthermore, SHGEY and SPYGF showed significant protection to HUVECs against H 2 O 2 damage by increasing superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) activity to lower the contents of reactive oxide species and malondialdehyde. Consequently, ACEi peptides derived from miiuy croaker swim bladders, especially SHGEY and SPYGF, are health-promoting ingredients for functional products as a supplementary treatment to hypertension and cardiovascular diseases.

Pelagic cyanobacterial nitrogen fixation in lakes and ponds of different latitudinal zones - Yan Li; Ye-Xin Yu; Shuo-Nan Ma; Rui-Ting Qiao; Yong-De Cui; Hai-Jun Wang; Hong-Zhu Wang (Aquatic Sciences, 2022)

Correction to: Sox10 Gene Is Required for the Survival of Saccular and Utricular Hair Cells in a Porcine Model - Jing-cui Qi; Qing-qing Jiang; Long Ma; Shuo-long Yuan; Wei Sun; Li-sheng Yu; Wei-wei Guo; Shi-ming Yang (Molecular Neurobiology, 2022)

Sox10 Gene Is Required for the Survival of Saccular and Utricular Hair Cells in a Porcine Model - Jing-cui Qi; Qing-qing Jiang; Long Ma; Shuo-long Yuan; Wei Sun; Li-sheng Yu; Wei-wei Guo; Shi-ming Yang (Molecular Neurobiology, 2022)

Intelligent identification method and application of seismic faults based on a balanced classification network - Jing Yang; Ren-Wei Ding; Hui-Yong Wang; Nian-Tian Lin; Li-Hong Zhao; Shuo Zhao; Yu-Jie Zhang (Applied Geophysics, 2022)

Comparative effects of cannabinoid CB1 receptor agonist and antagonist on timing impulsivity induced by d-amphetamine in a differential reinforcement of low-rate response task in male rats - Shuo-Fu Chen; Wei-Chung Hsu; Xi-Yun Lu; Chuen-Yu Chuang; Ruey-Ming Liao (Psychopharmacology, 2022)

Spinocerebellar Ataxia Type 10 with Atypical Clinical Manifestation in Han Chinese - Chengyuan Mao; Xinwei Li; Yun Su; Haiyang Luo; Liyuan Fan; Huimin Zheng; Yu Fan; Zhihua Yang; Shuo Zhang; Zhengwei Hu; Xiaoyan Hao; Changhe Shi; et al. (The Cerebellum, 2022)

Ocean Currents May Influence the Endolithic Bacterial Composition in Coral Skeletons - Po-Yu Liu; Sung-Yin Yang; Chih-Ying Lu; Naohisa Wada; Stéphane De Palmas; Shu-Shuo Yeh; Hideyuki Yamashiro; Sen-Lin Tang; Shan-Hua Yang (Frontiers in Marine Science, 2022)
Coral endolithic microbes can be an important nutrients support for hosts while under stresses. Previous studies have found that the endolithic microbial composition of a single coral species can be biogeographical diverse. However, the potential environmental factors, such as salinity, temperature, pH, and nutrient, that might influence the composition of the endolithic microbes remain unclear. In this study, we used both amplicon sequence variants (ASV) and a kmer-based taxonomic unit (KTU) to characterize the endolithic bacterial constitution of Isopora spp. located in the western Pacific Ocean—where it is subjected to the Kuroshio Current (in Okinawa, Japan and Green Island, Taiwan)—and the South China Sea (Dongsha Atoll). The endolithic bacterial community compositions showed a significant geographical difference, and we suggest that the ocean current and primary productivity are the most essential environmental factors influencing the bacterial communities in the skeleton of Isopora spp. In addition, our results showed that, technically, compared to ASV, bacterial composition based on KTU avoids extreme data, making it a suitable tool for explaining the associations between microbes and environmental factors.

Inherent conflicts between reaction norm slope and plasticity indices when comparing plasticity: a conceptual framework and empirical test - Shuo Wang; Wei-Wei Feng; Ming-Chao Liu; Kai Huang; Pieter A. Arnold; Adrienne B. Nicotra; Yu-Long Feng (Oecologia, 2022)

Migration and abiotic transformation of estrone (E1) and estrone-3-sulfate (E1-3S) during soil column transport - Banghao Du; Weiwei Yu; Lun Yang; Gongduan Fan; Shuo Yang; Hui Jiang; Shenglan Bi; Cheng Yu (Environmental Geochemistry and Health, 2022)

Three-dimensional forward modeling and response characteristics analysis of foundation pit leakage electric-field considering electrokinetic effect - Chen Yu-Feng; Chen Hui; Deng Ju-Zhi; Liu Sui-Ming; Tang Wen-Wu; Wang Shuo (Applied Geophysics, 2022)

Study of the characteristics of intestinal bacteria of little yellow croaker ( Larimichthys polyactis ) and big head croaker ( Collichthys lucidus ) from the Lyusi fishing ground - Shixuan Chen; Hao Xu; Shuo Zhang; Wenwen Yu (Marine Biology Research, 2022)

Smart traceability for food safety - Zhilong Yu; Dongyun Jung; Soyoun Park; Yaxi Hu; Kang Huang; Barbara A. Rasco; Shuo Wang; Jennifer Ronholm; Xiaonan Lu; Juhong Chen (Critical Reviews in Food Science and Nutrition, 2022)

A simple and robust method for calculating temperatures of granitoid magmas - Meng Duan; Yaoling Niu; Pu Sun; Shuo Chen; Juanjuan Kong; Jiyong Li; Yu Zhang; Yan Hu; Fengli Shao (Mineralogy and Petrology, 2022)
Calculating the temperatures of magmas from which granitoid rocks solidify is a key task of studying their petrogenesis, but few geothermometers are satisfactory. Zircon saturation thermometry has been the most widely used because it is conceptually simple and practically convenient, and because it is based on experimental calibrations with significant correlation of the calculated zircon saturation temperature ( T Zr ) with zirconium (Zr) content in the granitic melt (i.e., T Zr ∝ Zr MELT ). However, application of this thermometry to natural rocks can be misleading, resulting in the calculated T Zr having no geological significance. This thermometry requires Zr content and a compound bulk compositional parameter M of the melt as input variables. As the Zr and M information of the melt is not available, petrologists simply use bulk-rock Zr content (Zr BULK-ROCK ) and M to calculate T Zr . In the experimental calibration, T Zr shows no correlation with M , thus the calculated T Zr is only a function of Zr MELT . Because granitoid rocks represent cumulates or mixtures of melt with crystals before magma solidification and because significant amount Zr in the bulk-rock sample reside in zircon crystals of varying origin (liquidus, captured or inherited crystals) with unknown modal abundance, Zr BULK-ROCK cannot be equated with Zr MELT that is unknown. Hence, the calculated magma temperatures T Zr using Zr BULK-ROCK have no significance in both theory and practice. As an alternative, we propose to use the empirical equation $$T_{SiO_{2}}$$ T S i O 2 (°C) = -14.16 × SiO 2 + 1723 for granitoid studies, not to rely on exact values for individual samples but focus on the similarities and differences between samples and sample suites for comparison. This simple and robust thermometry is based on experimentally determined phase equilibria with T ∝ 1/SiO 2 .

New Insight Into the Mechanism of Ecological Effects of Artificial Habitats: Elucidating the Relationship Between Protists Associated With Artificial Reefs and Adjacent Seawater - Ruolin Li; Yu Guo; Chuanxin Qin; Shuo Zhang; Dongping Ji; Hui Zhang; Jing Wang; Naiqian Zhao (Frontiers in Marine Science, 2022)
Artificial habitat deployment can restore natural habitats or supplement existing natural habitats. The effect of resource proliferation and protection is obvious. However, few reports have addressed the biological community association between artificial habitats and adjacent environments. Here, Illumina sequencing of 18S rDNA was performed, and the diversity, community structure, and co-occurrence networks of protists in different layers of artificial reefs (ARs) and adjacent seawater (WAR) were described to verify that constructing ARs in Bailong Pearl Bay improves local spatial heterogeneity and functional diversity. In terms of the degree of species interaction, the protist communities were ranked as follows: surface and bottom of WAR > ARs and WAR > different layers of ARs. The α-diversity of protists associated with ARs and WAR decreased with an increase in depth. Protist diversity was greater in WAR than in ARs. β-Diversity analysis revealed significant differences in protist community structure between WAR and ARs ( P < 0.05), and the upper layers of ARs and the middle or bottom layers of ARs differed. The key topological features of protist networks showed more positive interspecific interactions in the AR-associated protist community, a higher degree of niche differentiation, and higher complexity and stability. The keystone protists in the bottom seawater layer displayed community functions that were biased toward initial fixation in the ocean carbon cycle. The AR-associated protist community tended to participate in carbon transfer in the food chain and decomposition and utilization of dissolved organic matter (DOM). This study revealed significant differences in protist community structure between ARs and the adjacent environment, and the ecological functions of the key phyla were found to be related. In conclusion, protist communities in WAR may provide food sources for AR-associated heterotrophic protists. A variety of key phyla associated with ARs have biological roles in the carbon pump via their ecological characteristics.

Enhanced stripe rust resistance obtained by combining Yr30 with a widely dispersed, consistent QTL on chromosome arm 4BL - Shengjie Liu; Xiaoting Wang; Yayun Zhang; Yangang Jin; Zhonghua Xia; Mingjie Xiang; Shuo Huang; Linyi Qiao; Weijun Zheng; Qingdong Zeng; Qilin Wang; Rui Yu; et al. (Theoretical and Applied Genetics, 2022)

Soil phosphorus determines the distinct assembly strategies for abundant and rare bacterial communities during successional reforestation - Ziheng Peng; Zhifeng Wang; Yu Liu; Tongyao Yang; Weimin Chen; Gehong Wei; Shuo Jiao (Soil Ecology Letters, 2021)

The co-expression of genes involved in seed coat and endosperm development promotes seed abortion in grapevine - Shasha Li; Xiangyu Geng; Shuo Chen; Keke Liu; Saisai Yu; Xiping Wang; Chaohong Zhang; Jianxia Zhang; Yingqiang Wen; Qiangwei Luo; Yan Xu; Yuejin Wang (Planta, 2021)

The Beneficial Role of Exercise on Treating Alzheimer’s Disease by Inhibiting β-Amyloid Peptide - Zi-Xuan Tan; Fang Dong; Lin-Yu Wu; Ya-Shuo Feng; Feng Zhang (Molecular Neurobiology, 2021)

Assessing vegetation community distribution characteristics and succession stages in mountainous areas hosting coming Winter Olympics Games - Heng-shuo Zhang; Tong-gang Zha; Yang Yu; Xiao-dong Ji; Rodrigo-Comino Jesús (Journal of Mountain Science, 2021)

Description of Lujinxingia vulgaris sp. nov., isolated from coastal sediment via prey-traps - Shuo Wang; Da-Shuai Mu; Guang-Yu Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2021)

Identification and characterization of Trpm4 gene involved in regulating Japanese flounder ( Paralichthys olivaceus ) inflammatory response - Shuo Li; Yu Feng; Tongtong Zhang; Shan Wang; Jinsheng Sun (Journal of Fish Diseases, 2021)
The transient receptor potential (TRP) melastatin 4 (TRPM4) is a widely expressed Ca 2+ ‐impermeable cation channel involved in modulating inflammatory and immune responses in mammals. However, the role of TRPM4 channel in fish immunity remains unclear. In this report, from a comparative immunological point of view, we identified and characterized a Trpm4 gene from Japanese flounder ( Paralichthys olivaceus ) and analysed its potential role in regulating the fish inflammatory response. The Japanese flounder Trpm4 gene is expressed in a wide range of tissues and encodes a 1264‐amino acid protein which expresses on the cell surface and shares several conserved domains with its mammalian counterparts. In vitro inflammatory challenge and in vivo bacterial infection experiments revealed that Japanese flounder Trpm4 expression was significantly modulated following different immune challenges, indicating the implication of Trpm4 in the fish immune response. Overexpression of TRPM4 significantly attenuated LPS‐ and poly(I:C)‐induced pro‐inflammatory cytokine expression in Japanese flounder FG‐9307 cells. In contrast, pharmacological inhibition of the endogenous TRPM4 channel activity in Japanese flounder head kidney macrophages resulted in increased pro‐inflammatory cytokine expression following LPS and poly(I:C) stimulations. Taken together, these findings indicate that TRPM4 channels may play a conserved role in regulating inflammatory response(s) in fish.

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Development of a dual-labeled, hydrolysis probe-based, real-time quantitative PCR assay for detection of both genotypes of duck circovirus-1 (DuCV-1) and DuCV-2 - Lin Zhang; Wenming Jiang; Fuyou Zhang; Yang Li; Jinping Li; Shaobo Liang; Xiaohui Yu; Cheng Peng; Shuo Liu; Jingjing Wang; Shuhong Sun; Hualei Liu (Virus Genes, 2021)

Refined mapping of stripe rust resistance gene YrP10090 within a desirable haplotype for wheat improvement on chromosome 6A - Shengjie Liu; Shuo Huang; Qingdong Zeng; Xiaoting Wang; Rui Yu; Qilin Wang; Ravi P. Singh; Sridhar Bhavani; Zhensheng Kang; Jianhui Wu; Dejun Han (Theoretical and Applied Genetics, 2021)

Bisphenol A induces ovarian cancer cell proliferation and metastasis through estrogen receptor-α pathways - Chen Sang; Yu Song; Tong-wang Jin; Shuo Zhang; Linyan Fu; Yi Zhao; Xinxin Zou; Zhe Wang; Hui Gao; Sijin Liu (Environmental Science and Pollution Research, 2021)

A cloud classification method based on random forest for FY-4A - Zhuofu Yu; Shuo Ma; Ding Han; Guanlin Li; Ding Gao; Wei Yan (International Journal of Remote Sensing, 2021)

Fast and reversible adsorption for dibenzothiophene in fuel oils with metallic nano-copper supported on mesoporous silica - Xinsheng Li; Shuo Ai; Yongchun Huang; Chengdu Huang; Wanguo Yu; Zhijuan Mao (Environmental Science and Pollution Research, 2021)

Lead ion adsorption on functionalized sugarcane bagasse prepared by concerted oxidation and deprotonation - Shuo Ai; Yongchun Huang; Chengdu Huang; Wanguo Yu; Zhijuan Mao (Environmental Science and Pollution Research, 2021)

The process of embryo abortion of stenospermocarpic grape and it develops into plantlet in vitro using embryo rescue - Shasha Li; Keke Liu; Saisai Yu; Shanshan Jia; Shuo Chen; Yuheng Fu; Feng Sun; Qiangwei Luo; Yuejin Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Quantitative Angiographic Hemodynamic Evaluation After Revascularization Surgery for Moyamoya Disease - Yu Chen; Li Ma; Shuo Yang; Jan-Karl Burkhardt; Junlin Lu; Xun Ye; Weijian Jiang; Zeguang Ren; Rong Wang; Xiaolin Chen; Yuanli Zhao (Translational Stroke Research, 2020)
The corresponding hemodynamic changes of the internal carotid artery (ICA) after the revascularization surgery for moyamoya disease (MMD) remain unclear. The aim of this study was to analyze the hemodynamic changes of the ipsilateral ICA after the combined direct and indirect extracranial-intracranial (EC-IC) bypass. MMD patients undergoing combined EC-IC bypass were retrospectively reviewed. The mean transit time (MTT) of ICA was evaluated by color-coding angiography before revascularization and at follow-up. The MTT defined as the blood transit time between the end of cervical portion (C1) and the C7 segment of ICA. The clinical prognosis was assessed with Matsushima grading system, moyamoya vessel reduction system, and modified Rankin Scale (mRS). The correlation between hemodynamic parameter and prognosis was analyzed. Subgroup analysis was conducted between different presentations and different ages. Fifty-one patients were identified and the mean imaging follow-up interval was 5.5 months. The ICA-MTT was increased after the combined revascularization ( P < 0.001) compared with contralateral ICA. Faster preoperative ICA-MTT was significantly associated with improved mRS in the ischemic group ( P = 0.05). The increased ICA-MTT was significantly associated with favorable neoangiogenesis ( P = 0.04), moyamoya vessel reduction (> 50%) ( P = 0.023), and improved mRS score ( P = 0.008). In subgroup analysis, the correlation in the ischemic subgroup and adult subgroup remained significant. In this cohort, the ICA-MTT increased after the combined EC-IC bypass, and there was a positive correlation between the increased blood transit time and favorable outcomes. Color-coding DSA proved to be useful as a quantitative and serial method to monitor postoperative courses after revascularization in MMD.

Comparing Subsurface Seasonal Deoxygenation and Acidification in the Yellow Sea and Northern East China Sea Along the North-to-South Latitude Gradient - Tian-qi Xiong; Qin-sheng Wei; Wei-dong Zhai; Cheng-long Li; Song-yin Wang; Yi-xing Zhang; Shuo-jiang Liu; Si-qing Yu (Frontiers in Marine Science, 2020)

Release from below- and aboveground natural enemies contributes to invasion success of a temperate invader - Yuan-Zheng Zhao; Ming-Chao Liu; Yu-Long Feng; Dong Wang; Wei-Wei Feng; Keith Clay; Lekeah A. Durden; Xiu-Rong Lu; Shuo Wang; Xiao-Lin Wei; De-Liang Kong (Plant and Soil, 2020)

QTL analysis of rice photosynthesis-related traits under the cold stress across multi-environments - Zhaoguo Wang; Shuo Wang; Chunhong Yu; Xiao Han; Detang Zou (Euphytica, 2020)

A remote sensing monitoring method for alpine grasslands desertification in the eastern Qinghai-Tibetan Plateau - Qian Kuang; Quan-zhi Yuan; Ji-chong Han; Rong Leng; Yu-shuang Wang; Ke-hong Zhu; Shuo Lin; Ping Ren (Journal of Mountain Science, 2020)

Low-temperature laminar flow ward for the treatment of multidrug resistance Acinetobacter baumannii pneumonia - Zhitao Gong; Jin Li; Hongliang Luo; Daqiang Zhan; Xuanhui Liu; Chuang Gao; Jinhao Huang; Yu Qian; Yiming Song; Wei Quan; Shuo An; Ye Tian; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Low-dose Roundup induces developmental toxicity in bovine preimplantation embryos in vitro - Wenyang Cai; Xiao Yang; Xiangchen Li; Hongtu Li; Shuo Wang; Zhengchao Wu; Mingxi Yu; Shiliang Ma; Shuang Tang (Environmental Science and Pollution Research, 2020)

AAV/BBB-Mediated Gene Transfer of CHIP Attenuates Brain Injury Following Experimental Intracerebral Hemorrhage - Shuo Zhang; Zheng-wei Hu; Hai-yang Luo; Cheng-yuan Mao; Mi-bo Tang; Yu-sheng Li; Bo Song; Yao-he Wang; Zhong-xian Zhang; Qi-meng Zhang; Li-yuan Fan; Yao Zhang; et al. (Translational Stroke Research, 2020)

Dopamine D2 Receptor-Mediated Modulation of Rat Retinal Ganglion Cell Excitability - Ning Yin; Yu-Long Yang; Shuo Cheng; Hong-Ning Wang; Xin Hu; Yanying Miao; Fang Li; Zhongfeng Wang (Neuroscience Bulletin, 2020)

Design and Experiment of a Plateau Data-Gathering AUV - Hao Xu; Guo-Cheng Zhang; Yu-Shan Sun; Shuo Pang; Xiang-Rui Ran; Xiang-Bin Wang (Journal of Marine Science and Engineering, 2019)
The design, control, and implementation of an autonomous underwater vehicle (AUV) for collecting hydrological information from plateau rivers and lakes are presented in this paper. The hardware and software structures of the control system were previously described. A novel sliding mode controller (SMC) with combinational reaching law of vertical hovering motion is proposed to improve the robustness and stability. The S-plane control, a nonlinear controller with little parameters, is used in the horizontal motion. Besides, the navigation strategy based on the dead-reckoning algorithm, a path tracking based on the light-of-sight (LOS) algorithm, and a control allocation strategy considering saturation are present. Finally, experiments were performed in a tank and in a river in the Qinghai–Tibet Plateau to prove the feasibility and reliability of the AUV system.

Selenium Attenuates Staphylococcus aureus Mastitis in Mice by Inhibiting the Activation of the NALP3 Inflammasome and NF-κB/MAPK Pathway - Junkun Ma; Shuo Zhu; Yingfang Guo; Meilin Hao; Yu Chen; Ying Wang; Mei Yang; Jianguo Chen; Mengyao Guo (Biological Trace Element Research, 2019)

A major QTL co-localized on chromosome 6BL and its epistatic interaction for enhanced wheat stripe rust resistance - Qingdong Zeng; Jianhui Wu; Shengjie Liu; Shuo Huang; Qilin Wang; Jingmei Mu; Shizhou Yu; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2019)

Correction to: Effects of Exogenous Spermidine and Elevated CO2 on Physiological and Biochemical Changes in Tomato Plants Under Iso-osmotic Salt Stress - Yi Zhang; Shuo Li; Ying Liang; Hailiang Zhao; Leiping Hou; Yu Shi; Golam Jalal Ahammed (Journal of Plant Growth Regulation, 2019)

Genetic architecture of wheat stripe rust resistance revealed by combining QTL mapping using SNP-based genetic maps and bulked segregant analysis - Jingmei Mu; Shuo Huang; Shengjie Liu; Qingdong Zeng; Miaofei Dai; Qilin Wang; Jianhui Wu; Shizhou Yu; Zhensheng Kang; Dejun Han (Theoretical and Applied Genetics, 2019)

Field-observation for an anticyclonic mesoscale eddy consisted of twelve gliders and sixty-two expendable probes in the northern South China Sea during summer 2017 - Yeqiang Shu; Ju Chen; Shuo Li; Qiang Wang; Jiancheng Yu; Dongxiao Wang (Science China Earth Sciences, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Effects of Exogenous Spermidine and Elevated CO2 on Physiological and Biochemical Changes in Tomato Plants Under Iso-osmotic Salt Stress - Zhang Yi; Shuo Li; Ying Liang; Hailiang Zhao; Leiping Hou; Shi Yu; Golam Jalal Ahammed (Journal of Plant Growth Regulation, 2018)

Origin of Early Cretaceous Guandian adakitic pluton in central eastern China: partial melting of delaminated lower continental crust triggered by ridge subduction - Ze-Bin Luo; Shuo Xue; Li-Peng Zhang; He Li; Cong-Ying Li; Hong Zhang; Yu-Long Liu; Ming-Xing Ling; Weidong Sun (International Geology Review, 2018)

Physiological Concentration of Prostaglandin E2 Exerts Anti-inflammatory Effects by Inhibiting Microglial Production of Superoxide Through a Novel Pathway - Shih-Heng Chen; Yueh-Feng Sung; Esteban A. Oyarzabal; Yu-Mei Tan; Jeremy Leonard; Mingri Guo; Shuo Li; Qingshan Wang; Chun-Hsien Chu; Shiou-Lan Chen; Ru-Band Lu; Jau-Shyong Hong (Molecular Neurobiology, 2018)

Unexpected dose response of HaCaT to UVB irradiation - Rong-Shing Chang; Chi-Shuo Chen; Ching-Lung Huang; Chiu-Ting Chang; Yujia Cui; Wei-Ju Chung; Wun-Yi Shu; Chi-Shiun Chiang; Chun-Yu Chuang; Ian C. Hsu (In Vitro Cellular & Developmental Biology - Animal, 2018)

Latent class analysis to evaluate performance of plasma cortisol, plasma catecholamines, and SHSQ-25 for early recognition of suboptimal health status - Yu-Xiang Yan; Li-Juan Wu; Huan-Bo Xiao; Shuo Wang; Jing Dong; Wei Wang (EPMA Journal, 2018)

Review of pre-processing technologies for ice cores - Wen-tao Du; Shi-chang Kang; Xiang Qin; Wei-jun Sun; Yu-lan Zhang; Yu-shuo Liu; Ji-zu Chen (Journal of Mountain Science, 2018)

Comparative genome-wide mapping versus extreme pool-genotyping and development of diagnostic SNP markers linked to QTL for adult plant resistance to stripe rust in common wheat - Jianhui Wu; Shuo Huang; Qingdong Zeng; Shengjie Liu; Qilin Wang; Jingmei Mu; Shizhou Yu; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2018)

SNP-based pool genotyping and haplotype analysis accelerate fine-mapping of the wheat genomic region containing stripe rust resistance gene Yr26 - Jianhui Wu; Qingdong Zeng; Qilin Wang; Shengjie Liu; Shizhou Yu; Jingmei Mu; Shuo Huang; Hanan Sela; Assaf Distelfeld; Lili Huang; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2018)

Long-term (≥20 years) application of fertilizers and straw return enhances soil carbon storage: a meta-analysis - Yu’e Li; Shengwei Shi; Muhammad Ahmed Waqas; Xiaoxia Zhou; Jianling Li; Yunfan Wan; Xiaobo Qin; Qingzhu Gao; Shuo Liu; Andreas Wilkes (Mitigation and Adaptation Strategies for Global Change, 2018)

Transport of Escherichia coli phage through saturated porous media considering managed aquifer recharge - Wenjing Zhang; Shuo Li; Shuang Wang; Liancheng Lei; Xipeng Yu; Tianyi Ma (Environmental Science and Pollution Research, 2018)

Rapid identification of an adult plant stripe rust resistance gene in hexaploid wheat by high-throughput SNP array genotyping of pooled extremes - Jianhui Wu; Shengjie Liu; Qilin Wang; Qingdong Zeng; Jingmei Mu; Shuo Huang; Shizhou Yu; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2018)

Variations of Laohugou Glacier No. 12 in the western Qilian Mountains, China, from 1957 to 2015 - Yu-shuo Liu; Xiang Qin; Ji-zu Chen; Zhen-lin Li; Jing Wang; Wen-tao Du; Wan-qin Guo (Journal of Mountain Science, 2018)

A Three-Day Consecutive Fingolimod Administration Improves Neurological Functions and Modulates Multiple Immune Responses of CCI Mice - Chuang Gao; Yu Qian; Jinhao Huang; Dong Wang; Wanqiang Su; Peng Wang; Linyue Guo; Wei Quan; Shuo An; Jianning Zhang; Rongcai Jiang (Molecular Neurobiology, 2017)

Petrogenesis of Luchuba and Wuchaba granitoids in western Qinling: geochronological and geochemical evidence - Juanjuan Kong; Yaoling Niu; Meng Duan; Yu Zhang; Yan Hu; Jiyong Li; Shuo Chen (Mineralogy and Petrology, 2017)

Crustal accretion and reworking processes of micro-continental massifs within orogenic belt: A case study of the Erguna Massif, NE China - ChenYang Sun; Jie Tang; WenLiang Xu; Yu Li; Shuo Zhao (Science China Earth Sciences, 2017)

Deletion of mammalian sterile 20-like kinase 1 attenuates neuronal loss and improves locomotor function in a mouse model of spinal cord trauma - Pan-feng Wang; Da-yuan Xu; Yuntong Zhang; Xiao-bin Liu; Yan Xia; Pan-yu Zhou; Qing-ge Fu; Shuo-gui Xu (Molecular and Cellular Biochemistry, 2017)

Association of GWAS-Reported Variant rs11196288 near HABP2 with Ischemic Stroke in Chinese Han Population - Shao-hua Li; Chang-he Shi; Yu-sheng Li; Fang Li; Mi-bo Tang; Xin-jing Liu; Shuo Zhang; Zhi-lei Wang; Bo Song; Yu-ming Xu (Journal of Molecular Neuroscience, 2017)

Petrogenesis of granitoids in the eastern section of the Central Qilian Block: Evidence from geochemistry and zircon U-Pb geochronology - Jiyong Li; Yaoling Niu; Shuo Chen; Wenli Sun; Yu Zhang; Yi Liu; Yuxin Ma; Zhenxing Hu; Guorui Zhang (Mineralogy and Petrology, 2017)

Toxic effect on the membrane system and cell proliferation of Prorocentrum donghaiense caused by the novel algicidal fungus Talaromyces purpurogenus YL13 - Wanjiao Shu; Ling Zhao; Shaoling Hou; Qiming Jimmy Yu; Shuo Tan; Pinghe Yin (Journal of Applied Phycology, 2017)

Isolation and characterization of microsatellite loci for Phragmites australis - SHUO YU; YU-XUAN ZHANG; YONG-LI REN; QI-XIANG SUN (Journal of Genetics, 2016)

The PI3K/Akt/mTOR pathway regulates the replicative senescence of human VSMCs - Pan Tan; Yan-Jiao Wang; Shuang Li; Yi Wang; Je-Yu He; Yi-Yin Chen; Hui-Qian Deng; Wu Huang; Jun-Kun Zhan; You-Shuo Liu (Molecular and Cellular Biochemistry, 2016)

Is CO2 emission a side effect of financial development? An empirical analysis for China - Yu Hao; Zong-Yong Zhang; Hua Liao; Yi-Ming Wei; Shuo Wang (Environmental Science and Pollution Research, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Optimization of the Expression Conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by Response Surface Methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Occurrence, compositional distribution, and toxicity assessment of pyrethroid insecticides in sediments from the fluvial systems of Chaohu Lake, Eastern China - Ji-Zhong Wang; Ya-Shu Bai; Yakton Wu; Shuo Zhang; Tian-Hu Chen; Shu-Chuan Peng; Yu-Wei Xie; Xiao-Wei Zhang (Environmental Science and Pollution Research, 2016)

On the origin of mafic magmatic enclaves (MMEs) in syn-collisional granitoids: evidence from the Baojishan pluton in the North Qilian Orogen, China - Shuo Chen; Yaoling Niu; Wenli Sun; Yu Zhang; Jiyong Li; Pengyuan Guo; Pu Sun (Mineralogy and Petrology, 2015)

Increased brain iron deposition is a risk factor for brain atrophy in patients with haemodialysis: a combined study of quantitative susceptibility mapping and whole brain volume analysis - Chao Chai; Mengjie Zhang; Miaomiao Long; Zhiqiang Chu; Tong Wang; Lijun Wang; Yu Guo; Shuo Yan; E. Mark Haacke; Wen Shen; Shuang Xia (Metabolic Brain Disease, 2015)

Optimization of the expression conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by response surface methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2015)

Residues of organophosphorus insecticides in sediment around a highly eutrophic lake, Eastern China - Yaketon Wu; Shuo Zhang; Chen Ren; Yu-Wei Xie; Xiao-Wei Zhang; Samuel O. Sojinu; Tian-Hu Chen; Ji-Zhong Wang (Journal of Soils and Sediments, 2015)

Identification of a potential novel type of influenza virus in Bovine in China - Wen-Ming Jiang; Su-Chun Wang; Cheng Peng; Jian-Min Yu; Qing-Ye Zhuang; Guang-Yu Hou; Shuo Liu; Jin-Ping Li; Ji-Ming Chen (Virus Genes, 2014)

Identification of four genotypes of H3N2 swine influenza virus in pigs from southern China - Jidang Chen; Xinliang Fu; Ye Chen; Shuyi He; Yun Zheng; Zhenpeng Cao; Wenxin Yu; Han Zhou; Shuo Su; Guihong Zhang (Archives of Virology, 2014)

Genotypic diversity of an invasive plant species promotes litter decomposition and associated processes - Xiao-Yan Wang; Yuan Miao; Shuo Yu; Xiao-Yong Chen; Bernhard Schmid (Oecologia, 2014)

Gene expression profiles in intracranial aneurysms - Lanbing Yu; Jinghan Fan; Shuo Wang; Dong Zhang; Rong Wang; Yuanli Zhao; Jizong Zhao (Neuroscience Bulletin, 2014)

Omni-directional distribution patterns of montane coniferous forest in the Helan Mountains of China - Yu Pang; Bai-ping Zhang; Fang Zhao; Yong-hui Yao; Shuo Zhang; Wen-wen Qi (Journal of Mountain Science, 2013)

Formation and mitigation of heterocyclic aromatic amines in fried pork - Yan Zhang; Chundi Yu; Jingbo Mei; Shuo Wang (Food Additives & Contaminants: Part A, 2013)

The migratory history of anadromous and non-anadromous tapertail anchovy Coilia nasus in the Yangtze River Estuary revealed by the otolith Sr:Ca ratio - Shuo-Zeng Dou; Kazuki Yokouchi; Xin Yu; Liang Cao; Mari Kuroki; Tsuguo Otake; Katsumi Tsukamoto (Environmental Biology of Fishes, 2012)

Elemental signature in otolith nuclei for stock discrimination of anadromous tapertail anchovy (Coilia nasus) using laser ablation ICPMS - Shuo-Zeng Dou; Yosuke Amano; Xin Yu; Liang Cao; Kotaro Shirai; Tsuguo Otake; Katsumi Tsukamoto (Environmental Biology of Fishes, 2012)

Autopoiesis and Interpretive Semiosis - Shuo-yu Charlotte Wu (Biosemiotics, 2011)

Twenty-three microsatellite loci for Styrax confusus and Styrax japonicus (Styracaceae) - Xiao-Yan Wang; Shuo Yu; Min Liu; Qing-Song Yang; Xiao-Yong Chen (Conservation Genetics Resources, 2010)

Isolation and characterization of polymorphic microsatellite markers in Metasequoia glyptostroboides (Taxodiaceae) - Min-Yan Cui; Shuo Yu; Min Liu; Yuan-Yuan Li (Conservation Genetics Resources, 2010)

Development and characterization of microsatellite loci in Ruppia maritima L. (Ruppiaceae) - Shuo Yu; Min-Yan Cui; Bin Liu; Xiao-Yan Wang; Xiao-Yong Chen (Conservation Genetics Resources, 2009)

Paracrine action mediate the antifibrotic effect of transplanted mesenchymal stem cells in a rat model of global heart failure - Lili Li; Shuo Zhang; Yao Zhang; Bo Yu; Yan Xu; ZhenZhong Guan (Molecular Biology Reports, 2009)

Tolerance and accumulation of lead by species of Iris L. - Yu-Lin Han; Su-Zhen Huang; Ji-Guang Gu; Shuo Qiu; Jie-Min Chen (Ecotoxicology, 2008)